Metal–organic frameworks as next-generation preservation platforms for postharvest fruits and vegetables: Gas regulation, antimicrobial control, bioactive delivery, and intelligent monitoring - Hao Shi; Min Zhang; Arun S. Mujumdar; Luming Rui (Postharvest Biology and Technology, 2027)

Stabilisation of aeolian sand with geopolymer and fines for use as pavement foundation - Rui Chen; Hai Chen; Xiaoding Ke; Ruoyu Hao; Yixian Wang (European Journal of Environmental and Civil Engineering, 2026)

Undesirable risks of ozone-resistant bacteria (ORB): biofilm formation potentials and control strategy - Hao-Bin Wang; Yin-Hu Wu; Yuan Bai; Zhuo Chen; Rui-Ning Wang; Han Liu; Nozomu Ikuno; Nakata Koji; Hong-Ying Hu (Water Research, 2026)

Comparative analysis of product distribution and kinetics in steam gasification of rice straw under atmospheric and pressurized conditions - Deming Zhang; Mingshui Ma; Hao Bai; Rui Zhou; Zhenguo Li; Yiqing Yao (Biomass and Bioenergy, 2026)

DSAP-WeedNet: A Down-Scale Attention-Guided Lightweight Network for Real-Time Weed Detection Enabling Precision Control in Potato Fields - Lei Han; Yi-Teng Wu; Ke-Jun Fan; Rui-Feng Wang; Wen-Hao Su (Potato Research, 2026)

L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Role of glutamine in promoting the proliferation and chondrogenic differentiation of ATDC5 cells: based on transcriptomic analysis - Rui-hao Zhang; Wen-huan Yuan; Ze-long Wang; Qi-rui Yang; Yi Sun; Quan-nian Shao; Wen-ji Wang; Jing Wang (Molecular Biology Reports, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Genomic characterization of historical Jinlingnan individuals: insights into genetic continuity and trans-Eurasian signals in eastern China - Shuyi Li; Yuchun Wang; Qu Shen; Jinguo Zan; Mengying Han; Zishuai Huang; Rui Wang; Xinyi Wang; Haifeng He; Le Tao; Hao Ma; Kongyang Zhu; et al. (Human Genetics, 2026)

Model tests on the evolution characteristics and aggravation effects of seepage erosion in shield tunnels under train vibration - Hui-Hao Chen; Dong-Mei Zhang; Xiao-Chuang Xie; Xue-Liang Zhang; Si-Rui Chen; Jie Yang (Tunnelling and Underground Space Technology, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Organic amendments induce crop-specific soil biotic homogenization associated with SOC sequestration: Evidence from a 35-year intercropping experiment - Guizong Zhang; Jiudong Zhang; Rui-Peng Yu; Hao Yang; Xingguo Bao; Wenju Liang; Qi Li; Long Li (Soil and Tillage Research, 2026)

Negative regulation of seed germination in Medicago truncatula by the lncRNA MtCIR1 under salt stress is associated with alternative splicing - Rui Tian; Xiaohan Sun; Mingui Zhao; Wen-Hao Zhang (Plant Science, 2026)

Identification and transcriptional analysis of eight C1q genes in Takifugu obscurus during bacterial infection - Hao Wu; Ding-Yi Chen; Xiao-Han Li; Rui Shen; Zhe Zhao; Ying Huang (Fish & Shellfish Immunology, 2026)

Association of combined exposure to polycyclic aromatic hydrocarbons, BTX and metals with metabolic syndrome risk - Xiaoyu Hao; Xiangkai Zhao; Zhiguang Gu; Bin Yang; Di Zhang; Rui Zhao; Xu Guo; Zhe Cheng; Gang Wang; Xiaohui Li; Junfeng Zhao; Zhiheng Li; et al. (Environmental Pollution, 2026)

Managing nitrate pollution in mixed land-use watersheds: source attribution and removal revealed by isotopes and 15N pairing - Jian Zhang; Hao Jiang; Yanping Li; Wenshi Zhang; Wenlu Lan; Junlin Shu; Xin Luo; Rui Zhang; Ke Pan (Ecological Engineering, 2026)

Built-in electric field for synergistically regulating electronic structure and interfacial hydrogen-bond network toward ampere-level current anion exchange membrane water electrolysis - Yujie Liang; Xinyu Lao; Jiaying Zhang; Hao Feng; Rui Min; Jingjing Wang; Yingying Zheng; Jiaqi Pan; Chaorong Li; Jun Cao (Chemical Engineering Journal, 2026)

Design of a biomimetic walking wheel inspired by reindeer hoof morphology and its snow-terrain locomotion performance - Kaixiang Chen; Rui Zhang; Mingxi Yu; Huailiang Wang; Hao Pang; Lige Wen (Cold Regions Science and Technology, 2026)

Organic amendment quality and quantity govern microbial necromass contributions to soil carbon sequestration: a meta-analysis - Jiaqi Hao; Mengdi Wang; Yiting Chen; Hui Xia; Hailin Zhang; Pete Smith; Yapeng Jiao; Binbin Cao; Yan Gao; Jianglan Shi; Xiangtian Meng; Rui Yin; et al. (Soil Biology and Biochemistry, 2026)

Boron-mediated pectin demethylesterification improves Na+ retention in root cell wall and alleviates salt stress in Brassica napus L. - Yu Yang; Wenjing Hao; Rui Jing; Xiaolei Feng; Diqing Yin; Muhammad Riaz; Mu Lu; Yusheng Niu; Lei Yan (Plant Science, 2026)

White mica as an exploration vector for Archean gold deposits: Integration of in-situ chemistry and SWIR spectroscopy at Kanowna Belle and Sunrise Dam, Western Australia - Yi-Hao Liu; Rui Wang; Dan-Ya Zhou; Yun Zhao (Journal of Geochemical Exploration, 2026)

A review of the mechanism, modification strategies and recent advances of piezocatalysis - Ying Cheng; Yue Cheng; Sa Li; Weichang Hao; Rui Guo (Journal of Environmental Chemical Engineering, 2026)

Magnetic composite-enhanced micro-pressure swirl reactor for municipal wastewater treatment: Performance and microbial community characteristics at different HRTs - Shengshu Ai; Jiayi Cao; Rui Hao; Yimin Wang; Yongtai Gao; Shangjing Zeng; Dejun Bian (Journal of Environmental Chemical Engineering, 2026)

Electronic, optical and mechanical properties, and photocatalytic water splitting of Janus ZrHfCO2 under biaxial strain: First-principles prediction - Rui-Wen Yan; Hao Zhang; Xiao-Hong Li; Rui-Zhou Zhang; Hong-Ling Cui (Journal of Environmental Chemical Engineering, 2026)

Transient geomorphic processes revealed by luminescence sensitivity of Yellow River terrace sediments - Ya Liu; Zheng-Hao Gu; Jia-Fu Zhang; Xue Rui; Yu-Jie Guo; Song-Xi Du; Yu-He Shen; Qing-Hao Ma (Geomorphology, 2026)

Beyond flavor: dietary vanillyl alcohol, a D₂ receptor antagonist promoting sleep - Lijing Zhang; Yujie Yang; Dongmei Yang; Richard Ward; Zhenshuai Hu; Hao Chen; Mengli Lan; Cheng Xiang; Su An; Jiameng Dai; Ying Zhu; Xianrun Sun; et al. (Food Research International, 2026)

Electrospun films prepared by incorporating modified ZnO nanoparticles-stabilized Pickering emulsions into polyvinyl alcohol and chitosan for active antibacterial packaging - Hao Wang; Ziyi Li; Hui Li; Lingna Meng; Rui Bai; Simin Li; Haibei Chi; Yuxing Xu (Food Research International, 2026)

Fermentation of ginseng juice by Lactiplantibacillus plantarum SP055 and Limosilactobacillus fermentum LB-9: Fermentation characteristics and ginsenoside biotransformation pathways - Jianwei Zang; Wei Liu; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Yimeng Kou; Chunling Meng; Jiamin Xu; Tao Lin; Xin Rui; Dan Gan; et al. (Food Microbiology, 2026)

Yield advantage in wide strip intercropping: Border-row effects and adding a third crop in double relay intercropping - Hao Yang; Huai-Ying Ma; Yi-Wen Zhao; Jiu-Dong Zhang; Gui-Zong Zhang; Jia-Kang Lu; Ya-Xian Huang; Xing-Guo Bao; Rui-Peng Yu; Wopke van der Werf; Long Li (Field Crops Research, 2026)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

How plant diversity and nitrogen deposition affect the net nutrient retention on temperate extensive green roofs: A case study - Guang Hao; Yihan Wang; Hechen Li; Shaobo Gao; Runze Wu; Zhuolin Li; Jiale Han; Hongyuan Li; Rui Hua; Nan Yang (Ecological Engineering, 2026)

Ecological risks of olivine with different particle sizes and dosages on planktonic ecosystems during ocean alkalinization - Zi-Rui Ding; Xin-Ming Wu; Ping Li; Xin-Yu Qian; Chang Liu; Ming-Hao Yin; Chun-Feng Qu; Zhihan Cao; Jinho Jung; Ling Liu; Zhi-Hua Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Smart responsive heterojunction hydrogel for synergistic therapy to promote drug-resistant diabetic wound repair and tissue regeneration - Zhiyang Ren; Rui Liu; Zhifu Liu; Xiaohan Zhang; Tianxin Wang; Lulu Chu; Wenjie Wang; Hao Wang (Chemical Engineering Journal, 2026)

Flower-like PtCuTe nanozymes for synergistic photothermal and Fenton-like antibacterial therapy in infected wound healing - Ding Luo; Ji Cheng; Hao Zhang; Rui Liu; Hanjing Lu; Xudong Liu; Yuji Weng; Yunjun Zhang; Jianli Liu; Xiangyan Meng; Jinghua Li; Qi Lv; et al. (Chemical Engineering Journal, 2026)

Transparent, bio-based dielectric films with ultrahigh breakdown strength fabricated from hydrogen-bonded cellulose acetate and tannic acid for energy storage - Rui Luo; Xin-rui Xiao; Zhe-hao Kang; Chao-qun Wu; Ting Huang; Nan Zhang; Yong Wang (Carbohydrate Polymers, 2026)

Synergistic Effect of Indole-3-Acetic Acid and Homogeneously Dispersed Ulva prolifera-Derived Carbon Quantum Dots in Enhancing CO2 Fixation, Biomass Production, and Macromolecules in Chlorella vulgaris - Chuande Liu; Hao Chen; Yuye Jiang; Rui Zhang; Linzhu Peng; Shuang Wang; Esakkimuthu Sivakumar (Bioresource Technology, 2026)

Sustainable valorization of agricultural waste into high-value aromatics via an integrated chemo-enzymatic strategy - Fang Gao; Shike She; Yaxin Wang; Mengyao Hao; Ming Wu; Yacheng Cao; Dong Zhu; Liping Shi; Liang Zhang; Rui Zhu (Biomass and Bioenergy, 2026)

A machine learning hail recognition method integrating DBSCAN clustering and spatiotemporal tracking - Yunong Guan; Chunguang Yin; Bin Wu; Haixing Gong; Siyu Zhu; Jiakai Zhu; Rui Shi; Hao Sun (Atmospheric Research, 2026)

A cross-city assessment method for street greenery equity based on the green landscape index - Jiayu Ge; Hao Chen; Xiaoping Rui; Yingxing Chen; Yiying Liu; Yunqiang Zhu (Urban Ecosystems, 2026)

Modulating local structural disorder in layered cathodes with alternating edge- and face-sharing octahedra for enhanced high-rate performance - Chengjun Fan; Xiaoxia Yang; Lingling Yao; Qin Wang; Xiao Ouyang; Leidang Zhou; Zhiwen Gao; Rui Jia; Xibang Chen; Jing Chen; Hao Liu; Bin Liao; et al. (Chemical Engineering Journal, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Bone biochar as a bifunctional catalyst for sustainable co-removal of nitrate and phosphate in constructed wetlands - Tao Liu; Hao Qin; Sihan Li; Gongliang Zhang; Rui Wang; Yi Sun; Haihua Wu; Yuxin Zeng; Yi Chen (Water Research, 2026)

Nanoconfinement-enhanced peroxymonosulfate activation by Co single atoms in hollow mesoporous carbon: Roles of active-site chemistry and mesoscale confinement - Hao Luo; Junli Zheng; Jiaxin Liu; Junjun Ma; Rui He; Chuqi Huang; Rong Xie; Qintie Lin (Water Research, 2026)

Transcriptome and metabolome analysis reveals that cuproptosis in bovine cumulus cells triggers the intercellular transmission of senescence and mitochondrial dysfunction to impair oocyte quality - Hong Xu; Tian Tian; Dan Xu; Xiaoxue Du; Rui Su; Jinghong Liang; Ying Liu; Yuqing Zhang; Chang Liu; Shuang Liang; Qingying Li; Deli Ding; et al. (Theriogenology, 2026)

Thaw slump susceptibility assessment in the central Qinghai–Tibet Plateau permafrost region based on an interpretable 2D-CNN framework with SBAS-InSAR deformation - Yuting Yang; Rui Wang; Chen Liu; Xia Hu; Jifu Liu; Lianyou Liu; Xiaoyan Li; Hao Zheng (Journal of Hydrology, 2026)

Divergent effects of biodegradable and conventional microplastics on denitrification in soils: Mechanisms governing N₂O emission and product stoichiometry - Hao Zhang; Xiao Li; Minhang Zhu; Rui Wang; Jinbo Zhang; Christoph Müller; Rui Jiang (Journal of Hazardous Materials, 2026)

Environmentally relevant imidacloprid exposure elicits hippocampal microglial apoptosis via JNK-FOXO3 pathway: Implication for latent central neurotoxicity - Xinyi Wen; Meiyan Li; Zhongyuan Zhang; Jingwen Wang; Hao Hu; Weihong Wang; Jing Jin; Kairong Wang; Jian Sun; Rui Zhang (Journal of Hazardous Materials, 2026)

Lactobacillus helveticus MB2-1 powders prepared using different drying strategies reshape dominant intermolecular interaction patterns and structural network formation during fermentation of coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Yibo Shi; Xiaotong Hao; Shiyuan Feng; Chunling Meng; Jiamin Xu; Di Yu; Tao Lin; Kai Ma; Changliang Zhang; Mingsheng Dong; et al. (Food and Bioproducts Processing, 2026)

Natural resource accounting for urban ecosystem: A case study in Central China based on the System of Environmental-Economic Accounting - Hao Zhang; Yanwen Wang; Rui Qi; Chao He; Mingmei Yang; Yuanyuan Cai; Guohui Chai (Ecological Economics, 2026)

Hydro-mechanical modeling of gas–water two-phase migration in fractured shale reservoirs by combining discrete hydraulic fractures with multi-continuum representation - Rui Yang; Hao Yang; Yunfei Du; Tianran Ma; Dachao Qi; Hongzhou Du (Computers and Geotechnics, 2026)

Stress-homogenized and solvation-regulated biomass hydrogel inducing Zn (101) epitaxial growth for ultra-stable anodes - Aoxue Lang; Yongfa Huang; Tingzhen Li; Rui Zhong; Linxuan Su; Zhendong Liu; Jianyun Gan; Ren Zou; Yuan He; Emmanuel Iwuoha; Usisipho Feleni; Kasim Ocakoglu; et al. (Chemical Engineering Journal, 2026)

Environment-responsive multi-enzymed Cu/Cu2O@NC nanorhombic nanoplatform for infected wound antimicrobial treatment - Ji Cheng; Hao Zhang; Yueting Jiang; Zuojia guo; Rui Liu; Xiantao Lin; Hanjin Lu; Yunjun zhang; Wenxuan Fan; Ding Luo; Jinghua Li (Chemical Engineering Journal, 2026)

Surface phosphate functionalization regulates electron polaron and glycerol oxidation pathway for dihydroxyacetone production over BiVO4 photoanodes - Songying Qu; Baiyi Li; Mingcong Wang; Zhanghong Zhou; Rui Zhao; Hao Wu (Chemical Engineering Journal, 2026)

Mesoporous carbon nanospheres-confined ZnMn2O4/Mn3O4 heterostructures for sustainable zinc-ion storage - Ling-Xin Kong; Songtao Zhang; Yaxun Hu; Peng Liu; Wanchang Feng; Zefan Sang; Xiaotian Guo; Hao Gong; Rui Wang; Dae Joon Kang; Huan Pang (Chemical Engineering Journal, 2026)

Tick-type Schottky contact engineering via Ni-CoOx interlayer for enhanced electron transfer in PEM water electrolyzers - Weiding Wang; Kaini Zhang; Hao Wang; Rui Zhao; Chuanjie Lin; Luning Li; Xinzhe Li; Jinzhan Su; Liejin Guo (Chemical Engineering Journal, 2026)

Wearable multifunctional conductive fabrics for integrated smart monitoring and protection of the human body - Miao Miao; Wendi Liu; Wuwei Bao; Rui Ma; Hao Yao; Zhenzhe Huang; Zixuan Lin; Ying Han; Wentao Shen; Yao Wang; Yifan Cui; Xinyang He (Chemical Engineering Journal, 2026)

Spatiotemporal dynamics of land degradation in the three gorges reservoir area and its coupling mechanisms with biodiversity and human activity intensity - Cuicui Ji; Hao Cui; Rui Ma; Dandan Ke; Xia Li; Fenglei Han; Xizeng Huang; Jie Liu; Gang Yang; Liejian Wang (CATENA, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Effects of Compound Yeast Culture on the Intestinal Morphology, Intestinal Function, and Microorganisms of Weaned Lambs - Shixiong Liu; Puguo Hao; Hui Chen; Xueqiang Li; Xiaohui Xu; Rui Du; Chen Xue; Lan Yang; Dacheng Liu (Probiotics and Antimicrobial Proteins, 2026)

Oxygen demand and behavioral responses of adult largemouth bass (Micropterus salmoides) to intensive aquaculture-related drivers - Hao Fan; Chang Guo; Xiang Lei; Peng Wan; Ming Zhu; Deqing Wang; Rui Song (Aquacultural Engineering, 2026)

An energy-spectrum-biased auto-importance sampling method for variance reduction in Monte Carlo energy spectrum simulations - Yang Zhou; Hui Zhang; Zhen Wu; Yisheng Hao; Rui Qiu; Jiajun Wu; Jiahe Shang; Junli Li (Annals of Nuclear Energy, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Paleoclimate and sediment provenance evolution revealed by terrestrial geochemical records from the carboniferous–cretaceous liupanshan basin, northwestern China - Qi-Fang Zheng; Rui Zhao; Shi-Qiang Xia; Yu-Zhou Zheng; Dao-Qing Zhou; Xing-Zhong Hao (Applied Geophysics, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Hierarchical regulation and molecular functions of co-transcriptional splicing - Rui Niu; Aiming Zhang; Michael G. Rosenfeld; Xiang-Dong Fu; Yajing Hao (Science Bulletin, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Toddacoumalins A-J, ten undescribed coumarins from the roots of Toddalia asiatica - Feng Wu; Han Yao; Xin-Rui Liao; Nan An; Xing-Shu Li; Wen-Hao Hu; Albert S.C. Chan; Hou-Jin Li; Wen-Jian Lan (Phytochemistry, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Long-term variations and formation drivers of PM2.5 nitrate in a megacity of Guanzhong Plain, China: Implications for air quality management - Liang Wen; Yan Yang; Yujie Zhang; Jiaying Feng; Rui Gao; Wei Guo; Shengnan Guo; Hao Wang; Fahe Chai; Hartmut Herrmann; Andreas Tilgner; Thomas Schaefer; et al. (Journal of Environmental Sciences, 2026)

Numerical simulation and synergistic NOx reduction of preheated combustion in a 660 MW tangential-fired boiler under variable loads - Rui Ju; Hao Lu; Wenjun Zhao; Chuanxiao Zheng; Huachen Liu; Heng Hu (Fuel, 2026)

Co-fermentation of Ampelopsis grossedentata with Camellia sinensis reduces bitterness, enhances sweet aroma, and generates novel bioactive theaflavin analogues - Si-Rui Li; Zi Yang; Na Song; Jia-Yi Li; Yu-Xing Zhang; Hao Li; Peng Zhang; Yu-Lan Song; Yu Sun; Kun Qian; Da-Wei Zhang; Guan-Hu Bao (Food Chemistry, 2026)

Lactiplantibacillus plantarum SP055 pretreatment attenuates experimental colitis in association with partial preservation of epithelial integrity and microbial-metabolic homeostasis - Jianwei Zang; Xiaotong Hao; Yibo Shi; Xia Fan; Yimeng Kou; Xiaogan Zhao; Qiaoya Mo; Di Yu; Jiamin Xu; Chunling Meng; Chang Xu; Luyao Xiao; et al. (Food Bioscience, 2026)

Catfish MyD88 mediates resistance to Aeromonas hydrophila infection through coordinated IL- and IFN-dependent signaling - Can Yang; Yanfang Wu; Qing Yang; Feiming Chen; Hong Yang; Jinwei Gao; Hao Wu; Zhenzhen Xiong; Jiayu Wu; Dongsheng Ou; Rui Song; Hao Feng (Fish & Shellfish Immunology, 2026)

Experimental study on seismic behaviour of full-scale glued laminated timber frame-glass wall composite structural unit - Tian Xia; Tao Zhou; Rui Xu; Hao Huang; Shao-Bo Kang (Engineering Structures, 2026)

Vibration-exacerbated suffusion in soils with different gradations: a coupled DEM–PNM study - Si-Rui Chen; Dong-Mei Zhang; Xue-Liang Zhang; Hui-Hao Chen; Zhao-Geng Chen; Xiao-Chuang Xie (Computers and Geotechnics, 2026)

The Matthew effect of defects in microflowers CuS/carbon foam composite optimizes the dielectric response for high-performance microwave absorption - Weibin Deng; Tiehu Li; Arooba Kanwal; Hao Li; Alei Dang; Keke Li; Peng Chang; Rui Zhou; Shengtao Gao; Yating Zhang; Hongjing Wu (Chemical Engineering Journal, 2026)

Microbial inoculation in green roofs: progress, challenges and ecological regulation strategies - Nan Yang; Hechen Li; Yihan Wang; Pingrui Jiang; Shaobo Gao; Hongyuan Li; Rui Hua; Xinjian Shi; Guang Hao (Urban Ecosystems, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Mitogenome assembly of the floating-leaved aquatic plant Nymphoides peltata provides insights into organellar evolution and aquatic adaptation in Asterales - Rui Dong; Meng-Na Yu; Lei Zhang; Si-Hao Wang; Xi-Ran Tong; Zhi-Zhong Li (Hydrobiologia, 2026)

CRISPR/Cas9 system inhibits largemouth bass virus infection in vitro and in vivo - Rui-Long He; Mao-sheng He; Xin-Yuan Jiang; Yi-Wang; Hao-Liang; Xiang-Yi Bu; Kun Xu; Fei Ling; Gao-Xue Wang; Hai-Feng Jiang (Aquaculture, 2026)

Acute Stress Drives Adaptive Anxiety via Excitatory-Inhibitory Imbalance in the Prefrontal-Amygdala Circuit in Male Mice - Jia-Xin Zou; En Cao; Zhi-Hao Wang; Rui Han; Xing-Yan Lu; Cheng-Yuan Huang; Xia Qin; Wei-Zhu Liu; Wen-Hua Zhang; Bing-Xing Pan (Neuroscience Bulletin, 2026)

Cross-species comparative transcriptomic analysis of spermatozoa reveals species-specific regulatory networks linked to fertilization-associated genes in cattle, sheep and goats - Yue Zhao; Linfeng Bai; Qiqi Jiang; Hao Xiao; Fangyuan Liu; Bilige Wuyun; Rihan Wu; Chunxia Hao; Rui Ding; Peng Yuan; Lizhi Wang; Ying Lu; et al. (Science China Life Sciences, 2026)

Two new protoflavonoids from Polytrichum commune and their cytotoxicity against human gastric cancer cells - Jing-jing Dong; Dan-rui Han; Hao Cheng; Xu-liu Shi; Dong-Lai Ma; Jian-kun Yan; Xu-Hong Duan (Natural Product Research, 2026)

Post-accretionary crustal growth and recycling in the Central Asian Orogenic Belt: new insights from Early Permian Bole rhyolites and regional zircon Hf mapping - Bo Liu; Zhi-Hao Xie; Rui-Xin Zhou; Xin-Yi Cheng; Ya-Nan Gong (International Geology Review, 2026)

Single-cell transcriptomic analysis identifies a MIF-driven keratinocyte-macrophage-Th2 axis as a key inflammatory circuit in atopic dermatitis - Yan Wei; Rui-Min Bai; Hao-Ran Guo; Jin Shan; Li-Juan Wang; Yan Zhou; Kuan-Hou Mou; Yan Zheng; Ya-Guang Zhang (Inflammation Research, 2026)

Diameter-independent indices for TBM rock-mass classification - Xiu-xiu Cao; Xu Li; Li-jie Du; Yu-zhi Zhang; Hao Cai; Yun-pei Zhang; Rui-lang Cao (Tunnelling and Underground Space Technology, 2026)

Flexotronic effect-triggered channel switching for high-sensitivity mechanical sensing - Jinwan Chen; Qing Zhao; Zhuangzhuang Zhang; Rui Ge; Hao Sun; Yongkang Zhang; Runze Yu; Longfei Wang; Shuhai Liu (Science Bulletin, 2026)

Revealing the rotational growth of carbon nanotubes by atmospheric environmental transmission electron microscopy - Rui-Hong Xie; Hao An; Lili Zhang; Zichu Zhang; Mengke Zou; Yinghui Pu; Bingsen Zhang; Feng Ding; Chang Liu (Science Bulletin, 2026)

Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

Research progress on the preparation, modification, and pollutant adsorption removal applications of waste tire pyrolysis char - Tao Wang; Lixin Qian; Rui Hao; Xiangjie Gao; Xiangyang Xu; Hexi Zhao; Hongming Long (Process Safety and Environmental Protection, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Rapid Early Miocene surface uplift of the Yarlung Tsangpo Suture Zone: Constraints from stable and clumped isotopes - Xiaohui Liu; Yimin Liu; Xudong Guo; Suoya Fan; Xiaoyu Guo; Wenxing Hao; Xingfu Huang; Xiaoming Shen; Qiuhua Ren; Ying Rao; Lin Ding; Rui Gao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

Lagged crop responses to drought across China: contrasting multivariate environmental pathways in rainfed and irrigated systems - Rui Yang; Litao Zhou; Hao Yuan; Xinyi Han; Jianhang Zhang; Jiayu Bao; Pengzhou Chen; Shichen Gao; Jianjun Wu (Journal of Environmental Management, 2026)

Distinct differences of rice grain quality caused by developmental stage and cultivar: A widely targeted metabolomics perspective - Xuexia Yuan; Pingxiang Liu; Rui Gao; Jingxiu Bi; Tong Zhao; Haining Hao; Xia Li; Yutao Wang (Food Chemistry, 2026)

A tropical fermented-food-derived Lactiplantibacillus plantarum SP055 alleviates DSS-induced colitis through coordinated regulation of gut microbiota and intestinal barrier function - Jianwei Zang; Yibo Shi; Xiaotong Hao; Xia Fan; Yimeng Kou; Wanxiang Zhang; Luyao Xiao; Chang Xu; Tao Lin; Xin Rui; Dan Gan; Wei Li (Food Bioscience, 2026)

Economic rhythms and green tides: Charting China's dual dividends through synergistic policies - Yu-Jie Hu; Rui Zhang; Ailing Luo; Yu Hao (Environmental Impact Assessment Review, 2026)

Hollow-structured Co3O4/CNTs as adsorbent for dispersive solid-phase extraction and sensitive detection of bisphenols - Yingge Hao; Huina Zhou; Mengying Xia; Yi Yuan; Rui Xiao; Minghua Lu (Chemical Engineering Journal, 2026)

Dynamic trajectories of health-related quality of life during neoadjuvant chemotherapy in breast cancer: differential effects of anthracycline-taxane sequencing - Yuanyuan Wang; Ye Wang; Hao Yao; Jingjing Ding; Yichun Gong; Junhan Li; Danni Shen; Rui Chen; Jue Wang; Xiaoming Zha (Science China Life Sciences, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

Modeling hiking speed via interpretable machine learning: Uncovering nonlinear impacts of multidimensional environmental factors - Hao Huang; Jin Yeu Tsou; Hao Zheng; Rui Ma; Haochen Shi; Botao Zhang (Applied Geography, 2026)

P2Y12-AMPKα2 signaling contributes to cardiomyocyte senescence in doxorubicin-induced heart failure - Qianqian Niu; Huidan Wang; Mengyao Zhao; Hongdou Zhang; Rui Hao; Peiyao Liu; Lijuan Guo; Bulei Chen; Yuting Xi; Peng Li; Yaling Yin (Molecular and Cellular Biochemistry, 2026)

Correction to: Puerarin alleviates myocardial ischemia-reperfusion injury by enhancing FUNDC1-mediated mitophagy - Na Feng; Anhua Zhang; Lingling Yao; Jie Tang; Min Lu; Dandan Shi; Zhuoran Zhu; Rui Liu; Jun Chen; Xinwen Min; Handong Yang; Hao Xu; et al. (Molecular and Cellular Biochemistry, 2026)

Hyperallometric Fecundity and Size-Dependent Egg Provisioning in the Yellowfin Goby (Acanthogobius flavimanus), a Short-Lived Estuarine Fish - Yupin Pu; Rui Ma; Hao Shi; Guanghui Fu (Fishes, 2026)
In highly variable estuarine environments, short-lived fishes must balance immediate reproduction against future growth, yet the reproductive role of maternal size remains poorly resolved. Here, we analyzed biological surveys of the yellowfin goby Acanthogobius flavimanus from Haizhou Bay, Yellow Sea, collected between 2023 and 2025, combining fecundity estimation, egg morphometry, histology, and size-structured reproductive-output modeling. Absolute fecundity scaled hyperallometrically with total length (β = 3.18, 95% CI: 3.05–3.31, R2 = 0.71, p 180 mm total length represented only 4.8% of abundance but contributed 18.5% of total standardized egg-production output under the assumptions of the model. Inter-annual monitoring further indicated a decline in mean body size and in the proportion of large individuals from 2023 to 2025, a pattern consistent with size truncation but requiring longer-term monitoring for causal attribution. These findings suggest that large females can contribute disproportionately to reproductive output even in a short-lived estuarine fish and support the inclusion of size structure in fisheries assessment and management.

A new seco -norlignan and a rare ring B aromatic 1(10→6) abeo -ergostane-type steroid from Tarlmounia elliptica - Qiao-Long Hao; Han-Mei Bai; Lei Miao; Shuang Yao; Chuan-Rui Zhang (Natural Product Research, 2026)

From addition to regulation: Lactic acid bacteria-driven interfacial mechanisms and spatial control in food bioactive packaging - Jianwei Zang; Yan Luo; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Luyao Xiao; Xin Rui; et al. (Trends in Food Science & Technology, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Duplex real-time qPCR assay targeting β-tubulin SNPs for detection of albendazole resistance in Haemonchus contortus - Xindi Chen; Lili Zhang; Tengyu Wang; Hao Zhang; Rui Wang; Jing Lu; Wa Gao; Wenlong Wang; Chunxia Liu (The Veterinary Journal, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

A long-afterglow-driven all-weather photocatalyst with indirect Z-scheme/Schottky heterojunction for marine antifouling and environmental disinfection - Qi’an Chen; Zhanping Zhang; Yuhong Qi; Miaomiao Ma; Xiwen Guan; Xufeng Zhang; Shukun Zhang; Jingyu Xu; Chuanjun Gu; Sinan Hao; Rui Zhang (Journal of Environmental Chemical Engineering, 2026)

A Ca-MOF@COF composite and its in situ grown gel membrane for highly efficient capture of Cd2+ - Xue-Mei Liu; Chuang-Chuang Zhang; Kun Yang; Wei-Liang Jin; Guan-Lian Mo; Rui Liu; Hong-Xin Jiang; Hao-Jie Cui; De-Ming Kong (Journal of Cleaner Production, 2026)

Genome-wide association study of wheat (Triticum aestivum L.) starch pasting properties - Jiahui Jiang; Hao Chang; Yongji Ma; Rui Jin; Rui Yu; Zhenhua Lu; Tianqi Bai; Yufeng Xu; Ruili Gou; Chengyu Lian; Wenting Zhang; Yingang Hu; et al. (Journal of Cereal Science, 2026)

Accessory minerals constrain anatexis and melt extraction in deep crust and implications for granite genesis - Wenxiang Zhang; Yujie Zhao; Bin Fu; Guangyan Zhou; Hao Wang; Rui Li; Zhaochu Hu; Yuanbao Wu (Geochimica et Cosmochimica Acta, 2026)

Influence of Pt-Cu synergistic action and TiO2 core–shell structure on NH3-SCO and anti-aging performance - Zhenhua Ji; Zhongqiang Bao; Zihao Wu; Peng Zhang; Rui Yang; Ding Luo; Hao Chen (Fuel, 2026)

Gallic acid-modified starch conjugates inhibit harmful aldehydes in fried battered fish: Based on structural characterization and antioxidant activity - Ying Li; Hao Zhang; Jiamu Kang; Meng Yang; Hanyu Liu; Wuyun Chen; Tingting Zhang; Deming Quan; Rui Zhang; Yuan Xia; Xin Du; Xiufang Xia (Food Research International, 2026)

Hydrophobization engineering in nitrile hydratase-nicotinamidase cascade system: Promoting multi-tunnel formation for enhanced niacin biosynthesis - Yinbiao Xu; Rui Wang; Chaofan Li; Yu Liu; Xinyue Zhang; Hao Fu; Zongda Chen; Pei Zhou; Yang Sun; Hua Li; Yupeng Liu (Chemical Engineering Journal, 2026)

Dependence of Fe2O3 crystal planes on CO oxidation performance for CuOx/Fe2O3 catalysts - Yuan She; Wenkang Niu; Rui Liu; Hao Meng; Changqing Peng; Xuanxuan Wang; Jiawei Qiang (Chemical Engineering Journal, 2026)

Pt decorated core-shell ZnS:Cu doped epoxy composites: Achieving enhanced breakdown strength and defect visualization - Zhi-Hao Xing; Ming-Xiao Zhu; Jian-Yi Xue; Jia Cheng; Guang Li; Bing Xia; Chongzi Cao; Yanbing Ji; Rui Liu (Chemical Engineering Journal, 2026)

Antimony precipitation processes of orogenic and magmatic-hydrothermal gold‑antimony systems in the West Qinling Orogen, China - Lian Zhang; Hao-Cheng Yu; Jie Wang; Rui Zhu; Lei Wang; Deng-Yang He; Jin-Hong Qiu; Jia-Hui Zhou; Kun-Feng Qiu (Chemical Geology, 2026)

High-Frequency Signal Recovery via the Constraint of Reflection Structure in f-x Domain - Chong Sun; Nan-ying Lan; Duo-ming Zheng; Hao-nan Tian; Shi-kai Jian; Lang Yang; Zhi-fang Ran; Rui-dong Liu (Applied Geophysics, 2026)

Puerarin alleviates myocardial ischemia-reperfusion injury by enhancing FUNDC1-mediated mitophagy - Na Feng; Anhua Zhang; Lingling Yao; Jie Tang; Min Lu; Dandan Shi; Zhuoran Zhu; Rui Liu; Jun Chen; Xinwen Min; Handong Yang; Hao Xu; et al. (Molecular and Cellular Biochemistry, 2026)

Position dependent elasticity of the anterior talofibular ligament in healthy young women: an in-vivo shear wave elastography study - Zili Chen; Wan Zhou; Hao Liang; Xing Liu; Yibo Li; Li Yang; Huijuan Xiang; Rui Du (European Journal of Applied Physiology, 2026)

Conservation tillage could achieve SOC accumulation of eroding farmland in black soil regions - Rui Qian; Lei Gao; Wei Hu; Junjie Liu; Hao Du; Xinhua Peng (Soil and Tillage Research, 2026)

Multivariate distribution modeling and cross-correlation spatial variability stochastic characterization for mechanical properties of marine clay - Hao Li; Rui Liu; Lipeng Liu; Tao Wang; Guoqing Zhou (Ocean Engineering, 2026)

Typology-based spatial modeling of urban block commercial vitality: Evidence from Shenzhen for land use planning - Chendi Yang; Hao Huang; Sian Meng; Yunjie Zhang; Jacqueline T.Y. Lo; Rui Ma (Land Use Policy, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Microbiota-responsive BmMBF2-11 limits dysbiosis and promotes intestinal immune homeostasis in the silkworm - Qingxiu He; Rui Yang; Huawei Liu; Huanan Zhu; Yu Zhang; Hao Chen; Qingsong Liu; Guangcheng Huang; Qingyou Xia; Ping Zhao (Insect Biochemistry and Molecular Biology, 2026)

Fish oil emulsion stabilized by multi-modified β-Lg improves lipid metabolism, inflammation, and hepatic–gut homeostasis in high-fat diet mice - Qingchun Zhang; Hao Zhu; Rui Wang; Weilin Liu; Jianfei He; Wei Tang; Jianhua Liu (Food Bioscience, 2026)

Physicochemical properties, antioxidant activity, antibacterial properties, and fruit preservation potential of black soldier fly chitosan films - Bin-Qiao Yuan; Ting-Hao Yu; Jun-Kui Huang; Xin-Rui Ren; Run-Jia Wang; Guo-Xin Huang; Nortoji A. Khujamshukurov; Da-Wei Huang; Jin-Hua Xiao (Food Bioscience, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

The modulation of glucose release from noodles through the addition of low methoxyl pectin and sodium alginate - Oni Yuliarti; Daryl Ho Zi Hao; Muhammed Tariq Dawood Batcha; Bek Rui Min (Food and Humanity, 2026)

Dynamic extracellular polymeric substance component succession primes cyanobacterial metabolism for distinct bloom stages - Kaikai Deng; Qiang He; Rui Yang; Fang Fang; Yuanchen Huo; Bin Chen; Hao Yang; Guijiao Lin; Peng Yan; Youpeng Chen; Jinsong Guo (Environmental Pollution, 2026)

Fluoride-ion mediated radical scavenging in a hydrophobic microenvironment for durable PEM fuel cells - Xuelin Wei; Gang Zhu; Donghao Ye; Aojie Zhang; Hao Zhang; Wangkai Zhu; Tian Tian; Shengqiu Zhao; Jiangping Song; Rui Chen; Haolin Tang (Chemical Engineering Journal, 2026)

Biotransport and biotransformation of arsenic in earthworm tissues: Advancing vermiremediation strategies of soil contamination - Yunxiang Xu; Muyuan Wang; Yizhao Wu; Yifan Zhang; Rui Jiang; Qi Zhao; Jibao Jiang; Hao Qiu; Yinsheng Li (Chemical Engineering Journal, 2026)

Tailoring pore architecture in hard carbons: Clarifying the distinct sodium storage roles of closed pores and ultra-micropores - Wei-wei Kang; Hai-tao Zeng; Guang-xu Huang; Jian-bo Jia; Qiang Li; Han Hu; Bing Xu; Wei-jie Guo; Rui Hao; Bao-lin Xing; Chuan-xiang Zhang (Chemical Engineering Journal, 2026)

A critical review of gaseous pollutants in vehicle cabin: Composition, characterization, and controlling standards - Hao Wang; Hong Ni; Qingling Liu; Rui Han; Qian Zhao; Caixia Liu (Atmospheric Environment, 2026)

Proteome profile analysis reveals regulatory mechanisms in the liver of Carassius auratus under short‐term salinity stress (10‰, 48 h) - Rui Zhao; Muhan Meng; Xiaolian Liu; Shuang Hao; Xin Luo; Ning Wu; Lin Ma; Sun Hongqing; Hongzheng You (Journal of Fish Biology, 2026)
Carassius auratus , a commercially important species in the ornamental aquarium industry, is sensitive to salinity fluctuations. In this study, 30 C. auratus of length 13.1 ± 2.9 cm and weight 103.8 ± 40.8 g/fish were placed into six plastic tanks (80 L) with five fish per tank. About 15 fish were exposed to 10‰ salinity for 48 h, while another 15 fish were kept in freshwater and continuously aerated (0‰) as a control. To investigate the effects of short‐term salinity stress (10‰, 48 h), proteomic profiling of the liver was conducted. Short‐term salinity stress resulted in 104 upregulated and 95 downregulated proteins in the liver of C. auratus . Gene ontology enrichment analysis indicated significant enrichment in areas such as proteolysis, nitrogen compound transport, cellular component, peptidase activity, acting on L‐amino acid peptides, endopeptidase activity, serine‐type peptidase activity and enzyme inhibitor activity. Furthermore, the Kyoto Encyclopedia of Genes and Genomes enrichment analysis identified mitogen‐activated protein kinase kinase kinase 7 (MAP3K7) as an essential regulated protein in the IL‐17 signalling pathway and glutamine synthetase (GS) in the arginine biosynthesis pathway. These findings suggest that short‐term salinity stress induces significant proteomic changes in C. auratus , with functional enrichment in peptide metabolism and enzyme regulation. Notably, MAP3K7 and GS may play crucial roles in coping with short‐term salinity stress, providing new insights into the proteomic regulatory mechanisms of C. auratus under short‐term salinity stress.

Integrated Transcriptomics and Machine Learning Reveal Lipid Metabolism Related Genes in Ischemic Stroke - Qiu-Lin Wang; Chang-Le Fang; Tian-Hao Bao; Rui-Ze Niu (Journal of Molecular Neuroscience, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Unveiling the “Glycolysis-Lactate-Lactylation” Axis: A Novel Target in Ischemic Cerebrovascular Disease - Yi Xie; Mengmeng Dai; Rui Liu; Ying Li; Hao Yan; Jiacheng Li; Xuantong Liu; Zhiyuan Yu; Shabei Xu; Wei Wang; Xiang Luo (Neuroscience Bulletin, 2026)
Ischemic cerebrovascular disease involves complex interactions between metabolic reprogramming and epigenetic regulation. Recent studies indicate that enhanced glycolysis and lactate accumulation under hypoxic conditions not only maintain cell viability by supplying energy but also participate in disease regulation through lactylation. Lactylation regulates gene expression, immune polarization, metabolic enzyme activity, and angiogenesis through epigenetic remodeling. In ischemic cerebrovascular disease, lactylation exerts dual roles: on one hand, it can induce neuronal death, exacerbate neuroinflammation, and form a vicious metabolic cycle; on the other hand, it can influence immune cell function and gene expression, thereby exerting neuroprotective effects. Accordingly, targeting lactate metabolism or lactylation-modifying enzymes holds considerable therapeutic potential. Nevertheless, the spatiotemporal regulation, synergistic effects, and broader physiopathological implications of lactylation warrant further in-depth investigation. This review systematically summarizes the role of the “glycolysis-lactate-lactylation” axis in the pathogenesis of ischemic cerebrovascular disease, and discusses its potential as a therapeutic target.

Data-driven assessment of nitrogen and phosphorus buffering capacity across 460 Chinese watersheds: Spatial patterns, drivers, and future projections - Yunfei Cao; He Yao; Chuang Zhang; Chaojun Gu; Lin Yang; Rui Hao; Xiao Li; Zhen Wang; Haibing Xiao; Jian Wang; Zhihua Shi (Water Research, 2026)

WaveCastNet-C: Forecasting the significant wave height in the China Sea with a fully convolutional neural network - Hao Dai; Zhihan Xie; Famei Lei; Xining Zhang; Guomei Wei; Rui Lin; Weijie Zhang; Shaoping Shang (Ocean Engineering, 2026)

Resilience assessment and enhancement of regional transportation system - Honghai Li; Rui Hao; Bin Yu (Journal of Transport Geography, 2026)

Integrating distributed hydrologic simulation with low-flow resilience: a spatiotemporal perspective - Yan Zhou; Chi Zhang; Rui Hao; Yongxin Liao; Wei Yin; Dianchang Wang (Journal of Hydrology, 2026)

Algal ecological dynamics tracking model for studying hydrodynamic impacts on algae transport and accumulation in a shallow lake - Fei Du; Xiaobo Liu; Shiyan Wang; Chang Liu; Aiping Huang; Weijie Wang; Budong Li; Rui Gao; Xin Tian; Zhen Han; Hao Fan; Bi Wu (Journal of Hydrology, 2026)

Evolution of groundwater nitrate during managed aquifer recharge: Insights from DOM characteristics and stable isotopes - Congchao Xu; Rui Li; Weiwu Hu; Liting Hao; Bowen Shi; Tianyu Zhang; Chuanping Feng; Nan Chen (Journal of Hazardous Materials, 2026)

Effect of Mo on ZnSO4 resistance over FeCe catalyst from vanadium slag for low-temperature NH3-SCR of NO - Yuan She; Hao Meng; Wenkang Niu; Changqing Peng; Junjie Wang; Xuanxuan Wang; Rui Liu; Zhifeng Ding (Journal of Environmental Chemical Engineering, 2026)

Revisit the improvement of coagulation pretreatment on ozonation performance: The critical roles of HO• and O3 for effluent organic matter transformation and micropollutant degradation - Rui Hu; Hao-Tong Zheng; Boxi Tang; Jialing Tu; Yu-Hong Cui; Xuedong Zhai; Gang Wen; Zheng-Qian Liu (Journal of Cleaner Production, 2026)

Ecosystem vertical structural complexity and soil nutrition synergistically enhance extreme drought resistance via water use efficiency in the Yangtze River Basin - Yue Cao; Xinyi Hao; Fei Yu; Rui Wang; Huiwen Li (Journal of Environmental Management, 2026)

Study on physicochemical properties and light-controlled antibacterial activity of side-by-side nanofiber films prepared by dual-channel electrospinning system - Hao Wang; Lingna Meng; Hui Li; Ziyi Li; Simin Li; Rui Bai; Haibei Chi; Xiaoge Wang (Food Research International, 2026)

Integrated design of thermally actuated metastructure for modulatable dual vibration isolation function - Yue Hu; Jianlei Zhao; Hao Zhou; Ivana Kovacic; Runan Hua; Honggang Li; Rui Zhu (Engineering Structures, 2026)

Characterizing on-road particle number emissions from container diesel trucks using interpretable machine learning - Rui-min Hao; Hong-di He; Hong-mei Zhao; Wen-jian Jia; Zhong-ren Peng; Hui Wang (Atmospheric Pollution Research, 2026)

Human Umbilical Cord-Derived Mesenchymal Stem Cells-Involved Strategies: Advancing Tendon Injuries Therapy Towards Clinical Translation - Mumin Cao; Mengze Tong; Yunmeng Pu; Xuepeng Lv; Yimin Sun; Haoyu Zhang; Renwang Sheng; Hao Wang; Yucheng Gao; Guangchun Dai; Fei Xiong; Qianqian Wang; et al. (Stem Cell Reviews and Reports, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Interactive effects of microplastics, heavy metals, and soil microecology under different irrigation water sources - Rui Yang; Lijuan Huo; Hao Yang; Yan Gong; Gaiqiang Yang; Shuting Tian; Shuhui Cao; Xia Li; Qingwei Ding; Yaqiong Fan; Qi Liu (Applied Soil Ecology, 2026)

Advancement and field evaluation of a honeysuckle harvesting robot with integrated clamping and air-suction mechanisms - Zhaoyu Rui; Zhao Zhang; Cunming Hao; Yingxin Jia; Zhenhuan Ye; Saddam Hussain; Mahmoud A. Abdelhamid; C. Igathinathane; Yiannis Ampatzidis (Computers and Electronics in Agriculture, 2026)

Faecalibacterium prausnitzii derived postbiotic attenuates PEDV-induced mitochondrial apoptosis through blocking viral entry - Lingcong Deng; Rui Luo; Shihan Yang; Letian Li; Nan Li; Yu Dong; Jiayi Hao; Ju Li; Anqi Deng; Xueyan Ai; Maopeng Wang; Chang Li (Veterinary Microbiology, 2026)

Assessment of genetic diversity and pathogenicity of porcine rotavirus A, and immunogenicity of a bivalent inactivated vaccine in southern China - Guangli Hu; Zhiqing Zhao; Liguo Gao; Rui Geng; Shengjin Liu; Hao Zhang; Yongchang Cao; Hanqin Shen; Chunyi Xue (Veterinary Microbiology, 2026)

Modeling and experimental validation of crack-induced bottom-side erosion effects in buried pipelines - Yan-Ning Wang; Tai-Kai Li; Jing-Rui Peng; Xin-Hao Min; Lin-Shuang Zhao (Tunnelling and Underground Space Technology, 2026)

From resistance to detection: The role of nanomaterials in plant stress responses - Jing-wan Zhang; Rui-Rui Hao; Abolghassem Emamverdian; Wen-Xun Su; Xing-Hao Zhang; Meisam Zargar; Mo-Xian Chen; Fu-Yuan Zhu (Plant Science, 2026)

Comprehensive analysis of Clade A PP2C family in poplar unveils PtrPP2C-9 as a negative regulator of osmotic stress tolerance through ABF3/GBF3 network - Yuan Zhang; Rui-Quan Wang; Xin-Yi Wang; Shu-Ying Wei; Hao Li; Shuang-Lian Deng; Jia-Hui Liu; Ting Wang; Liang-Hua Chen; Fang He (Plant Science, 2026)

Research on HaNRX, a potential RNAi target gene in Helicoverpa armigera - Rui Han; Dongdong Chu; Zhibin Hao; Haichao Li; Xuexia Miao; Shiheng An; Ruobing Guan (Pesticide Biochemistry and Physiology, 2026)

Effects of mung bean addition on quality and starch anti-digestion mechanism of oat noodles - Rui-xian Shang; Wei-feng Zhang; Zi-hao Tu; Xiu-juan Ren; Yan-xia An; Gui-Hong Yin; Jian Zhang; Yang Zhao (Journal of Cereal Science, 2026)

Twinned structure–enhanced S-scheme heterojunction in Zn0.8Cd0.2@g-C3N4 for efficient CO2 photocatalytic reduction - Ming-yang Liu; Hao-wen Zhu; Qing-shan Wang; Cong Liu; Heng-fei Cui; Jun-ying Tang; Rui-tang Guo (Fuel, 2026)

Insights into the low-temperature NH3-SCR of NO performance and mechanism over vanadium slag catalyst - Yuan She; Hao Meng; Wenkang Niu; Changqing Peng; Junjie Wang; Rui Liu; Xuanxuan Wang (Fuel, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Construction and textural modification of soft surimi gel from spanish mackerel (Scomberomorus niphonius) by polysaccharides - Yin-Yin Lv; Xian-Hao Zhang; Jia-Ni Zhou; Ying-Rui Wang; Zhu-Jun Zhang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2026)

Pulsed electric field facilitated fibrillation of soy protein isolate: preparation, characterization, and functional properties - Dong-Yang Xu; Ben Yu; Wen-Hao Xiao; Zhong Han; Rui Wang; Xin-An Zeng (Food Hydrocolloids, 2026)

Alpaca nanobody-based sandwich ELISA for specific detection of Salmonella enteritidis in chicken - Liang Yuan; Shibo Wang; Yani Ren; Zhenghua Ji; Xinru Jiang; Beili Hao; Shuangshuang Hao; Xiaoxi Han; Changwen Li; Yicong Chang; Rui Li; Fangping Liu (Food Control, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Longitudinal triglyceride-glucose index and Metal Interactions: A multi-model cohort integrating synergistic and antagonistic indices - Jinhao Jia; Yihong Di; Limeng Xiong; Buyun Liu; Zeyang Bai; Jiaming Fu; Yuhan Zhang; Xiaozhe Geng; Yuxi Wang; Chunqing Gao; Guojie Qiao; Hao Hu; et al. (Environmental Pollution, 2026)

Magnetorheological intelligent chiral metamaterials with ultra-low frequency bandgap - Kaixiang Wang; Jian Zhu; Rui Zhang; Wei Ding; Hao Liu; Tianning Chen (Engineering Structures, 2026)

Self-enhancing climatic resilience of surface soil through bio-carbonation constructed barrier - Rui Wang; Chao-Sheng Tang; Guang-Hui Lei; Xiao-Hua Pan; Zhi-Hao Dong; Shao-Dan Wang; Xiancai Lu (Engineering Geology, 2026)

Interfacial charge threshold induced high-safety energetic co-particles - Hao-Rui Zhang; Yingqi Mao; Minghui Dai; Djalal Trache; Xu Zhao; Zhijian Yang; Qi-Long Yan (Chemical Engineering Journal, 2026)

Robust oxygen vacancy surfaces induce chemical bonding interfaces of Bi2Sn2O7/Bi2MoO6 S-scheme heterojunction with asymmetric adsorption sites for efficient photocatalytic nitrogen fixation - Yongli Li; Xin Kong; Rui Bao; Liang Liu; Zhenhua Ge; Feng Liu; Hao Cui; Jianhong Yi (Chemical Engineering Journal, 2026)

Corrigendum to “Anodic microbiota reassembly via cell-cell interactions confers oxygen resilience in microbial fuel cells” [Bioresour. Technol. 443 (2026) 133815] - Jingtong Dai; Xinyu Cao; Heng Xu; Can Wang; Likai Hao; Binbin Xie; Shun Li; Kelei Zhao; Lei Cui; Zhao Yin; Baoshi Yao; Tao Chen; et al. (Bioresource Technology, 2026)

Anodic microbiota reassembly via cell-cell interactions confers oxygen resilience in microbial fuel cells - Jingtong Dai; Xinyu Cao; Heng Xu; Can Wang; Likai Hao; Binbin Xie; Shun Li; Kelei Zhao; Lei Cui; Zhao Yin; Baoshi Yao; Tao Chen; et al. (Bioresource Technology, 2026)

How biodegradable mulching alters soil nitrogen transformations to enhance soil nitrogen supply and influence gas emissions in a maize cropping system - Hao Zhang; Kai Wang; Jinbo Zhang; Christoph Müller; Dianyuan Ding; Qiang Li; Hengliang Tang; Rui Jiang (Plant and Soil, 2026)

The effect and mechanism of Synechococcus sp. PCC 7942 harboring VP26 in the immunity of Litopenaeus vannamei against WSSV - Xiang Ding; Shengyu Liao; Chan Zhu; Xiaofeng Gao; Hao Xing; Rui Jia (Algal Research, 2026)

Multifunctional deep learning-based mechanical-laser collaborative adaptive precision weeding system for lettuce - Rui Hu; Lei Kong; Wen-Hao Su; Bo-Wen Dong; Yujin Wang; Xiaobin Li; Yankun Peng (Computers and Electronics in Agriculture, 2026)

Is China's energy transition pace driven by the supply-side or the demand-side? - Hu Wang; Feng Wang; Juan Liu; Rui Ling; Hao Zhang; Hongfei Jiang (Utilities Policy, 2026)

Suffusion in shield tunnel surrounding soils under train vibration using an improved DEM-PNM coupling method - Si-Rui Chen; Dong-Mei Zhang; Xiao-Chuang Xie; Zhao-Geng Chen; Hui-Hao Chen; Hai-Yun Li (Tunnelling and Underground Space Technology, 2026)

QuaFT: Quality-guided semantic fault intelligence under corrupted industrial data - Lu Ning; Rui Wang; Xiaoran Wei; Hao Huang; Zonghan Zhang; Zehua Chen; Xiaolu Liu; Bo Zhang; Yao Liu; Hao Gong; Kai Song (Process Safety and Environmental Protection, 2026)

Ginkgonins A and B: Two new sesquiterpenoids from Streptomyces ginkgonis TH01 - Yun-Fei He; Jing Miao; Chao Jian; Rui-Jun Wang; Yong-Sheng Gao; Jie-Hao Jin; Xiao-Yi Chen; Ji-Dong Wang; Shao-Yong Zhang (Phytochemistry Letters, 2026)

Contamination risk assessment of shallow groundwater in Xi'an City's plain area based on groundwater vulnerability, pollution loading, and groundwater function value - Yan Liu; Jialu Pang; Weiwei Hu; Zhifeng Jia; Jia Chen; Hao Liu; Rui Lei (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Species delimitation within a taxonomically complex group: An example from the genus Apodemus (Rodentia: Muridae) - Xuan Pan; Buqing Peng; Xuming Wang; Zhongzheng Chen; Hao Cheng; Rui Liao; Chia-Lung Huang; Jiatang Li; Shaoying Liu (Molecular Phylogenetics and Evolution, 2026)

Comparative effects of raw and aged tire microplastics on anaerobic fermentation of excess sludge - Kai Hu; Hao Ding; Wei Wang; Rui Guo; Wei Chen; Hang Xu (Journal of Hazardous Materials, 2026)

Multichannel charge separation induced by multiple internal electric fields in ReS2/CoSx/CdS hollow nanostructures for efficient photocatalysis - Qi-Rui Zhang; Yu-Long Wang; Zhi-Hao Deng; You-Long Chen; Si-Jing Ding; Liang Ma (Journal of Environmental Chemical Engineering, 2026)

The enhanced role of formic acid on sulfuric acid-ammonia-driven nucleation in forest regions and polluted city areas - Shasha Chen; Rongrong Li; Chengyan Zhang; Shuqin Wei; Rui Wang; Biwu Chu; Xiaomeng Zhang; Hao Li; Tianlei Zhang (Journal of Environmental Sciences, 2026)

The botryoidal dolomite of the Ediacaran Dengying Formation (Yangtze Craton): Multi-proxy constraints on the terminal Neoproterozoic “dolomite sea” - Yao Wang; Wenlong Ding; Ziyou Zhang; Shuaiyu Shi; Rui Xia; Mengyang Zhang; Hao Jian (Journal of Asian Earth Sciences, 2026)

Transcription factor Schlank positively regulates odorant-binding protein 9 expression to mediate recognition of two volatiles in Nilaparvata lugens (Stål) - Rui-Lin Zhang; Hao-Wei Wang; Man-Qun Wang (Insect Biochemistry and Molecular Biology, 2026)

Grain-size controls on quartz OSL sensitivity in fluvial systems: insights from transport mechanisms in the upper Yellow River - Ya Liu; Song-Xi Du; Jia-Fu Zhang; Xue Rui; Yu-He Shen; Jia-Jing Wang; Qing-Hao Ma; Zheng-Hao Gu (Geomorphology, 2026)

Molecular insight into the structure and formation mechanism of fluid phase in the classical coking theory - Bo Gong; Jie-Ping Wang; Hao-Dong Liu; Rui Guo; Jin-Xiao Dou; Guang-Yue Li; Ying-Hua Liang (Fuel, 2026)

Strain-dependent immunomodulatory activities of lipoteichoic acids from probiotics: From interspecies to intraspecies variation - Yini Liu; Rui Xiao; Min Guo; Jingyu Lu; Jianxin Zhao; Ruojie Zhang; Hao Zhang; Gang Wang; Zipei Zhang (Food Bioscience, 2026)

Quantifying the impact of vegetation greenness change on surface urban heat islands across 133 major cities of China - Rui Yao; Zhihao Zhang; Wenjie Li; Hao Li; Shiya Zhu; Hongji Zhu; Chuan Wang; Dewei Luo; Ying Yang; Junli Li; Weitao Han; Xin Huang (Environmental Research, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Bi single-atom decorated Cu/Cu2O heterostructure via spray pyrolysis for 100% selectivity in photocatalytic CO production - Danyang Ma; Xin Kong; Xin You; Liang Liu; Rui Bao; Hao Cui; Feng Liu; Jianhong Yi (Chemical Engineering Journal, 2026)

Edge activation-oxidation strategy enhances sodium storage performance and economic viability of spent battery graphite - Yifeng Han; Hao Tan; Hongling Yao; Shuya Chang; Zihan Huang; Zhaojun He; Anan Zuo; Yong Ding; Rui Xia; Tao Mei (Chemical Engineering Journal, 2026)

Precision in the air: A lightweight, cost-effective, CFD-assisted method for occupant localization and demand-based airflow control in crowded indoor spaces - Zhe Wang; Hao Sun; Mingda Harvey Yang; John Kaiser Calautit; Jianbin Chen; Rui Guan; Zhu Tao; Xue Zheng; Abdullah Dik; Jo Darkwa (Building and Environment, 2026)

Heterogeneous typing of physical-mental symptoms in stroke patients during recovery phase based on latent class analysis and influencing factors - Li Cao; Rui Song; Bingying Zhai; Zihan Zhang; Xiao Zhang; Yuying Hao (Neurophysiology, 2026)

Eucommia ulmoides leaf extract enhanced growth, supported liver and intestinal function, modulated gut microbiota composition, and increased disease resistance in juvenile largemouth bass (Micropterus salmoides) - Qiang Hao; Tsegay Teame; Rui Xia; Qianwen Ding; Yuanyuan Yao; Chao Ran; Yalin Yang; Zhen Zhang; Zhigang Zhou (Aquaculture, 2026)

Non-degenerate and degenerate soliton solutions to the semi-discrete vector nonlinear Schrödinger system - Yang-Yang Du; Yan-Nan Zhao; Hui-Qin Hao; Rui Guo; Jian-Wen Zhang (Wave Motion, 2026)

Estrogen inhibits granulosa cell apoptosis via nuclear receptors by suppressing death receptor and mitochondrial pathways in goat small antral follicles - Sihai Lu; Baijuan Yue; Yaju Tang; Haoyu Xu; Rui Xu; Xiaoe Zhao; Qiang Wei; Jia Xue; Meng-Hao Pan; Sha Peng; Baohua Ma (Theriogenology, 2026)

GABPα2β2 tetramer deficiency impairs natural killer cell maturation, compromising cytotoxicity and resistance against melanoma - Weiwei Jia; Wanting Zhong; Shanshan Hao; Zhao Wang; Shuaishuai Niu; Yingdi Xu; Yajiao Zhang; Mingxia Feng; Haitao Jiang; Jiarui Zhang; Danli Song; Peiyao Yan; et al. (Science Bulletin, 2026)

Enhanced rock-breaking performance of an angular Helmholtz cavitation jet nozzle: Flow field dynamics and mechanism analysis - Chenrui Guo; Rui Li; Hao Wang; Zhongwei Huang; Gensheng Li; Huan Li; Jingbin Li; Jiaqing You (Process Safety and Environmental Protection, 2026)

AhNHL24 enhances peanut resistance to bacterial wilt and stem rot via glutathione and phenylpropanoid pathways - Mengtian Hou; Hao Li; Zenghui Cao; Fang Wang; Sasa Hu; Yanzhe Li; Qian Ma; Yaoyao Li; Yi Fan; Kai Zhao; Kunkun Zhao; Ding Qiu; et al. (Plant Science, 2026)

Effective domain adaptive shipwreck detection method in side-scan sonar images for unmanned underwater vehicles - Rui Tang; Yimin Chen; Dawei Gao; Jian Gao; Shaowen Hao (Ocean Engineering, 2026)

Intraspecific competition can stabilize asymmetric nursery pollination mutualisms - Jian-Zhong Gao; Feng Zhang; Derek W. Dunn; Hao Wang; K.Charlotte Jandér; Rui-Wu Wang (Journal of Theoretical Biology, 2026)

Recent progress on Cu-based MOF electrocatalysts for CO2 reduction - Heng-fei Cui; Xiao-jing Liu; Cong Liu; Hao-wen Zhu; Ming-yang Liu; Rui-tang Guo (Fuel, 2026)

Dietary components cooperate with intestinal flora to regulate food allergy - Jiaxi Yan; Li Niu; Wei Wang; Rui Gao; Jianxiong Hao; Huan Rao; Dandan Zhao; Xueqiang Liu; Wentong Xue; Yang Tian (Food Chemistry, 2026)

Comprehensive performance of iron-loaded biochar adsorption of U(VI) at an industrial scale based on life cycle assessment and economic analysis - Jia He; Zhou Shen; Yisa Li; Hao Wen; Rui Lu; Shaoli Fan; Jian Gao (Environmental Research, 2026)

Seawater desalination in China: Current situation, problems, and development prospects - Rui hao Wang; Cheng peng Wang; Sheng hui Wang; Dai wang Song; Pengfei Huang; Xiaoli Wang; Ren wen Ma (Desalination, 2026)

TensorSymmetry: a package to get symmetry-adapted tensors disentangling spin-orbit coupling effect and establishing analytical relationship with magnetic order - Rui-Chun Xiao; Yuanjun Jin; Zhi-Fan Zhang; Zi-Hao Feng; Ding-Fu Shao; Mingliang Tian (Computer Physics Communications, 2026)

Revealing the operando ORR mechanism of single-atom catalysts anchored in nanobowl structures for advanced hydroxide exchange membrane fuel cells - Sun-Tang Chang; Hui-Xin Liu; Yi-Ching Chu; Ying-Rui Lu; Chen-Hao Wang (Chemical Engineering Journal, 2026)

Soil respiration and its temperature sensitivity on croplands in response to biotic and abiotic factors under straw and nitrogen fertilizer management - Ru Guo; Ruixuan Hao; Xiaoyi Yang; Rui Qian; Zijun Ma; Yunyun Yang; Peng Zhang; Zhikuan Jia; Yuncheng Liao; Xiaolong Ren; Xiaoli Chen (CATENA, 2026)

Efficient bioconversion of corn stover hydrolysates into phenazine-1-carboxylic acid by engineered Pseudomonas chlororaphis for sustainable biopesticide production - Sheng-Jie Yue; Yu-Xuan Li; Kai-Quan Liu; Sheng-Xiao Zhang; Peng Huang; Wei Wang; Xue-Hong Zhang; Xiang-Rui Hao; Lian Jiang; Hong-Bo Hu (Bioresource Technology, 2026)

Expression of Beta vulgaris betaine aldehyde dehydrogenase 1 (BvBADH1) confers salt tolerance in tobacco (Nicotiana benthamiana) - Ming Wei; Xiang-Yu Chen; Meng-Li Li; Hao Li; Xin-Rui Wu; Guo-Qiang Wu (Physiology and Molecular Biology of Plants, 2026)

A near-infrared hemicyanine-derived fluorescent probe for sulfite detection in biomedical investigate - Kai Wang; Dan-Xian Cai; Hao-Xiang Jiang; Zi-Rui Luo; Hong-Rui Zhan (Analytica Chimica Acta, 2026)

A dual-mode colorimetric and electrochemical strategy for sensitive detection of PRRSV using imidazole-copper nanozymes - Jing Li; Xiang Lai; Chong Zhang; Yu-Fan Huang; Guo-Bao Ning; Si-Ying Ma; Ao-Xiang Chen; Ming-Rui Li; Guo-Hao Li; Qin Zhao; Can-Peng Li; Hui Zhao (Analytica Chimica Acta, 2026)

Integrated assessment reveals plowing/no-tillage rotation as the trade-off considering crop yield and environmental performance in the Loess Plateau - Xingyu Guo; Shulan Wang; Hao Wang; Naeem Ahmad; Xiaoli Wang; Jun Li; Rui Wang (Agricultural Systems, 2026)

Low-thrust transfers to halo orbits in different systems: Hybrid optimization and free-coast design - Zhaoyu Li; Tianyou Li; Hao Zeng; Rui Xu (Advances in Space Research, 2026)

Correction: Lei et al. Transcriptomic Analysis of Non-Specific Immune Responses in the Rice Field Eel (Monopterus albus) Infected with Pallisentis (Neosentis) celatus. Fishes 2024, 9, 452 - Qin Lei; Xiaoling Li; Hao Wu; Yiwen Wan; Yukun Xie; Jinwei Gao; Wenwen Suo; Ming Zeng; Lingli Liu; Dongsheng Ou; Zhonggui Xie; Rui Song (Fishes, 2025)
In the original publication [...]

From plant-based food waste to biochar: A green strategy for agri-food supply chain waste valorization–a comprehensive review - Xuejiao Chen; Yanbo Hao; Wei Lin; Liya Xie; Rui Yang; Wenliang Xiang; Zhilian Gong; Feng Gu; Hongyan Liu; Jie Tang (Trends in Food Science & Technology, 2025)

Environmental relevant concentrations of TBBPA cause complex toxicological mechanisms - Yuxing Liao; Yilin Wang; Hao Dong; YaJie Lin; Yuxi Xiao; Rummana Jaman; Mohith Mohan; Farheen Azim; Rui Lu; Tengji Zhao; Jiao Zhu; Guiyuan Chen; et al. (Toxicology Letters, 2025)

Reconstructing hydrocarbon accumulation and burial history of Permian reservoirs in northwest Sichuan Basin, China: Integrated fluid inclusion thermometry and U-Pb dating - Rui Ni; Yong Chen; Yifan Song; Hui Zhang; Yanwei Feng; Fang Hao; Xuesong Lu; Xingzhi Ma (Marine and Petroleum Geology, 2025)

The Eocene blueschist in Zeyarat metamorphic complex, Iranian Makran: Implication for subduction dynamics in plates interface - Zhou Tan; Wenjiao Xiao; Rasoul Esmaeili; Parisa Gharibnejad; Miao Sang; Qigui Mao; Hao Wang; Rui Li; Zhiyong Zhang; Jien Zhang (Lithos, 2025)

Precise construction of Anderson-type polyoxometalate-based covalent organic frameworks for photocatalytic hydrogen peroxide production - Zhang-Di Liu; Zai-Xiang Zhang; Yang Yang; Rui Xing; Zi-Hao Wei; Hou-He Liu; Jiang-Bo Ming; Jin Zhu; De-Yin Wang (Journal of Water Process Engineering, 2025)

Synergistic KOH/MgSO₄ activation of hazelnut shell biochar: Tailored hierarchical porosity and surface chemistry boosting high-efficiency capacitive deionization - Shumin He; Youzhao Wang; Xiaolong Gao; Jiedong Hao; Enbo Zhang; Rui Du; Tengfei Li; Yaonan Zhu; Tong Zhu (Journal of Environmental Chemical Engineering, 2025)

Retention-driven water flow regulation: A network perspective - Xuan Jiang; Jinsong Zhao; Zhiwen Cai; Jiating Li; Jian Wang; Ling Wang; Xiao Li; Rui Hao; Shuxia Yu; Zhihua Shi (Journal of Environmental Management, 2025)

Location-specific climate and environmental benefits of China’s coal mining phase-down towards carbon neutrality - Hao Li; Tao Yang; Linman Li; Bin Lu; Tianzheng Zhang; Xiaolong Lu; Rui Peng; Zhaohua Wang (Global Environmental Change, 2025)

Microwave-driven catalytic upgrading of waste engine oil using defect-rich steel slag: Oxygen vacancy modulation and reaction mechanisms - Junhao Lin; Jiahui Hou; Jiashan Chen; Yanxi Liu; Yanan You; Mingxing Chen; Rui Ma; Hao Wang; Shichang Sun (Fuel, 2025)

Multi-modified β-Lg-stabilized fish oil emulsions: physicochemical stability, antioxidant capacity, and bioavailability in Caco-2 cells - Qingchun Zhang; Hao Zhu; Rui Wang; Jianfei He; Christos Ritzoulis; Owen Griffith Jones; Weilin Liu; Wei Tang; Jianhua Liu (Food Chemistry, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Superacid polymer electrolyte with end-group-protected proton sites mitigates ammonia poisoning for efficient electrochemical hydrogen separation from ammonia cracking reformate gas - Jiaqi Shuai; Hao Li; Zhengrui Xiao; Zeqi You; Yucong Liao; Rui Wang; Yafeng Li; Yuanwei Yan; Jiangping Song; Tian Tian; Lan Zhang; Siew Hwa Chan; et al. (Chemical Engineering Journal, 2025)

3D printed hydrogel with fingerprint-inspired features for enhanced sensing performance in electronic skin - Jianshe Hao; Yanbin Xu; Chaofan Yang; Rui Guo; Yang Lyu; Zhongying Ji; Xiaolong Wang (Chemical Engineering Journal, 2025)

Recent advances and perspectives in coordination polymer-based fluorescent sensors for vitamin detection - Zi-Hao Zhao; Zhi-Wei Liu; Xin-Rui Xu; Qian-Yu Yang; Zhao-Yang Tong (Chemical Engineering Journal, 2025)

Mitigative effects of Vitamin C on deltamethrin-induced acute toxicity in crucian carp by modulating the AhR/Nrf2 signaling pathways - Hao Wu; Jinwei Gao; Dong Liu; Xiangrong Liu; Feiming Chen; Jiayuan Qin; Yunfei Ye; Zhenzhen Xiong; Jiayu Wu; Can Yang; Min Xie; Rui Song; et al. (Aquatic Toxicology, 2025)

Different Chemical Fertilization Levels Affect Arbuscular Mycorrhizal Fungal Communities in Rhizosphere Soils of Ratoon Sugarcane - Xiao-Juan Qin; Sheng Wang; Ying-Jie Nong; Yi-Hao Kang; Jin-Lian Zhang; Shi-Yuan Zeng; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2025)

FAM72A promotes cervical cancer progression by regulating the PI3K pathway - Qin wang; Hao Yu; Rui Huang (Functional & Integrative Genomics, 2025)

A systematic review of montmorillonite-asphalt composite materials: Green clay mineral-reinforced asphalt for sustainable pavement solutions - Hao Lai; Anhua Xu; Jianliang Zhai; Youjie Zong; Wei Deng; Haoyan Guo; Bowen Guan; Mingfeng Chang; Rui Xiong; Zhenjun Wang (Applied Clay Science, 2025)

Effects of geochemical reactions on flow properties during compressed air energy storage in aquifer - Shida Zheng; Jinsheng Wang; Chengzhi Wang; Jiawei Liu; Rui Zuo; Guanlan Wu; Xiaofan Yang; Minghao Pan; Hao Wang; Guangrong Hu (Advances in Water Resources, 2025)

Quantifying the relative importance of factors influencing rainfall partitioning in a rainfed apple orchard - Rui Zhang; Li Wang; Hao Liu (Hydrological Sciences Journal, 2025)

Multiscale responses of gap-graded soil under the combined effect of train vibration and seepage erosion - Dong-Mei Zhang; Hui-Hao Chen; Xiao-Chuang Xie; Si-Rui Chen; Zhao-Geng Chen; Jia-Ping Li (Transportation Geotechnics, 2025)

Prevalence and risk factors of Giardia duodenalis in sheep and goats in global: A systematic review and meta-analysis - Zhengyi Li; Wei Wei; Yuan Ma; Luyao Hao; Yuan Guo; Rui Wang (Preventive Veterinary Medicine, 2025)

Post-collisional crustal evolution in the central Lhasa block of southern Tibet: Insights from early and late Cretaceous magmatism - Shu-Ya Huang; Lu-Lu Hao; Qiang Wang; Andrew C. Kerr; Wan-Long Hu; Qing-Qing Mo; Mao-Rui Liu; Yue Qi; Wei Dan; Xiu-Zheng Zhang (Lithos, 2025)

Microplastics modulate neutrophil migration via an ROShistone lactylation positive feedback loop - Yi-li Wang; Xiao-chen Yuan; Chun-jiao Wei; Ke-yun Li; Lin-xi Zuo; Hao-yi Zhang; Rui-chen Ding; Ren Zhou; Yun-hua Zhang; Da-long Ren (Journal of Hazardous Materials, 2025)

Simple and economical photoelectrode modification for efficient ranitidine removal: Improved surface reactivity and switchable radical/non-radical pathways - Jiajun An; Yanan Li; Lei Wang; Jiajin Hao; Lujie Nie; Bo Gao; Xudong Wang; Jin Wang; Rui Miao; Miaolu He; Danxi Huang (Journal of Hazardous Materials, 2025)

Enhancing NO3− reduction on BiFeO3/Cu cathode via ferroelectric polarization: A novel strategy for surface electronic structure regulation - Hao Chen; Houfen Li; Yue Zhao; Yunlong Ma; Zhichao Liu; Rui Li; Sufang Wang; Aijuan Zhou; Xiuping Yue; Haibing Meng; Hongtao Yu; Xu Zhao (Journal of Environmental Management, 2025)

Enhanced electrocatalytic oxidation of high-salinity quaternary ammonium compound wastewater using CNTs-(Ru Ir O2)/Ti Anode - Hao-Tian Liu; Han-Qing Zhao; Yi-Rui Yang; Shuang Wu; Jia-Ping Huang; Rui-Han Yu; Hongcheng Bai; Aqiang Ding; Daijun Zhang; Peili Lu (Journal of Environmental Sciences, 2025)

Effect of egg white peptides‑selenium chelate against APAP-induced damage in HepG2 cells and C. elegans via Nrf2 signaling - Yuwei Wu; Yiqiao Pei; Wenjie Wang; Siyu Du; Fengshi Shang; Zhifu Liu; Rui Liu; Ye Zhang; Hao Wang (Food Chemistry, 2025)

Chlorine atoms modulated Fe d-band centers drive non-radical pathways to degrade bisphenol A with attenuated intermediates toxicity - Jianwen Huang; Yuxin Liu; Kun Yao; Qintie Lin; Zirui Zhao; Jieyi Pan; Longyi Wei; Hao Luo; Rui He (Chemical Engineering Journal, 2025)

Hierarchical Janus sponge evaporator functionalized with liquid-like PDMS molecular brushes for efficient and sustainable solar evaporation and electricity generation - Siying Guan; Taolin Zhang; Shouzheng Jiao; Rongxue Xi; Rui Ma; Chenshun Hu; Yuwei Hao; Zhicheng Sun; Zhongjun Cheng (Chemical Engineering Journal, 2025)

Environmentally friendly, lightweight, and recyclable nanocomposite foams for sustainable electromagnetic interference shielding via integrating a dynamically crosslinked biobased polyamide system with supercritical carbon dioxide foaming - Chia-Hsing Lin; Chia-Wei Lee; Lyu-Ying Wang; Rui-Hao Li; Yi-Huan Lee (Chemical Engineering Journal, 2025)

Corrosion-resistant TiZrNbTaW high-entropy alloy coatings for Ti anode polar plates of proton exchange membrane water electrolyzers - Hongwu Zhao; Rui Gao; Hao Li; Muyu Ma; Guoxing Chen; Daiman Zhu; Marcos Antonio Coelho Berton; De Ning; Anke Weidenkaff; Yongli Li (Chemical Engineering Journal, 2025)

Dual-catalytic polymerization of high-performance PEDOT thermoelectric fabrics for self-powered sensing - Yifan Cui; Qin Chen; Wuwei Bao; Hao Yao; Zhenzhe Huang; Rui Ma; Miao Miao; Lizhi Sheng; Xinyang He (Chemical Engineering Journal, 2025)

Optimizing electromagnetic attenuation properties via controlled dielectric polarization in Zn single-atom-decorated polymer-derived SiZnCN ceramics - Hao Deng; Yang Li; Ruihua Chen; Chao Ma; Junpeng Jiang; Daoyang Han; Bingbing Fan; Hailong Wang; Rui Zhang; Gang Shao (Chemical Engineering Journal, 2025)

Ni/Al2O3 catalysts for the selective hydrogenation of 1,3–butadiene to butene: From theoretical research to experimental proving - Linxia Cui; Mingyuan Zhang; Xin Chen; Yuanyao Xie; Yang Jiang; Rui Gao; Haigang Hao (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Fusarium infection alters the effects of vegetable residue and its compost on nitrous oxide emissions from acid soil - Yumeng Xu; Xiaoxiao Xiang; Waqar Ahmed; Junhui Yin; Owen Fenton; Wenxuan Shi; Jiaqi Wang; Ruixue Chang; Rui Liu; Hao Chen; Guorong Xin; Qing Chen (Applied Soil Ecology, 2025)

Multifunctional fluorescent sensors N/CDs@Eu-MOFs for rapid detection of childhood obesity and acute myeloid leukemia biomarkers and identification of chiral enantiomers of lysine - Liping Peng; Rui Xue; Henglong Ren; Borong Ren; Mingyue Wang; Xiuli Niu; Hao Guo; Wu Yang (Analytica Chimica Acta, 2025)

Isolation, identification, and bioactivity evaluation of endophytic fungi from Ruta graveolens: insights into antimicrobial and antioxidant potential - Qianyun Hao; Wei Wang; Yanlin He; Chaoyong Cui; Jing Du; Rui Yang (Folia Microbiologica, 2025)

Smart weeding system with multi-sensor fusion for tomato plant detection and targeted micro-spraying of intra-row weeds - Jia-Le Li; Wen-Hao Su; Rui Hu; Long-Tao Niu; Qi Wang (Computers and Electronics in Agriculture, 2025)

Identifying hundredfold carbon emission gaps in multiple resource recycling routes of construction waste via process and hybrid life cycle assessment - Rui Chen; Haiyuan Wu; Junjie Li; Hao Wang; Lanxin Li; Linlin Sun; Fumin Ren (Waste Management, 2025)

Evaluation of heavy metal accumulation and pollution in soils from the vanadium–titanium magnetite mining region in Panzhihua, China - Tingting Fu; Hao Song; Bin Yang; Rui Liu (Ore and Energy Resource Geology, 2025)

Electrospun Mn-doped ZIF-67 composite nanofibers with high water stability for efficient adsorption of antibiotics in aqueous systems - Xiaolin Yue; Can Cui; Shaolin Deng; Lan Wang; Ping Li; Anhong Li; Yizhong Zhang; Rui Hao; Wenyuan Tan (Journal of Environmental Chemical Engineering, 2025)

Synergistic engineering of four-pointed star-like layered stacking and oxygen vacancies toward high-efficiency Bi2O2-xSe photocatalysts for the degradation of tetracycline and Congo red - Yao Yang Liu; Zhong Li; Yi Liang; Jing Hao Zhuang; Wen Ji Zhang; Tao Tang; Yin Fen Cheng; Rui Ou; Bao Yue Zhang; Jian Zhen Ou (Journal of Environmental Chemical Engineering, 2025)

Pig bedding biochar enhances the Cd extraction capacity of Perilla frutescens by mitigating the toxicity of Cd-contaminated soil - Tianlian He; Xingyu Hao; Rui Jing; Zhenguo Li; Ying Chen; Mingwei Yang; Chengzhen Gu; Yulin Wang; Ruiyu Lin; Xinyu Zheng (Journal of Environmental Sciences, 2025)

Super-resolution for evolutionary probability density of stochastic dynamic responses using physics-guided diffusion model - Zidong Xu; Rui Zhou; Hao Wang (Engineering Structures, 2025)

Utilizing a three-zone control model of adaptive concentrating photovoltaic facade to enhance visual comfort and energy benefits - Bo Wang; Yifan Xu; Hao Wang; Xinshuo Zhang; Yuan Chen; Rui Tang; Ayin Yan; Mengli Zhang; Ying He (Energy and Buildings, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Photothermal PCN-134-2D interlayer-driven foaming intensification for improving lithium enrichment in forward osmosis membranes - Miaolu He; Yina Wu; Suo Shi; Jin Wang; Yue Hu; Yilin Yang; Jiajing Hao; Xudong Wang; Rui Miao; Lei Wang (Chemical Engineering Journal, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

Jugular Vein Evans Blue Injection for Blood–Brain Barrier Assessment Following Hemorrhagic Stroke in a Mouse Model - Yu Zeng; Fang Wang; Rui Liu; Jian liu; Tao Xiong; Guodong Liu; Hao Yin; Guoqiang Han; Jian liu; Jiqin Zhang; Ying Tan (Translational Stroke Research, 2025)

A novel method for predicting debris flow hazard: a multi-strategy fusion approach based on the light gradient boosting machine framework - Tianlong Wang; Qi Ge; Tianxing Ma; Hao Chen; Rui Luo; Xu Wang; Keying Zhang; Zhaowei Chu; Xiaohui Ni; Hongyue Sun (Stochastic Environmental Research and Risk Assessment, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Enhancing Cannabidiol Apparent Solubility and Oral Delivery: Self-assembled Nanomicelles of Amphiphilic Block Copolymer with γ-Polyglutamic Acid-grafted Cholesterol - Rui Li; Wenhui Ruan; Liyan Lu; Zhijuan Wu; Rui Hao; Yingli Wang; Jue Chen (Pharmaceutical Research, 2025)

Flavonoids as Signals Mediate Plant-nematode Communication Through Regulating Nematode Perceptual Ability - Xiang-Yu Zhang; Rui Yuan; Yaseen Ullah; Xu-Dong Li; Hao-Ran Li; Wei Zhang (Journal of Chemical Ecology, 2025)

Research progress on programmed cell death of cardiomyocytes in pressure-overload hypertrophic cardiomyopathy - Fei Xiao; Hui-Li Li; Jia-Rui Wang; Hui-Min Wu; Yu-Qi Cai; Jia-Wan Wang; Hao Che; Gang Li; Zheng-Yuan Xia; Yu-Bo Xie; Sheng Wang (Apoptosis, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Unsupervised domain adaptation semantic segmentation method for wheat disease detection based on UAV multispectral images - Yuchen Zhang; Xingan Hao; Feilong Li; Zexi Wang; Dongxiang Li; Mei Li; Rui Mao (Computers and Electronics in Agriculture, 2025)

Identification and characterization of a new strain of Ictalurid herpesvirus 1 isolated from channel catfish in China - Fei Yu; Jiehua Xu; Sheng Yuan; Yi Yang; Siyang Song; Kai Hao; Rui Yuan; Yu Wang; Xiaohui Chen; Zhe Zhao (Aquaculture, 2025)

Development and field evaluation of a straddle-frame honeysuckle harvesting robot - Zhaoyu Rui; Zhao Zhang; Cunming Hao; C. Igathinathane; Afshin Azizi; Xiaofei Wu; Man Zhang; Fazeel Abid; Seyed Mohamad Javidan (Biosystems Engineering, 2025)

Emerging MXene-based Composites: Synthesis, and Recent Advances in Food Contaminant Analysis - Mengmeng Gao; Rongchao Li; Huilin Li; Xiaochun Hu; Jingming Sun; Hao Wang; Rui Gao; Huilin Liu; Mingfei Pan; Shuo Wang (Trends in Food Science & Technology, 2025)

New point mutations in osmosensing two-component histidine kinase gene associated with iprodione resistance in Monilinia fructicola field isolates from China - Qian Long; Yiyi Guo; Miaomiao Yi; Changsheng Lu; Rui Zhong; Hao Zhang; Usama Amin; Dufang Ke; Zongwen Wang; Fengping Chen (Pesticide Biochemistry and Physiology, 2025)

Decoupling erosion effects on carbon fractions and stability in black soil agricultural landscapes - Rui QIAN; Lei GAO; Asim BISWAS; Hao DU; Shuai LIU; Xinhua PENG (Pedosphere, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

Electrocatalytic removal of nitrate by non-noble Fe3C/Cu: Property, mechanism, and practical water treatment performance - Yang Guo; Hao Chen; Houfen Li; Jiming Liu; Xiao Zhang; Aijuan Zhou; Xiuping Yue; Rui Li; Jindong Wang; Pengxiao Liu; Hongtao Yu; Xu Zhao (Journal of Hazardous Materials, 2025)

A ratiometric fluorescent sensor based on Eu3 + -β-diketone functionalized covalent organic framework hybrid material-loaded in electrospun polyvinylidene fluoride film for ultra-sensitive and rapid detection of glyphosate - Yingfei Hui; Hao Guo; Rui Xue; Mingyue Wang; Yanyan Ma; Dengke Zhuang; Wu Yang (Journal of Hazardous Materials, 2025)

Computer-aided precise hapten design strategy for the monospecific detection of altrenogest: Experimental validation and analysis of the molecular recognition mechanism - Hongfei Yang; Hao Wen; Yu Si; Mingyue Ding; Yiting Liu; Ziyan Yu; Linwei Zhang; Jiacan Wang; Xiaoming Pan; Shiyun Han; Yiting Wang; Shixiang Wu; et al. (Food Chemistry, 2025)

Protective effects of rosmarinic acid against oxidative damage and atherosclerosis via the PI3K/AKT pathway - Tiantian Tang; Mingze Sun; Baiyuan Sha; Rui Liu; Zhiyang Ren; Liwei Li; Ye Zhang; Hao Wang; Kai Yu (Food and Chemical Toxicology, 2025)

Holographic, traceable, and switchable anti-counterfeiting using temperature-tolerant relief gratings on polyimide substrate - Chengwei Xiao; Haixian Shi; Hao Zhong; Chengbin Zou; Yiyong Chen; Jinru Li; Weien Liang; Wanying Zhang; Dezhi Zhan; Shilong Zhong; Rui Chen; Zhaoxiang Zhu; et al. (Chemical Engineering Journal, 2025)

Engineering B₄O₇2−-cross-linked double‑carbon layer separators for mitigating molecular shuttle in rechargeable small-molecule batteries - Xinyu Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Mingsheng Yang; Bei Wang; Haiping Yu; Mengxiao Li; Yuxin Hao; Zhihui Wang; Jingru Liu; Mingjun Hu; et al. (Chemical Engineering Journal, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

Gradient distribution of trap states in polymer dielectrics induced by electric field for enhanced insulation properties - Bing Xia; Ming-Xiao Zhu; Zhi-Hao Xing; Rui Liu; Jie-Rui Ren; Xue-Kai Xu (Chemical Engineering Journal, 2025)

SiO2-assisted co-assembly of ultrafine aramid nanofiber-based porous thermal-resistant separator for Lithium-ion batteries - Fuhai Guo; Minghan Xu; Shi Feng; Keyu Zhang; Xiaotong Zheng; Hao Xue; Fulan Hao; Rui Zhuang; Qingchun Liu; Lei Zhang; Jianjun Zhang; Qingfu Wang (Chemical Engineering Journal, 2025)

Optimizing patterned laser-induced graphene strain sensors via novel piezoresistive modeling and multi-objective analysis - Jia-Chen Shang; Wen-Feng Pan; Wen-Hao Zhao; Heng Yang; Yu-Yi Chen; Rui Wang; Ri-Han Wang; Ling-Yu Sun; Yao-Guang Cao; Shi-Chun Yang (Chemical Engineering Journal, 2025)

Properties of rich-Nae effect and reversible oxygen redox with a complete solid-solution sodium-storage behavior - Wei Zhao; Shao-Hua Luo; Yicheng Lin; Guodong Hao; Rui Huang; Pengyu Li; Ge Wang; Jun Cong; Shengxun Yan; Lixiong Qian (Chemical Engineering Journal, 2025)

Kinematic mechanisms of coordinated fore and hind hoof movements for stability enhancement and energy efficiency in reindeer long-distance migration - Kaixiang Chen; Rui Zhang; Wenchao Dong; Hao Pang; Guoyu Li; Lige Wen (Polar Biology, 2025)

Transcriptome Profiling of the Primary and Crown Root in Response to Nitrate in Foxtail Millet (Setaria italica) - Xueting Kang; Jian-Hong Hao; Jiayi Chen; Xuan Zhou; Dan-Ying Chen; Rui Zhao; Ru Meng; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; et al. (Journal of Plant Growth Regulation, 2025)

MLWNNR: LncRNA-Disease Association Prediction with Multi-Kernel Learning-Driven Weighted Nuclear Norm Regularization - Guo-Bo Xie; Hao-Jie Xu; Guo-Sheng Gu; Zhi-Yi Lin; Jun-Rui Yu; Rui-Bin Chen (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Effect of Drought Stress on Root Metabolome and Soil Microbial Characteristics for Maize (Zea mays L.) Seedlings - Rui Hao; Hao Li; Shufang Qin; Wenquan Chen; Qiuchen Guo; Yanan Huang; Xiaohong Chen; Yajun Li (Current Microbiology, 2025)

Xylem hydraulic impairment due to stronger drought stress accounts for the reduced crown vitality and growth performance of Mongolian pine trees in higher-density plantations - Xue-Wei Gong; Yi-Lei Ouyang; Yan-Yan Liu; Jin-En Zhang; Zhao-Kui Li; Hong-Li Li; Zhuo-Qun Fang; Yu Cao; De-Dong Wu; Qiu-Rui Ning; Guang-You Hao (Agricultural and Forest Meteorology, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

Chinese Tuina ameliorates muscle damage by regulating endoplasmic reticulum stress and autophagy in a rat model of skeletal muscle contusion - Hai-chao Liu; Hao-ming Zhu; Ming Li; Bo-rui Chen; Zheng-yu Yang; Yu Wang; Shi-zhong Wang; Shao-qing Chen; Jian-ping Lin (Tissue and Cell, 2025)

Exploring the psychological impacts of air contamination: A cross-national study - Yu Hao; Shiyao Liu; Xueyu Rui; Xiaoxiao Hu; Lu Wang; Shen Wang; Guisen Zhang; Asyraf Afthanorhan; Zhi-Nan Lu (Journal of Environmental Management, 2025)

3D inversion of airborne transient electromagnetic data using deep learning - Shuowei Zhang; Rui Liu; Hao Feng; Zhihong Wang; Shangbin Liu; Yan Luo; Ziqiang Zheng; Huaifeng Sun (Journal of Applied Geophysics, 2025)

Coaxial emulsion electrospinning fiber films loaded with OEO for active packaging of pork - Hao Wang; Rui Ren; Mengjiao Li; Zhennan Gao; Hui Li; Simin Li (Food Research International, 2025)

Developing a Cas12a-based detection method on the emetic Bacillus cereus strains in infant formulas - Hao Wang; Rui Yin; Yingying Huang; Yan Li; Min Yue (Food Research International, 2025)

Strain-specific effects of fish originated Bacillus velezensis on growth, gut health, and disease resistance of zebrafish - Yuan-Yuan Yao; Wen-Hao Zhou; Juan Hu; Ya-Lin Yang; Ming Li; Rui Xia; Chao Ran; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2025)

Key role of macrophyte-dominated habitats over cyanobacteria-dominated habitats in stability of microbial sulfur cycling in freshwater lakes - Rui-Ze Li; Zhi-Jie Zhu; Xing-Hao Li; Yi-Ying Jiao; Li-Ya Zhao; Zhao-Hua Li; Mo Chen (Environmental Research, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

Functional nucleic acid-stabilized selenium nanotechnology enable synergistic healing of diabetic chronic wounds - Si-Wei Yang; Jing Wang; Yan Tan; Xiao Jing; Chen-Yu Wang; Zhi-Li Yao; Wen-Hui Wang; Yong-Ji Li; Hao-Rui Li; Yan Zhao; De-Ming Kong; Qi-Liang Cai (Chemical Engineering Journal, 2025)

2D nonlayered titanium oxynitrides intercalated with nitrogen-doped graphene for pseudocapacitive energy storage - Xiuli Li; Rui Huo; Zihuan Tang; Yulei Ren; Hao Song; Paul K. Chu; Kaifu Huo (Chemical Engineering Journal, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Multifunctional Janus hydrogel targeting mitochondrial regulation and inflammatory pathways promotes infected burn wound repair - Xiaohui Li; Longbao Feng; Honglin Wu; Hao Yang; Peng Wang; Yongfei Chen; Yuxi Zhou; Jiayuan Zhu; Wei Xue; Rui Guo; Zhicheng Hu (Chemical Engineering Journal, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Influence of Winter Tasman Sea SST on the Antarctic Peninsula: A Perspective from Historical Simulations - Rui Wang; Fei Zheng; Hao Wang (Advances in Atmospheric Sciences, 2025)

Drivers of ecosystem service trade-off changes in different climate zones: a case study of the Sichuan–Yunnan–Loess plateau ecological shelter, China - Hao-Rui Li; Shuai Ma; Ming Zhang; Yun-Ke Yin; Hai-Bo Hu; Liang-Jie Wang; Jiang Jiang (Environment, Development and Sustainability, 2025)

Streptococcus suis AdcA interacts with factor H and inhibits C3b deposition on the bacteria to participate in complement evasion - Siqi Pang; Zhulin Qiao; Jiajia Xu; Hao Tang; Qiuhong Zhang; Weiyao Han; Lu Peng; Jiaojiao Yang; Jiao Zhang; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2025)

Corrigendum to “Infection mechanisms of Pochonia chlamydosporia: A breakthrough in Fasciola hepatica egg control” [Vet. Parasitol. 337 (2025)110463] - Luyao Hao; Hongyou Liu; Fengmiao Zhao; Yuan Ma; Zhengyi Li; Rui Wang (Veterinary Parasitology, 2025)

Infection mechanisms of Pochonia chlamydosporia: A breakthrough in Fasciola hepatica egg control - Luyao Hao; Hongyou Liu; Fengmiao Zhao; Yuan Ma; Zhengyi Li; Rui Wang (Veterinary Parasitology, 2025)

Evolution and functional characterization of a biosynthetic gene cluster for saponin biosynthesis in Sapindaceae - Yingxiao Mai; Huimin Hu; Wenjuan Ji; Yaxuan Xiao; Hong Zhou; Zaohai Zeng; Wenshu Lv; Xingling Su; Jiakun Zheng; Jing Xu; Yanwei Hao; Zhenhua Liu; et al. (Molecular Plant, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Aluminum and microplastic release from reflective agricultural films disrupt microbial communities and functions in soil - Kai Wang; Markus Flury; Yakov Kuzyakov; Hao Zhang; Wei Zhu; Rui Jiang (Journal of Hazardous Materials, 2025)

Synthesis of high yield mesoporous silica for efficient CO2 adsorption using coal gasification fine slag - Zekai Miao; Hao Ge; Xinran Han; Rui Wu; Hai Zhu; Congchao Zhang; Shengping Wang (Fuel, 2025)

Flexural behavior of reinforced concrete beams subjected to natural corrosion in marine environment - Yang Liu; Wei-Ping Zhang; Chao Jiang; Feng Wu; Jun-Li Qiu; Rui-Lin Wang; Nai-Hao Zheng (Engineering Structures, 2025)

An innovative and efficient approach for slope reliability analysis: Machine learning based surrogate modeling with advanced attention mechanisms - Nenghao Huang; Yu Han; Weiwei Xie; Rui Hu; Hao Peng; Guanxian Song; Menglan Wu; Menglong Zhu; Hua Wei; Ming Liang (Engineering Geology, 2025)

VPS35/Retromer-dependent MT1-MMP regulation confers melanoma metastasis - Qinggang Hao; Yan Bai; Ruiqi Guan; Rui Dong; Weiyu Bai; Hayam Hamdy; Liqiong Wang; Mingyao Meng; Yan Sun; Junling Shen; Jianwei Sun (Science China Life Sciences, 2025)

Inversion of Stress Redistribution Based on Focal Mechanism Solutions: A Case Study of the Dongtan Coal Mine - Kai Zhan; Hao Luo; Rui Xu; Xiaotao Wen; Cong Wang (Rock Mechanics and Rock Engineering, 2025)

Transcriptomics and Metabolomics Analysis Reveal the Mechanism of Hormones Regulation of the Flower Bud Formation and Development in Phalaenopsis Orchid - Xiaofen Gao; Yang Hao; Xiaoying Yang; Yanping Shi; Li Zhang; Rui Yan (Journal of Plant Growth Regulation, 2025)

Evaluation of the Products from Hydrothermal Liquefaction of Palm Empty Fruit Bunch - Brendan Ong Wei Ling; Han Hao Chon; Rui Hong Teoh; Suchithra Thangalazhy-Gopakumar (BioEnergy Research, 2025)

Cerebellar large-scale network connectivity in Parkinson’s disease: associations with emotion, cognition, and aging effects - Chentao He; Zhenzhen Chen; Mengfei Cai; Piao Zhang; Hao Li; Xi Chen; Qi Qi; Rui Yang; Yan Li; Zaiyi Liu; Lijuan Wang; Yuhu Zhang (Brain Imaging and Behavior, 2025)

Resilience maintenance strategy for mixed vehicle traffic on port expressway based on lane management - Yao Sun; Dongxuan Bai; Guoxiao Han; Rui Feng; Jinghan Hao; Baozhen Yao (Ocean & Coastal Management, 2025)

Bisphenol S promotes clear cell renal cell carcinoma progression by modulating the WNT5A-dependent EMT pathway - Hua Zhang; Fei Lin; Bo-Han Lin; Xiong-Lin Sun; Qing-Shui Zheng; Rui Gao; Yong Wei; Shao-Hao Chen; Xue-Yi Xue (Toxicology, 2025)

Mangiferin promotes porcine oocyte maturation and delays the postovulatory aging process by up-regulating NRF2 levels - Xiuwen Yuan; Hewei Ji; Yuhao Zhang; Huilin Peng; Neng-hao Cao; Jia-jun Ren; Xue-rui Yao; Xingwei Liang; Nam-hyung Kim; Yong-nan Xu; Ying-hua Li (Theriogenology, 2025)

Using open GPS trajectory data to quantify nature-based recreation at a national scale - Pei Wang; Zhicong Zhao; Ruijia Zhu; Hao Wang; Shaochong Xue; Yiwei Liu; Fangyi Wang; Yue Cao; Le Yu; Rui Yang (Resources, Conservation and Recycling, 2025)

Nitrogen addition and rhizosphere effects differentially shape prokaryotic and fungal communities in peanut–maize cropping systems - Yang Chen; Zejin Zhang; Yichao Rui; Carson Pearl; Sheng Lu; Fang Wang; Flemming Ekelund; Yanbin Hao; Xiaoyong Cui (Rhizosphere, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Au-modified Cu2O with CO-enriched active sites for tandem catalysis of CO2 deep-reduction to C2H4 - Ji-song Yan; Wei Qiu; Hao Liu; Qing-shan Wang; Ling-qi Yu; Sheng-hui Guo; Rui-tang Guo (Journal of Environmental Chemical Engineering, 2025)

Hydrophobically modified Cu-ZnO-Al2O3 catalyst for CO2 hydrogenation to methanol - Xiuyun Jiang; Jucang Ke; Rui Li; Hao Huang; Zhihao Liu; Haozhe Feng; Qingxiang Ma; Xinhua Gao; Guangbo Liu; Xiaobo Feng; Tian-Sheng Zhao; Noritatsu Tsubaki (Journal of Environmental Chemical Engineering, 2025)

Cement-mortar lining failure and metal release caused by electrochemical corrosion of ductile iron pipes in drinking water distribution systems - Hao Guo; Rui Wang; Menghan Jiang; Yimei Tian; Yapeng Jin; Weigao Zhao; Chenwan Wang; Jianhua Yin (Journal of Environmental Sciences, 2025)

Intelligent double-layer pads containing blueberry anthocyanins/citric acid/tricolor lake for chilled pork real-time freshness monitoring - Junna Sun; Ye Zhang; Rui Liu; Jian Du; Qingdai Liu; Tianxin Wang; Yuan Wang; Hao Wang (Food Chemistry, 2025)

Discovery of novel DPP4 inhibitory peptides from egg yolk by machine learning and molecular docking: In vitro and in vivo validation - Yujie Xu; Yiqiao Pei; Zhifu Liu; Peng Tan; Rui Liu; Lulu Chu; Ye Zhang; Wenjie Wang; Hao Wang (Food Chemistry, 2025)

Tethering pH-Induced structural modifications of ovomucin to stabilize W1/O/W2 double emulsions for enhanced protection of Companilactobacillus crustorum MN047 - Bohan Sun; Youming Liu; Rui Sun; Wei Hu; Yi Hao; Yuanyuan Shan; Pengrui Wu; Charles S. Brennan; Gang Wu; Yanglei Yi; Xin Lü (Food Hydrocolloids, 2025)

Blast response and multi-objective optimization of multi-layered kirigami corrugated sandwich panels - Hao Liu; Zengshen Yue; Rui Zhang; Jiawei Lu; Jian Zhu (Engineering Structures, 2025)

Field and numerical investigations on linkage failure of the main roof and pumpable supports in the pre-excavation recovery room - Dong Zhang; Jianbiao Bai; Yonghong Guo; Zizheng Zhang; Rui Wang; Zhijun Tian; Shuai Yan; Qiancheng Zhu; Min Deng; Hao Fu; Shuaigang Liu (Engineering Geology, 2025)

Corrigendum to ‘Design of polypyrrole layer enhanced MIL-88B(Fe) composite electrode material for electrosorption separation of copper ions’ [Desalination 603 (15 May 2025) 118606] - Lujie Nie; Yanna Ren; Lei Wang; Yingying Wang; Jiajun An; Jiajin Hao; Jiaqi Wang; Chen Zhao; Xin Zhang; Yongtao Lv; Miaolu He; Hongyun Nie; et al. (Desalination, 2025)

Multi-shank flexible implantable neural interface for long-term olfactory neuron recording toward odor perception - Qunchen Yuan; Jiale Wang; Chunlian Qin; Shunuo Shang; Haoze Xu; Fan Wu; Yong Qiu; Haoting Zhang; Rui Sun; Ping Wang; Liujing Zhuang; Hao Wan (Chemical Engineering Journal, 2025)

A new CNN-GRU deep learning framework optimized by CHIO for precise prediction of debris flow velocity - Liangxu Shen; Tianxing Ma; Hao Chen; Bingfeng Ye; Rui Luo; Hongyue Sun (Stochastic Environmental Research and Risk Assessment, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Transcriptomic and metabolomic analyses reveal the key factors through which exogenous hormones regulate pedicel formation in Phalaenopsis orchids - Rui Yan; Yunyun Huo; Xiaofen Gao; Yang Hao (Horticulture, Environment, and Biotechnology, 2025)

Modeling and Quantitative Assessment of Critical Defects in Shield Tunnels with Cascading Effects - Xiangyu Chang; Rui Zhang; Jianxiao Mao; Yuguang Fu; Hongyun Fan; Hao Wang (Geotechnical and Geological Engineering, 2025)

Mesoscopic interpretation of fines clogging-induced permeability changes in completely decomposed granite - Rui Chen; Zhi-yuan Luo; Ai-guo Li; Hao Wang; Lei-lei Liu; Liang-liang Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Identification of Age-Related Characteristic Genes Involved in Severe COVID-19 Infection Among Elderly Patients Using Machine Learning and Immune Cell Infiltration Analysis - Huan Li; Jin Zhao; Yan Xing; Jia Chen; Ziying Wen; Rui Ma; Fengxia Han; Boyong Huang; Hao Wang; Cui Li; Yang Chen; Xiaoxuan Ning (Biochemical Genetics, 2025)

The antioxidant protein PntA coordinates with OmpW to resist oxidant stress in Actinobacillus pleuropneumoniae - Weiyao Han; Qiuhong Zhang; Zhen Luo; Hao Tang; Xiabing Chen; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

CYP321F3 mediates metabolic resistance to methoxyfenozide in rice stem borer, Chilo suppressalis - Fang-Rui Guo; Shu-Chao Wang; Yan Liu; Shuai Wang; Jing-Mei Huang; Hao Sun; Lin-Feng He; Yuan Xie; Song-Tao Qiao; Feng-Xia Yang; Chris Bass; Cong-Fen Gao; et al. (Pesticide Biochemistry and Physiology, 2025)

Behavior of truss connectors in composite walls subjected to cyclic loading - Ying Qin; Weifeng Hao; Rui Yin; Wei Ren; Ke Jiang (Engineering Structures, 2025)

Design of polypyrrole layer enhanced MIL-88B(Fe) composite electrode material for electrosorption separation of copper ions - Lujie Nie; Yanna Ren; Lei Wang; Yingying Wang; Jiajun An; Jiajin Hao; Jiaqi Wang; Chen Zhao; Xin Zhang; Yongtao Lv; Miaolu He; Hongyun Nie; et al. (Desalination, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Radiochromic perovskite La2MgZrO6:Pr for X-ray imaging and ionizing radiation detection - Zi-Hao Chen; Qiang Tang; Jian-An Zeng; Haijiao Xie; Rui Zou; Jing Wang; Bo-Mei Liu (Chemical Engineering Journal, 2025)

Cation-induced phase transformation in PVDF for efficient energy harvesting - Dinku Hazarika; Jiaqi Lu; Jiafeng Ni; Chuanrui Chen; Muhammad Naeem Shah; Liangquan Xu; Jianhui Wu; Kaihang Zhang; Jie Li; Xinyu Cai; Rui Wan; Hao Jin; et al. (Chemical Engineering Journal, 2025)

Electronic structure modulation and substance transfer acceleration induced by synchronous construction of a tri-functional electrocatalyst with host–guest role swapping in zinc-air batteries - Liping Hao; Tao Yu; Xiaomao Liu; Jinsheng Li; Rui Guo; Xuanwen Liu; Sihan Chen; Chunming Liu (Chemical Engineering Journal, 2025)

Preparation of sodium alginate antibacterial porous composite pads embedded with centrifugally spun nanofibers by freeze-drying and recasting for active food packaging - Hao Wang; Mengjiao Li; Rui Ren; Zhennan Gao; Lingna Meng; Ziyi Li; Chuanai Cao (Carbohydrate Polymers, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Design optimization of dual-circulation wells using deep learning - Yang Sikai; Fang Zhang; Ma Yanling; Ke Hao; Zhou Rui; Muhammad Sadam (Stochastic Environmental Research and Risk Assessment, 2025)

Metabolomics provide novel insights into the settlement and metamorphosis of the scyphozoan jellyfish Aurelia coerulea - Shuai Liu; Xiaoyu Tang; Xuerui Liu; Rui Zhang; Xiangrui Guo; Zhen Yu; Ye Zhao; Jiehui Yin; Hao Sun; Yanying Zhang (Journal of Oceanology and Limnology, 2025)

Cardiovascular dysfunction and altered lysosomal signaling in a murine model of acid sphingomyelinase deficiency - Yun-Ting Wang; Alexandra K. Moura; Rui Zuo; Kiana Roudbari; Jenny Z. Hu; Saher A. Khan; Zhengchao Wang; Yangping Shentu; Mi Wang; Pin-Lan Li; Jiukuan Hao; Yang Zhang; et al. (Journal of Molecular Medicine, 2025)

Optimizing cultivation substrate moisture and calcium application for the comprehensive growth of cucumber under different air temperatures - Jing Wang; Feng Qu; Jiayue Zhang; Rui Zhao; Hao Wang; Xiaohui Hu (Irrigation Science, 2025)

Applicability analysis of passive containment heat remove system calculation model based on integrated code - Nan Zhang; Shuai Yuan; Xiang Xia; Chang Wang; Rui Hao (Annals of Nuclear Energy, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Undrained permanent deformation characteristics of Yellow River silt under one-way cyclic loads - Yuke Wang; Hao Chen; Yujie Xue; Rui Jiang; Xiang Yu; Xiaoying Lin (Marine Georesources & Geotechnology, 2025)

Identification and fungicide sensitivity of Fusarium oxysporum, the cause of Fusarium wilt on Codonopsis pilosula in Shanxi Province (Lu Dangshen), China - Yan Wang; Dainan Hao; Haozhe Jiang; Zhaoxiong Fei; Rui Zhao; Jiaxin Gao; Guangxin Li; Chunwei Wang (Crop Protection, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Atmospheric carbonyls in urban Beijing in the summertime under the continuous implementation of clean air actions: Decreasing trends, source apportionments and new insights for control strategies - Xin Zhang; Fang Bi; Mingzhu Li; Lu Zhao; Hao Zhang; Yunfeng Li; Likun Xue; Rui Gao; Yujie Zhang; Xuezhong Wang; Zhenhai Wu; Zhanshan Wang; et al. (Journal of Cleaner Production, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Selective preparation of aromatic compounds from catalytic pyrolysis polyester coating over Ni, Mo and Co metal modified ZSM-5 - Zhen-Qiang Yu; Yao-Xin Xiao; Dong Liang; Che Zhao; Zhen Huang; Gang-Qi Cheng; Rui Shan; Hao-Ran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Selenium doped CeO2 catalysts efficiently activated H2O2 for norfloxacin degradation: Oxygen vacancies mediated electron transfer processes - Zhengkai Hao; Lipeng Jiang; Rui Tan; Yaxin Wang; Bowen Deng; Xinrui Yan; Dengqian Chen; Dongxue Cao; Limei Chen; Dongdong Liu (Journal of Environmental Chemical Engineering, 2025)

Field test of geosynthetic-reinforced floating pile-supported embankments on soft soil - Rui Rui; Shi-kai He; Long-fan Peng; S.J.M. Van Eekelen; Liang-hao Li; Yu-qiu Ye (Geotextiles and Geomembranes, 2025)

Corrigendum to “Super antioxidant and high antibacterial ability bi-functional xylitol/2-hydroxypropyl-β-cyclodextrin carbon dots with hydroxyl-functionalized for rainbow trout preservation” [Food Research International 203 (2025) 115792] - Dangfeng Wang; Hao Dong; Yang Jiang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Research International, 2025)

Correlation of lipid hydrolysis, oxidation, and molecular transformation with volatile compound revolution in pork during postmortem wet-aging process - Kaihua Zhang; Rui Hao; Shouwei Wang; Zheqi Zhang; Dan Li; Xiaoman Li; Bing Zhao; Shunliang Zhang; Yan Zhao; Xiangning Chen (Food Chemistry, 2025)

Catalyst pre-diffusion: An efficient strategy for the construction of COF nanofiltration membranes - Lin Yu; Aida Aibulatova; Zhen-Liang Xu; Li Li; Changqing Hao; Rui Jia; Yin-Xin Fang; Yan Zheng; Yong-Jian Tang (Desalination, 2025)

Regulation pattern of carotenoid biosynthesis induced by low light stress in Dunaliella - Hao-Hong Chen; Jing-Xuan Wu; Rui-qi Chen; Sacha Fouquay O’Donnell; Ming-Hua Liang; Jian-Guo Jiang (Bioresource Technology, 2025)

A large-scale gene co-expression network analysis reveals Glutamate Dehydrogenase 2 (GhGDH2_D03) as a hub regulator of salt and salt-alkali tolerance in cotton - Rui Hao; Zhan Gao; Xianliang Zhang; Xingxing Wang; Wuwei Ye; Xiugui Chen; Xiongfeng Ma; Xianpeng Xiong; Guanjing Hu (Plant Molecular Biology, 2025)

Immune cell traits and causal relationships with cholecystitis: a mendelian randomization analysis - Ze-fa Xiao; Wei-hao Chai; Xiao-long Shu; Hong-rui Yuan; Fei Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Suitability and Bearing Behavior of PHC Pipe Piles in Underlying Mudstone - Qing-rui Feng; Hao-feng Xing; Hong-bo Chen; Hua Wei (Geotechnical and Geological Engineering, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Ratio Fluorescence Sensor Based on Bimetal MOFs for the Detection of Hg2+and H2O2 - Bo-Ming Han; Hao-Rui Zhang; Wen-Jie Gao; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Journal of Fluorescence, 2025)

Detecting wheat yellow dwarf disease by employing a Dual-Branch multiscale model from UAV multispectral images - Xingan Hao; Zexi Wang; Yuchen Zhang; Feilong Li; Meili Wang; Jialin Li; Rui Mao (Computers and Electronics in Agriculture, 2025)

Vertical migration characteristics of polychlorinated biphenyls (PCBs) in estuarine and coastal zones under complex environmental conditions - Rui Pan; Nan Zhang; Jiqing Li; Xiao Xiao; Hao Wu; Xianzhang Dang; Shuya Hu (Marine Pollution Bulletin, 2025)

Novel approaches for alleviating shallow soil compaction using microbial fertilizers and their beneficial impacts on plant growth and soil physicochemical properties - Xiang Yao; Hailin Guo; Dandan Li; Junqin Zong; Rui Zhang; Jingbo Chen; Dongli Hao; Xinyong Zhao; Jianxiu Liu; Haoran Wang; Chunjie Li (Soil and Tillage Research, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

RNA interference-mediated silencing of GNBP2 reduces the immunity of stored pest Tribolium castaneum against bacteria - Jingxiu Bi; Xiangjun Ma; Yuying Jiang; Pingxiang Liu; Rui Gao; Tong Zhao; Xuexia Yuan; Haining Hao; Bin Li; Yutao Wang (Pesticide Biochemistry and Physiology, 2025)

A small RNA effector conserved in herbivore insects suppresses host plant defense by cross-kingdom gene silencing - Wen-Hao Han; Shun-Xia Ji; Feng-Bin Zhang; Hong-Da Song; Jun-Xia Wang; Xiao-Ping Fan; Rui Xie; Shu-Sheng Liu; Xiao-Wei Wang (Molecular Plant, 2025)

Insight into resistance relaxation characteristics of proton exchange membrane fuel cell in purge operation: Experiment, application, and mechanisms - Yuqing Li; Hao Yuan; Xueyuan Wang; Xuezhe Wei; Jiangong Zhu; Rui Ma; Lei Gao; Haifeng Dai (Journal of Cleaner Production, 2025)

Fish oil emulsions stabilized by enzymatic hydrolysis, glycation, and fibrillation of β-Lg: Stability and EPA/DHA bioaccessibility - Qingchun Zhang; Hao Zhu; Rui Wang; Jianfei He; Christos Ritzoulis; Weilin Liu; Wei Tang; Jianhua Liu (Food Chemistry, 2025)

Amelioration of myofibrillar protein emulsion gel properties by mildly oxidized sunflower oil - Jinyang Chang; Rui Liu; BeiBei Zheng; Xinzhu Gao; Baorui Li; Ye Zhang; Tianxin Wang; Hao Wang (Food Chemistry, 2025)

Microbial community structure and water quality performance in local scrubber reclaim system for water reclamation of the semiconductor industry: A case study of a semiconductor plant in Beijing - Yu-Di Li; Yin-Hu Wu; Hao-Bin Wang; Rui-Ning Wang; Pei-Hua Li; Bang-Hao Huang; Hong-Ying Hu (Environmental Research, 2025)

Environmentally relevant concentrations of DBDPE (decabromodiphenyl ethane) induce intestinal toxicity in silkworms (Bombyx mori L.) - Xue Luo; Rui Xing; Man Xu; Hui-Jun Jiang; Yu-Rui Wang; Ming-Yue Hu; Hao Zhang; Feng Ge; Wei Zhang; Hong-Wei Wang (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

PKS1 involved in anthocyanin accumulation in red-skinned pear fruit - Lei Guo; Yuting Hao; Ying Tang; Mengjia Wu; Rui Zhai; Chengquan Yang; Lingfei Xu; Zhigang Wang (Plant Cell Reports, 2025)

The Impact of Different Mating Systems on Locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Ruo-Xi Wang; Jia-Xin Xu; Kai-Chen Weng; An-Xin Wang; Hao Huang; Yu-Yuan Lu; Yi-Jie Chen; Yu-Chen Wang (Journal of Insect Behavior, 2025)

A new oviraptorosaur from the Lower Cretaceous Miaogou Formation of western Inner Mongolia, China - Mingze Hao; Zhiyu Li; Zhili Wang; Shuqiong Wang; Feimin Ma; Qinggele; J. Logan King; Rui Pei; Qi Zhao; Xing Xu (Cretaceous Research, 2025)

Prediction of sandstone porosity in coal seam roof based on variable mode decomposition and random forest method - Ya-ping Huang; Xue-mei Qi; Yan Cheng; Ling-ling Zhou; Jia-hao Yan; Fan-rui Huang (Applied Geophysics, 2025)

Seismic Prediction Methods for Tidal Flat Sand Bodies in the Shunbei Area of the Tarim Basin - Zhi-peng Sun; Rui-zhao Yang; Jing-rui Chen; Hao Zhang; Shi-jie Zhang; Peng-hui Yang; Feng Geng (Applied Geophysics, 2025)

Effects of ammonia nitrogen stress on liver tissue structure and physiological indicators, and metabolomic analysis of juvenile four-finger threadfin (Eleutheronema tetradactylum) - Jing-Hui Jin; Hao-Jie Wang; Eric Amenyogbe; Yi Lu; Rui-Tao Xie; Zhong-Liang Wang; Jian-Sheng Huang (Frontiers in Marine Science, 2025)
In intensive aquaculture, ammonia nitrogen (NH₃-N) is a major pollutant, causing oxidative stress and immune damage to aquatic organisms. The liver is crucial in protecting against biotic and abiotic stresses, but the response mechanisms to ammonia stress in juvenile four-finger threadfin ( Eleutheronema tetradactylum ) are not well understood. This study investigated these mechanisms by examining liver tissue structure, enzyme activities, and metabolomic changes in response to ammonia stress. Juvenile four-finger threadfin (7.4 ± 0.6 g) were divided into control, NH₃-N stress (50% LC 50 96 h , 10 ± 0.4 mg/L), and postexposure recovery groups. Stress durations of 12, 24, 48, and 96 h were evaluated, followed by 48 h recovery. Prolonged ammonia stress led to increased liver tissue damage, including disordered hepatocyte arrangement, swelling, necrosis, and the disappearance of nucleoli. After 48 h recovery, liver damage was alleviated but did not fully return to control levels, suggesting that the toxic effects of ammonia are recoverable yet persistent. Antioxidant enzyme activities (superoxide dismutase, catalase, and glutathione peroxidase) initially showed significant increases peaking at 24 h after stress, before declining by 96 h. Malondialdehyde levels rose initially and remained elevated compared with controls. After 48 h of recovery, antioxidant enzyme activity had not returned to control levels, indicating inadequate recovery from ROS-induced stress. Metabolomic analysis revealed 1219 significantly different metabolites in the 96 h stress group, with increases in L -histidine, L -threonine, and cholesterol. In the recovery group, 904 metabolites differed from controls, with notable reductions in urea and choline. The key affected pathways included amino acid, lipid, and nucleotide metabolism. This study elucidates the toxic effects of ammonia nitrogen on juvenile four-finger threadfin and their adaptive responses through physiological and metabolomic changes, providing insights for aquaculture practices and breeding ammonia-tolerant strains.

TreegrowNet: a completion network for incomplete single tree point cloud from TLS - Tao Zhang; Chunhua Hu; Jiangang Han; Hao Sun; Rui Wang; Zhen Jing (International Journal of Remote Sensing, 2025)

Antagonistic activity of Pochonia chlamydosporia against three helminth eggs and characterization of its serine protease - Luyao Hao; Fengmiao Zhao; Yuan Guo; Yuan Ma; Zhengyi Li; Wen Wang; Hongliang Luo; Rui Wang (Veterinary Parasitology, 2025)

Parametric investigation of suction actuators on the tunnel wall for alleviating pressure interactions in high-speed maglev train/tunnel system - Zheng-Wei Chen; Zhan-Hao Guo; Yi-Qing Ni; Zi-Jian Guo; Tian-Tian Wang; En-Ze Rui; Guang-Zhi Zeng (Tunnelling and Underground Space Technology, 2025)

Ancient genomes shed light on the long-term genetic stability in the Central Plain of China - Hao Ma; Yawei Zhou; Rui Wang; Fei Yan; Haodong Chen; Limin Qiu; Jing Zhao; Li Jin; Chuan-Chao Wang (Science Bulletin, 2025)

Cytotoxic monoterpenoid indole alkaloids from Tabernaemontana bovina - Bang-Yin Tan; Hua Lin; Heng-Gang Zhang; Jing-Zhi Zhao; Shi-Yu Deng; Rui-Rong Guo; Xin Wei; Lan-Chun Zhang; Rong-Ping Zhang; Hao-Fei Yu (Phytochemistry, 2025)

Physical insight into transient hydrodynamics and corresponding flow structures of a pitching hydrofoil via boundary vorticity dynamics - Hui-yun Hao; Rui Yuan; Qin Wu; Biao Huang (Ocean Engineering, 2025)

Enhanced electron transport through hydrogen bonds and Ag nanoparticles in the PCN-222/Ag/COF core–shell photocatalyst for efficient oxytetracycline degradation - Bing-Bing Lu; Jia-Chang Lu; Qing-Yun Zhao; Rui Wang; Ze-Lin Chen; Ji-Qiang Guan; Hao Liu; Ying Fu; Fei Ye (Journal of Cleaner Production, 2025)

Adsorption characteristics and mechanism insights of K2FeO4 coupling with ZnCl2-assisted modified functionalized biochar for Pb (II) in wastewater - Xuewen Yang; Fulin Yang; Can Liu; Hao Sun; Defa Hou; Yunwu Zheng; Hui Gao; Rui Shi; Xiahong He; Xu Lin (Journal of Environmental Chemical Engineering, 2025)

Non-steady flow decomposition behaviors of heat and mass transfer on intrinsic kinetics for methane hydrate particles transported in pipelines - Xinfu Liu; Chunhua Liu; Qingping Li; Zhongxian Hao; Rui Qin; Haiyuan Yao; Ming Li; Zunzhao Li (Fuel, 2025)

Super antioxidant and high antibacterial ability bi-functional xylitol/2-hydroxypropyl-β-cyclodextrin carbon dots with hydroxyl-functionalized for rainbow trout preservation - Dangfeng Wang; Hao Dong; Yang Jiang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Research International, 2025)

Erroneous Differentiation of Tendon Stem/Progenitor Cells in the Pathogenesis of Tendinopathy: Current Evidence and Future Perspectives - Yucheng Gao; Hao Wang; Liu Shi; Panpan Lu; Guangchun Dai; Ming Zhang; Bowen Han; Mumin Cao; Yingjuan Li; Yunfeng Rui (Stem Cell Reviews and Reports, 2025)

Spatial Characteristics of the Plasma Spark Source Wavelet - Jia Wei; Xiaozhu Hao; Jing Feng; Rui Yang; Lei Xing; Huaishan Liu; Wei Wang; Zhiqiang Wu; Dong Zhang; Linwei Li (Journal of Ocean University of China, 2025)

Assessment of Peripheral Neuropathy Using Current Perception Threshold Measurement in Patients with Spinocerebellar Ataxia Type 3 - Xia-Hua Liu; Wei Lin; Hao-Ling Xu; Mao-Lin Cui; Zhuo-Ying Huang; Ying Li; Nan-Nan Zhang; Ning Wang; Zhi-Yong Wang; Shi-Rui Gan (The Cerebellum, 2025)

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

U-shaped relationship between environmental regulation and the digital transformation of the Chinese coal industry: Mechanism and moderating effects - Pu-hao Guo; Xiang-qian Wang; Xiang-rui Meng (Journal of Environmental Management, 2025)

Noble gases in Paleozoic shale fluids document tectonic events and fluid migration in the Upper Yangtze Block - Rui Liu; Tao Wen; Daniele L. Pinti; Rui Xu; Fang Hao; Shang Xu; Zhiguo Shu (International Journal of Coal Geology, 2025)

DFT study the influence of active site structure on the electrocatalytic nitrogen reduction reaction - Ke Shi; Linxia Cui; Mingyuan Zhang; Yang Jiang; Rui Gao; Haigang Hao (Fuel, 2025)

Design method of simplified dynamic test model for high-rise building with underground structures considering nonlinear behavior similarity - Rui Wang; Zhi-Qian Dong; Gang Li; Ding-Hao Yu; Yao-Zhong Cui; Han Zhang; Jia-Long Li (Engineering Structures, 2025)

Fatigue behavior of square steel strut-to-gusset plate welded connections under eccentric compression: Full-scale and reduced-scale tests - Xiaoqing Xu; Hongfa Luo; Bin Wang; Yuqing Liu; Kaixiang Miao; Rui Hao; Weiwei Lin; Yuwen Zhou; Dongyang He; Md Asadujjaman (Engineering Structures, 2025)

Reversible multilevel stimuli-responsiveness and multicolor room temperature phosphorescence to fluorescence transition based on a metal–organic framework system - Hui-Li Sun; Zhong-Hao Wang; Rui-Qi Huang; Zhuo-Di Chen; Mei Pan (Chemical Engineering Journal, 2025)

Enhanced wastewater treatment using biochar-supported layered-double-hydroxide composites - Ao Huang; Nan Zhang; Qian-Bin Wang; Bo-Han Zhao; Rui-Bao Zhang; Ming Cheng; Chen Shi; Xiao-Di Hao (Chemical Engineering Journal, 2025)

Sandwich-like NiFe-LDH/MnCO3/MXene ternary nanocomposites serve as battery-type electrode for high-performance asymmetric supercapacitor - Liangchen He; Ping Cai; Huajun Lai; Kecheng Lu; Zebing Xu; Rui Zeng; Chenggang Hao; Zhongmin Wang; Weijiang Gan (Chemical Engineering Journal, 2025)

Water-triggered stimuli-responsive luminescent crown-ether-coordinated cuprous bromides for multi-functional applications - Rui Wu; Hao Yang; Meifeng Jiang; Hui Tong; Xinyu Hu; Ziyang Liu; Chunhua Luo; Hui Peng; Hechun Lin (Chemical Engineering Journal, 2025)

Readily recyclable, degradable, stretchable, highly conductive, anti-freezing and anti-drying glycerohydrogel for triboelectric nanogenerator - Sihan Jiang; Yang Wang; Meiqin Tian; Haiyang Zhang; Rui Wang; Haokun Yan; Hao Tan; Rasoul Esmaeely Neisiany; Wei Sun; Zhengwei You (Chemical Engineering Journal, 2025)

Highly active and CO-resistant PdRuMo/C with a wide potential-stable window toward alkaline hydrogen oxidation reaction - Chunxiao Chai; Haoliang Huang; Hao Yang; Jiaqi Qin; Chongyun Sun; Yongpeng Li; Zhaoqi Wang; Xinwei Zhao; Zhongyu Qiu; Tiantian Li; Jiahuan Li; Rui Gao; et al. (Chemical Engineering Journal, 2025)

Interfacial built-in electric field in 2D Ni(OH)2 heterojunction with the sodium organic compound for enhanced oxygen evolution catalysis - Jiao Zhou; Mingyuan Zhang; Baiyu Ren; Qian Yi; Hao Yu; Baoyue Zhang; Ang Li; Xinyi Hu; Zhong Li; Guanyu Chen; Yinfen Cheng; Rui Gao; et al. (Chemical Engineering Journal, 2025)

ε-Poly-L-lysine/rhamnolipid bifunctional coating based on green electrostatic assembly technology for fruit packaging and preservation - Quanfei Li; Qian Chen; Kai Yang; Hao Liu; Delei Xu; Yian Gu; Liang Sun; Peng Lei; Rui Wang; Hong Xu (Chemical Engineering Journal, 2025)

Eliminating bacterial endotoxins and associated inhalation hazards in reclaimed water via ultraviolet/ferrate combination disinfection - Muhan Sun; Xiaoxu Jiang; Rui Liu; Deqin Kong; Hao Wu; Zhao Wang; Gang Zheng; Chongmiao Zhang; Weihua Yu (Chemical Engineering Journal, 2025)

A combined strategy of brain neuroprotection and endogenous neuroregeneration for enhanced intracerebral hemorrhage treatment via an injectable biomimetic hydrogel with efficient ROS scavenging and therapeutics delivery - Jiake Xu; Luyao Wan; Xueqi Wang; Yang Wei; Yinhai He; Shenglan You; Rui Zhong; Chengwei Wang; Hao Li; Chao You; Meng Tian (Chemical Engineering Journal, 2025)

A Microbially Induced Magnesia Carbonation (MIMC) Method with Potential Application for Crack Healing of Sandstone Cultural Relics: Improving Interfacial Bonding Strength - Zhi-Hao Dong; Xiao-Hua Pan; Chao-Sheng Tang; Dian-Long Wang; Rui Wang; Bin Shi (Rock Mechanics and Rock Engineering, 2025)

Therapeutic Potential of Mesenchymal Stem Cell-Derived Exosomes in Spinal Cord Injury - Jing An; Bo Chen; Rui Zhang; Ding Tian; Kuohao Shi; Lingling Zhang; Gaorong Zhang; Jingchao Wang; Hao Yang (Molecular Neurobiology, 2025)

Identifying the Pathogenicity of a Novel NPRL3 Missense Mutation Using Personalized Cortical Organoid Model of Focal Cortical Dysplasia - Rongrong Lu; Ying Xu; Hao Li; Man Xiong; Wenhao Zhou; Weijun Feng; Rui Zhao (Journal of Molecular Neuroscience, 2024)

Formation and evolution of thermokarst landslides in the Qinghai-Tibet Plateau, China - Tao Wei; Hao Wang; Peng Cui; Yan Wang; Bo Zhang; Rui-Long Wei; Zhen-Xing Liu; Chao-Yue Li (Science of The Total Environment, 2024)

Neolithization of Dawenkou culture in the lower Yellow River involved the demic diffusion from the Central Plain - Fen Wang; Rui Wang; Hao Ma; Wen Zeng; Yongsheng Zhao; Hao Wu; Zhongming Tang; Haifeng He; Hui Fang; Chuan-Chao Wang (Science Bulletin, 2024)

Mechanisms of selectivity for azadirachtin in honeybees (Apis cerana): A new strategy for avoiding thiamethoxam ingestion - Hao Wu; Sheng-nan Li; Rui-quan Hou; Peng-rui Du; Kun-yu Zhao; Muhammad Zeeshan; Han-hong Xu; Zhi-xiang Zhang; Pei-wen Zhang (Pesticide Biochemistry and Physiology, 2024)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

Holocene paleoenvironment of the Nihewan Basin, China, inferred from high-resolution luminescence dating and a multiproxy analysis of gully sediments - Qing-Hao Ma; Yu-Jie Guo; Hua-Rui Lei; Yu-He Shen; Jia-Jing Wang; Ya Liu; Zhen-Yu Zhou; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Physical mechanism-based simulation methods for soil and ground heat flux from observations at multi-sites - Zhaofei Liu; Dong Jiang; Rui Wang; Mengmeng Hao; Xingxing Zhang (Journal of Hydrology, 2024)

Embryonic exposure to glycopeptides induces acute toxicity and developmental neurotoxicity in zebrafish (Danio rerio) - Kehui Liu; Jiyang Du; Yuanyuan Ma; Haicheng Hu; Xinyan Ma; Rui Zhang; Hao Wang; Liyan Yu; Jingpu Zhang; Ying Han (Journal of Hazardous Materials, 2024)

Ultrabright silicon nanoparticles combined with o-phenylenediamine for ratiometric fluorescence and smartphone imaging dual-mode detection of nitrite - Wen-Jie Gao; Ming-Yue Tian; Xing-Hui Ren; Hao-Rui Zhang; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Journal of Hazardous Materials, 2024)

ABA-regulated MAPK signaling pathway promotes hormesis in sugar beet under cadmium exposure - Xiaoxin Zhao; Shuoqi Huang; Qi Yao; Rui He; Hao Wang; Zhaodan Xu; Wang Xing; Dali Liu (Journal of Hazardous Materials, 2024)

Endogenous phosphorus release from plateau lakes responds significantly to temperature variability over the last 50 years - Chao Yan; Rui Xia; Yan Chen; Lixin Jiao; Xiaoyu Liu; Yingze Yin; Qiang Hu; Kai Zhang; Lina Li; Hao Liu (Journal of Environmental Management, 2024)

Comparative organic pollutants removal efficiency and life cycle assessment of pyrolysis and solvent elution for industrial waste salt recycling - Xinyu Huang; Hao Wang; Min Song; Rui Chen; Saijun Lv; Haoqing Zhang; Chuqi Wang; Jerome Ramirez; Xiuxiu Ruan (Journal of Environmental Management, 2024)

Construction mechanisms, synthesis strategies, and photocatalytic applications of homojunction catalysts: A review - Hao-wen Zhu; Rui-tang Guo; Qing-shan Wang; Cong Liu; Heng-fei Cui; Ming-yang Liu; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Carboxymethyl chitosan coating infused with linalool-loaded molten globular β-Lactoglobulin nanoparticles for extended preservation of fresh-cut apples - Xiaotong Wang; Junxiang Zhu; Tianjin Tang; Lei Yang; Xingyu Chen; Si Meng; Rui Zheng; Hao Wu (Food Chemistry, 2024)

Composition of four polyphenol fractions extracted from partridge tea and their mechanisms on ameliorate insulin resistance in HepG2 cells - Ke-Xin Hao; Ying-Jing Zhang; Rui-Fang Zhong; Yi-Meng Li; Ling Wang; Xiao Chang; Da-Wei Wang; Jian-Guo Jiang; Wei Zhu (Food Bioscience, 2024)

An efficient bio-stabilization technology with bio‑carbonation of reactive magnesia for soil improvement in cold regions - Rui Wang; Chao-Sheng Tang; Xiao-Hua Pan; Dian-Long Wang; Zhi-Hao Dong; Xiancai Lu (Engineering Geology, 2024)

Exceeding the theoretical limit of interfacial evaporation efficiency by using the carbon-based aerogel evaporator with cold evaporation surface - Rui Yang; Xiaoke Li; Wei Xie; Size Zheng; Hao Shi; Jinwen Shi; Dengwei Jing (Desalination, 2024)

Molecular engineering in thizolo[5,4-d]thiazole-based donor-acceptor covalent organic framework Induced high-efficient photosynthesis of H2O2 - Ding-Ming Xue; Yi-Jun Zhang; Jing-Wen Chen; Hao Yang; Rui-Jie Xie; Shi-Chao Qi; Yuan-Qing Bu; Fei Liu; Hou-Hu Zhang; Jacques Lalevée (Chemical Engineering Journal, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Community of Arbuscular Mycorrhizal Fungi in the Rhizosphere Soils with Different Generations of Hybridized Progeny of Wild Erianthus arundinaceus and Sugarcane - Jin-Lian Zhang; Yi-Hao Kang; Juan Song; Huan-Ying Xu; Wei Zhang; Ying-Jie Nong; Qian Wang; Qin-Nan Wang; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Exploring retinal degenerative diseases through CRISPR-based screening - Rui Li; Fengming Yang; Boling Chu; Dehua Kong; Jing Hu; Hao Qian (Molecular Biology Reports, 2024)

Study of the effect of keap1 on oxidative stress in human umbilical cord mesenchymal stem cells - Hongrong Deng; Yunxia Chen; Huiwen Liu; Li Wang; Hao Xu; Bin Tan; Qin Yi; Rui Wang; Bolin He; Jie Tian; Jing Zhu (Molecular Biology Reports, 2024)
Background HucMSCs had shown promising efficacy in treating childhood diseases, but oxidative stress induced by the poor microenvironment at the site of damage resulted in low cell survival after transplantation, thus preventing the cells from maximizing therapeutic efficacy. Therefore, this study aimed to investigate the role and mechanism of keap1 in oxidative stress injury of human umbilical cord mesenchymal stem cells (hucMSCs), and to provide theoretical support for improving the efficacy of stem cell therapy. Methods The hucMSCs were treated with hypoxic low-sugar-free serum (GSDH) to mimic the damaged site microenvironment after implantation. Adenoviral overexpression of keap1 gene of hucMSCs was performed in vitro, and cell proliferation ability was detected by CCK8 assay, crystal violet staining assay, and cell cycle assay. Cellular redox level was assessed by Amplex Red, MDA, and GSH/GSSG kit. Mitochondrial morphology was evaluated by mitotracker Red staining. ATP production was estimated by ATP detection kit. The mRNA and protein expression levels were tested by western blotting and RT-qPCR. Results GSDH treatment substantially upregulated keap1 expression. Subsequently, we found that overexpression of keap1 notably inhibited cell proliferation and caused cells to stagnate in G1 phase. At the same time, overexpression of keap1 induced the production of large amounts of H 2 O 2 and the accumulation of MDA, but suppressed the GSH/GSSG ratio and the expression of antioxidant proteins NQO1 and SOD1, which caused oxidative stress damage. Overexpression of keap1 induced cells to produce a large number of dysfunctional mitochondria resulting in reduced ATP production. Moreover, Overexpression of keap1 significantly decreased the IKKβ protein level, while upregulating IkB mRNA levels and downregulating P50 mRNA levels. Conclusions Overexpression of keap1 may induce oxidative stress injury in hucMSCs by down-regulating IKKβ expression and inhibiting NF-κB pathway activation. This implies the importance of keap1 in hucMSCs and it may be a potential gene for genetic modification of hucMSCs.

Ignoring the food route underestimated human health risk from potentially toxic elements in agricultural environments of Ziyang, Shaanxi, China - Hao Wu; Jingyi Shi; Rongxin Ren; Jing Du; Fei Zhou; Mingxing Qi; Wanchen Zhao; Xiaoping Du; Zengrun Xia; Rui Ren; Dongli Liang (Environmental Geochemistry and Health, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

The effect of green coffee extract supplementation on obesity indices: critical umbrella review of interventional meta-analyses - Zhao Yang; Zhuo Shao; Weiyi Ouyang; Lu Ying; Rui Guo; Mingxuan Hao; Youfeng Liang; Wenjing Zhang; Xiaoyang Chen; Ruolan Chen; Changyuan Yu; Kousalya Prabahar; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Transcriptomic Analysis of Non-Specific Immune Responses in the Rice Field Eel (Monopterus albus) Infected with Pallisentis (Neosentis) celatus - Qin Lei; Xiaoling Li; Hao Wu; Yiwen Wan; Yukun Xie; Jinwei Gao; Wenwen Suo; Ming Zeng; Lingli Liu; Dongsheng Ou; Zhonggui Xie; Rui Song (Fishes, 2024)
Parasitic infestations present significant threats to the physiological health and ecological stability of aquatic species, frequently compromising immune defenses and elevating mortality rates. This study was conducted to elucidate the non-specific immune responses induced by Pallisentis (Neosentis) celatus infection in Monopterus albus, with a focus on intestinal histopathology and transcriptome gene expression. A histopathological examination revealed minor alterations in intestinal villi under low-level infection. A transcriptome analysis, performed using Illumina sequencing technology, identified 347 upregulated and 298 downregulated genes involved in critical biological pathways, such as lipid metabolism, immune responses, and the regulation of inflammatory processes. GO and KEGG analyses indicated the upregulation of immune-related pathways, including the RIG-I-like and IL-17 signaling pathways, highlighting a robust intestinal immune response. Conversely, the complement pathway was found to be downregulated, with significant suppression of C9, suggesting that the parasite may engage in immune evasion. Fluorescein-labeled C9 antibody assays confirmed reduced complement C9 levels in the infected tissues. A real-time PCR analysis identified the differential expression of eight genes, including C5, maats1, CFI, and gmnc, which were consistent with the sequencing results. These findings suggest that Pallisentis (Neosentis) celatus infection compromises intestinal health, induces inflammation, and activates non-specific immune responses in Monopterus albus. However, Pallisentis (Neosentis) celatus appears to evade the host immune response by suppressing the activation of complement components, thereby facilitating its reproductive parasitism.

Real-time lettuce-weed localization and weed severity classification based on lightweight YOLO convolutional neural networks for intelligent intra-row weed control - Rui Hu; Wen-Hao Su; Jia-Le Li; Yankun Peng (Computers and Electronics in Agriculture, 2024)

Green manuring combined with zeolite reduced nitrous oxide emissions in maize field by targeting microbial nitrogen transformations - Rui Liu; Danna Chang; Guopeng Zhou; Hao Liang; Jiudong Zhang; Qiang Chai; Weidong Cao (Science of The Total Environment, 2024)

Ancient genomic time transect unravels the population dynamics of Neolithic middle Yellow River farmers - Shiwei Li; Rui Wang; Hao Ma; Zheng Tu; Limin Qiu; Haodong Chen; Li Jiang; Yuezu Geng; Hai Liu; Jifeng Wang; Qu Shen; Li Jin; et al. (Science Bulletin, 2024)

Carbon capture, utilization and storage (CCUS) in oil and gas reservoirs in China: Status, opportunities and challenges - Bin Liang; Chong Chen; Chunsheng Jia; Chenhui Wang; Xiangzeng Wang; Yuqiang Zha; Rui Wang; Zhan Meng; Hao Wang (Fuel, 2024)

bcIRF5 activates bcTBK1 phosphorylation to enhance PANoptosis during GCRV infection - Can Yang; Jinwei Gao; Hao Wu; Zhenzhen Xiong; Jun Xiao; Yanfang Wu; Qing Yang; Zhonggui Xie; Rui Song; Dongsheng Ou; Hao Feng (Fish & Shellfish Immunology, 2024)

Effects of 12-year cropping systems and tillage practices on crop yield and carbon trade-off in dryland Loess Plateau - Xingyu Guo; Hao Wang; Naeem Ahmad; Rui Wang; Xiaoli Wang; Jun Li (Field Crops Research, 2024)

Dynamics of impure CO2 and composite oil in mineral nanopores: Implications for shale oil recovery and gas storage performance - Lu Wang; Run Zou; Yifan Yuan; Yifan Zhang; Rui Zou; Liang Huang; Yisheng Liu; Zhan Meng; Hao Chen (Chemical Engineering Journal, 2024)

Delaying cyclization of polyacrylonitrile by boric acid for sulfurized poly(acrylonitrile) cathode materials - Xuan Zhang; Hui-Chao Lu; Chen-Ran Hao; Ji-Qiong Liu; Xi-Rui Kong; Jiu-Lin Wang (Chemical Engineering Journal, 2024)

Perovskite nanocrystals photo-initiated in situ encapsulation for optical tracking - Xiao’e Jia; Tongyu Shi; Qingyuan Zhang; Hao Huang; Paul K. Chu; Xue-Feng Yu; Rui He (Chemical Engineering Journal, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

External ligand-free nickel-catalyzed synthesis of polypyrazines towards stable, high-capacity and low-potential sodium ion storage - Zhihui Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Xinyu Wang; HaiPing Yu; Yuxin Hao; Yujie Dai; Huige Ma; Mengxiao Li; Hongwei Li; Mingsheng Yang; et al. (Chemical Engineering Journal, 2024)

Association of the COL4A2 Gene Polymorphisms with Primary Intracerebral Hemorrhage Risk and Outcome in Chinese Han Population - Huan Wang; Yuyi Zhu; Lukai Zheng; Mingxi Chen; Zilong Hao; Rui Guo; Ling Feng; Deren Wang (Molecular Neurobiology, 2024)

Use of Environmental DNA to Evaluate the Spatial Distribution of False Kelpfish (Sebastiscus marmoratus) in Nearshore Areas of Gouqi Island - Rijin Jiang; Huibo Hao; Rui Yin; Peng Zhao; Feng Chen; Yongdong Zhou; Xuejun Chai (Fishes, 2024)
This study aims to explore the spatial distribution of false kelpfish (Sebastiscus marmoratus) in the mussel farming area, artificial reef areas of Gouqi Island (Shengsi, China), and natural areas using eDNA detection methods. Surface and bottom water samples were collected at 12 stations in November 2022 and April 2023, totaling 52 samples. We used species-specific primers and probes for quantitative PCR (qPCR) detection of Sebastiscus marmoratus eDNA. The eDNA concentrations differed seasonally (p 0.05) among the three sampling areas and two water layers. The greatest eDNA concentrations occurred in the surface layer during the spring. Higher concentrations of Sebastiscus marmoratus eDNA were also found in the mussel aquaculture area. Temperature exhibited a significant positive correlation with Sebastiscus marmoratus eDNA concentration (p

Deltamethrin increased susceptibility to Aeromonas hydrophila in crucian carp through compromising gill barrier - Xiping Yuan; Hao Wu; Jinwei Gao; Can Yang; Zhenzhen Xiong; Jiayu Wu; Chongrui Wang; Dong Liu; Jianzhong Shen; Rui Song (Chemosphere, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Assessing the role of urban green infrastructure in mitigating summertime Urban Heat Island (UHI) effect in metropolitan Shanghai, China - Hao Zhang; Meng-yuan Kang; Zhen-ru Guan; Rui Zhou; Ai-lian Zhao; Wen-jia Wu; Hao-rong Yang (Sustainable Cities and Society, 2024)

Long-term escape behavior and release mechanism of organic emissions from asphalt materials - Rui Zhang; Naipeng Tang; Hongzhou Zhu; Yuan Xi; Rui Li; Gengren Hao (Science of The Total Environment, 2024)

Numerical study on the hydrodynamic performance of a high-speed taxiing fuselage: Investigation on the affecting factors in the numerical simulation - Rui Deng; Hang Ren; Hao Li; Sichong Huang; Tiecheng Wu (Ocean Engineering, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

Enhancing soil gross nitrogen transformation through regulation of microbial nitrogen-cycling genes by biodegradable microplastics - Hao Zhang; Wei Zhu; Jinbo Zhang; Christoph Müller; Lifen Wang; Rui Jiang (Journal of Hazardous Materials, 2024)

Migration mechanism of atrazine in the simulated lake icing process at different freezing temperatures based on density function theory - Yan Zhang; Hao Lin; Aixin Yu; Xiaozhuang Wang; Yucan Liu; Tongshuai Liu; Chen Zhao; Rui Mei (Journal of Environmental Sciences, 2024)

Shrinking and upward shifting of siberian Jerboa's suitable habitat in China under climate change impacts - Ruixun Gan; Limin Hua; Tao Yu; Zhuangsheng Tang; Xincheng Cai; Rui Dong; Longming Dong; Daerhan Bao; Bin Chu; Yuanyuan Hao (Journal of Arid Environments, 2024)

Enhanced oxidative stability and quality of chilled mirror carp fillet using an antioxidant film of chitosan/clove essential oil nanoemulsion - Ying Li; Litong Rui; Hao Zhang; Xiufang Xia (Food Bioscience, 2024)

Quantitative evaluation method for post-earthquake functionality loss of pedestrian flow pathways within a complex building using evacuation and rescue simulation - Zhao-Long Shi; Zhi-Qian Dong; Gang Li; Ding-Hao Yu; Han Zhang; Rui Wang (Engineering Structures, 2024)

Computational engine for finite element digital twins of structural dynamics via motion data - Youqi Zhang; Rui Hao; Jarkko Niiranen; Yaohua Yang; Eugen Brühwiler; Di Su; Tomonori Nagayama (Engineering Structures, 2024)

Monitoring crack opening via seismic velocity variation to assess that fatal effect of precipitation for landslide motion - Zhiqiang Liu; Chuntao Liang; Christoph Sens-Schönfelder; Wei Hu; Xinlei Sun; Tuo Zhang; Rui Xu; Zhiyu Jiang; Hao Jiang (Earth and Planetary Science Letters, 2024)

Extracellular vesicles in pulmonary infection: From pathophysiology to theranostic technologies - Xu Wang; Mai-Qing Shi; Yang Wang; Hao Zhou; Ke Peng; Jun Wang; Shi-Kun Sun; Xu-Rui Shen; Jia-Jia Wang; Zhi Zhao; Xian-Guang Ding; Fu-Hai Ji (Chemical Engineering Journal, 2024)

Novel catalytic membrane based on γ-FeOOH@PVDF/peroxymonosulfate for efficient ammonia recovery: Self-cleaning mechanism and emerging organic contaminant degradation performance - Wucheng Ma; Chenfei Liu; Liang Zhu; Rui Han; Wei Zhang; Hao Zhang; Linting Zhao; Shi Wang; Lin Chen; Yiping Li (Chemical Engineering Journal, 2024)

Strong absorption of silica over full solar spectrum boosted by interfacial junctions and light–heat–storage of Mg(OH)2–(CrOx–SiO2) - Rui-Min Hao; Lin Zhu; Teng-Fei Shang; Zhi-Bin Xu; Qin-Pei Wu (Chemical Engineering Journal, 2024)

Suppression the glucose-induced ferroptosis in endothelial cells by 4OI-loading exosomes hydrogel for the treatment of diabetic foot ulcer - Kuo Shen; Rui Zheng; Bangrui Yu; Hao Zhang; Peng Wang; Peng Zhao; Jijun Chen; Yixuan Yuan; Yuhang Wang; Kejia Wang; Yanhui Jia; Ruizhi Wang; et al. (Chemical Engineering Journal, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

High-altitude exposure leads to increased modularity of brain functional network with the increased occupation of attention resources in early processing of visual working memory - Jing Zhou; Nian-Nian Wang; Xiao-Yan Huang; Rui Su; Hao Li; Hai-Lin Ma; Ming Liu; De-Long Zhang (Cognitive Neurodynamics, 2024)

Co-incorporation of wheat straw and hairy vetch reduced soil N2O emission via regulating nitrifier and denitrifier structure on the Qinghai plateau - Rui Liu; Peng Jiang; Guopeng Zhou; Danna Chang; Hao Liang; Qiang Chai; Weidong Cao (Applied Soil Ecology, 2024)

Digital twin-driven safety management and decision support approach for port operations and logistics - Kan Wang; Hang Xu; Hao Wang; Rui Qiu; Qianqian Hu; Xiaolei Liu (Frontiers in Marine Science, 2024)
Ports are of great significance in processing cargo containers and facilitating global marine logistics. Nevertheless, the susceptibility of the container shipping network for hazardous cargo is likely to intensify in the event of a significant disruption at a major port, such as adverse weather conditions, inadequate management practices, or unforeseen catastrophes. Such situations require the deployment of port protection emergency response and prevention in advance. This study proposes a digital twin (DT) model that employs extensive and trajectory data within containers to comprehensively analyze the occurrence of hazardous cargo failures within the port storage process. The virtual models of physical entities in the port are created through a data-driven approach, and the behavior of these entities in a port environment with big data is then simulated. A combination of a convolutional neural network (CNN) and a long short-term memory (LSTM) algorithm is employed to provide predictions for the service layer of the DT system. The predicted correlation coefficients of temperature and humidity in the container reach 0.9855 and 0.9181, respectively. The developed system driven by DT models integrated with a CNN and the LSTM algorithm can more effectively assist the safety manager in achieving prevention in port operations. This study enables marine authorities and decision-makers to optimize emergency procedures, thereby reducing the probability of accidents in port operations and logistics.

Polypod Carboxylic Acid-Rare Earth Complex with High Cyclic Stability for Nitrobenzene Compound Detection - Licong Chen; Rui Shi; Zhongzhi Wang; Xin Qiao; Pengcheng Hao; Wenyu Zhao (Journal of Fluorescence, 2024)

Activation technology of steel slag for concrete exposed to plateau climate: a state-of-the-art review - Wei Deng; Rui Xiong; Xinming Zhai; Kai Huang; Liding Li; Youjie Zong; Haoyu Wang; Jianliang Zhai; Hao Lai; Nan Mao; Changchun Shi; Fuyang Lu (Environmental Science and Pollution Research, 2024)

Transient response of semi-elliptical hill with an elliptical tunnel under blast and seismic loading - Hao Luo; Ming Tao; Zheng Yang; Rui Zhao; Chengqing Wu (Soil Dynamics and Earthquake Engineering, 2024)

A cost-effective approach to identify conservation priority for 30 × 30 biodiversity target on the premise of food security - Shuyu Hou; Rui Yang; Zhicong Zhao; Yue Cao; Tz-Hsuan Tseng; Fangyi Wang; Hao Wang; Pei Wang; Xiaoshan Wang; Le Yu (Science of The Total Environment, 2024)

A novel OsGST gene encoding 9glutathione reductase negatively regulates cadmium accumulation in rice - Rui Guo; Su Li; Yong Qiang Gao; Jia Tong He; Hao Yu Wang; Jin Chen; Jiu Huang; Ren Fang Shen; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

Amphibole fractionation as a key driver for oxidation of magmas in convergent margins - Chen-Hao Luo; Rui Wang; Oliver Nebel; Qi-Wei Li (Earth and Planetary Science Letters, 2024)

A multifunctional barium-modified geopolymer foam for the efficient and flexible treatment of high-sulfate coal mine drainage - Xuhao Zhang; Xiao Zhang; Minghui Ma; Rui Cheng; Chenglong Hao; Li Zhang; Jiaqi Zhang (Chemical Engineering Journal, 2024)

Cu-substituted Na0.75Ni0.17Cu0.08Mn0.75O2 cathode with suppressing P2-O2 phase transition and air-stable for high-performance sodium-ion batteries - Guodong Hao; Shao-hua Luo; Pengyu Li; Ge Wang; Wei Zhao; Rui Huang; Haoran Zang; Jiachen Wang; Lixiong Qian (Chemical Engineering Journal, 2024)

Wearable hydrogel-based health monitoring systems: A new paradigm for health monitoring? - Xintao Wang; Haixia Ji; Li Gao; Rui Hao; Ying Shi; Junyan Yang; Yuan Hao; Jiahui Chen (Chemical Engineering Journal, 2024)

Mutations in wheat TaAPA2 gene result in pleiotropic effects on plant architecture - Shengsheng Bai; Guiping Wang; Rui Song; Yanna Liu; Lei Hua; Jinwei Yang; Lijun Zhang; Shams ur Rehman; Xiaohua Hao; Lifeng Hou; Chaozhong Zhang; Hongna Li; et al. (Science China Life Sciences, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

Effect of surcharge width on evolution of soil arching for active and passive trapdoor - Rui-Xiao Zhang; Dong Su; Hao Xiong; Xing-Tao Lin (European Journal of Environmental and Civil Engineering, 2024)

MicroRNA-128-3p Affects Neuronal Apoptosis and Neurobehavior in Cerebral Palsy Rats by Targeting E3 Ubiquitin-Linking Enzyme Smurf2 and Regulating YY1 Expression - Xiaoqi Nie; Rui Cheng; Pengfei Hao; Yuhong Guo; Gang Chen; Lei Ji; Lu Jia (Molecular Neurobiology, 2024)

Improving effect of N-acetylcysteine on growth and intestinal health in juvenile Cyprinus carpio involve the Nrf2/MAPK/NF-κB pathways - Rui Zhu; Deng-Lai Li; Bao-Yuan Zhang; Liang Li; Guo-Jun Shang; Hao-Tong Wang; Zhi-Yong Yang; Xiao-fang Wei; Si-Tong Meng; Si-Ying Liu; Yin-Tao Wang; Li-Fang Wu; et al. (Aquaculture, 2024)

Karst carbon sink mechanism and its contribution to carbon neutralization under land- use management - Min Zhao; Dong Li; Zaihua Liu; Qian Bao; Fan Xia; Hao Yan; Bo Chen; Yundi Hu; Guanxia Cai; Rui Lang; Hang Li; Liangxing Shi; et al. (Science of The Total Environment, 2024)

Promotion and monitor wound healing by anthocyanin enhanced light curing ε-poly-l-lysine hydrogel encapsulated Cu-MOF - Xiawei Zhao; Rui Liu; Tiantian Tang; Zihao Liu; Xiaozhi Liu; Kai Yu; Ye Zhang; Hao Wang (Chemical Engineering Journal, 2024)

Positive temperature coefficient material based on silicone rubber/ paraffin/ graphite/ carbon nanotubes for wearable thermal management devices - Jian-Min Hao; Yin-Fa Yang; Yi-Tao Shen; Rui Zhou; Wei Zhang; Hua Chen; Wen-Long Cheng (Chemical Engineering Journal, 2024)

Environmentally relevant estrogens impaired spermatogenesis and sexual behaviors in male and female zebrafish - Mei-Ling Tan; Yan-Jun Shen; Qi-Liang Chen; Feng-Rui Wu; Zhi-Hao Liu (Aquatic Toxicology, 2024)

Nitrogen transformations in plastic-film mulched soils - Hao Zhang; Zihao Zhang; Zhe Liu; Tingting Lei; Jinbo Zhang; Christoph Müller; Abeer S. Aloufi; Ekaterina Filimonenko; Yakov Kuzyakov; Rui Jiang (Plant and Soil, 2024)

Identification of key genes involved in lignin and flavonoid accumulation during Tilia tuan seed maturation - Lei Liu; Cui Long; Xuri Hao; Rui Zhang; Chenqi Li; Yuepeng Song (Plant Cell Reports, 2024)

Ile-Pro-Pro attenuates sympathetic activity and hypertension - Jun-Liu Chen; Rui Ge; Xiu-Zhen Li; Yue Zhang; Wen-Yuan Hao; Na Li; Zhi-Qin Xu; Qi Chen; Yue-Hua Li; Guo-Qing Zhu; Xiao Tan (Journal of Physiology and Biochemistry, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Genetic affinity of cave burial and Hmong-Mien populations in Guangxi inferred from ancient genomes - Jianxin Guo; Haifeng He; Guangmao Xie; Le Tao; Xi Mai; Kongyang Zhu; Qiusheng Qin; Xiaomin Yang; Ying Xie; Rui Wang; Hao Ma; Jing Zhao; et al. (Archaeological and Anthropological Sciences, 2024)

Phylogenetic origin of an insect fauna at the boundary of the Palaearctic and Oriental realms: Evidence from ‘site‐based’ mitogenomics - Rui‐E Nie; Lu‐Lu Li; Anderson Feijó; Mei‐Xia Yang; Ming Bai; Thomas J. Creedy; Xu Jin; Jia‐Sheng Hao; Yong‐Ying Ruan; Hua‐Xi Liu; Beulah H. Garner; Ladislav Bocak; et al. (Journal of Biogeography, 2024)
Aim Knowledge of taxonomy and species distributions in highly diverse lineages of invertebrates remains too incomplete for the study of biogeographical patterns at the global scale. This limits the understanding of processes leading to the formation and maintenance of boundaries between major biogeographical realms. Site‐based metagenomic approaches may provide an alternative source of data for inference of historical processes of in situ speciation and interchange among biogeographical regions. We applied the methodology to explore the historical biogeography of the Qinling Mountains at the boundary of the Oriental and Palaearctic regions. Location The focal area in the Qinling Mountains; sites in Borneo, Panama, and Spain, representing the Oriental, Neotropical and Palaearctic faunas. Time Period Contemporary. Major Taxa Studied Chrysomelidae, a group of ~40,000 species with worldwide distribution. Methods Mass‐trapped insects were subjected to deep Illumina DNA sequencing and mitochondrial genome assembly, followed by phylogenetic analysis and historical biogeographical inference on a dated tree. The methodology produced 622 mitogenomes (304 newly sequenced) each representing a morphologically distinct species. Results Ancestral area reconstruction revealed that the Qinling fauna is a composite of distinct clades that, respectively, have Oriental or Palaearctic ancient origins, while in situ speciation and local clade formation were limited. The global diversity of Chrysomelidae consists of regionalised deep clades at the level of the major zoogeographic realms, which remain recognisable where these realms abut in the Qinling mountains. Yet, the Qinling fauna is clearly distinct from the source areas although local lineage ages are generally Main Conclusions The Qinling fauna is a composite of clades that have either Oriental or Palaearctic origin, indicating the important role of immigration at the realm boundary. Global site‐based phylogenetic analyses based on metagenomic sequencing can address previously intractable questions about the historical biogeography of poorly studied groups even without a fully developed taxonomy.

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

An ontology-driven method for urban building energy modeling - Rui Ma; Qi Li; Botao Zhang; Hao Huang; Chendi Yang (Sustainable Cities and Society, 2024)

Biodegradable film mulching increases soil microbial network complexity and decreases nitrogen-cycling gene abundance - Hao Zhang; Duntao Shu; Jiaqi Zhang; Xuejun Liu; Kai Wang; Rui Jiang (Science of The Total Environment, 2024)

The cellular response and molecular mechanism of superoxide dismutase interacting with superparamagnetic iron oxide nanoparticles - Hao Ju; Yue Liu; Yameng Wang; Rui Lu; Bin Yang; Deyi Wang; Jing Wang (NanoImpact, 2024)

Prediction and explanation of debris flow velocity based on multi-strategy fusion Stacking ensemble learning model - Tianlong Wang; Keying Zhang; Zhenghua Liu; Tianxing Ma; Rui Luo; Hao Chen; Xu Wang; Wei Ge; Hongyue Sun (Journal of Hydrology, 2024)

Destabilization of a model O/W/O double emulsion: From bulk to interface - Zijian Zhi; Hao Li; Indi Geurs; Benny Lewille; Rui Liu; Paul Van der Meeren; Koen Dewettinck; Filip van Bockstaele (Food Chemistry, 2024)

Fish skin mucosal surface becomes a barrier of antibiotic resistance genes under apramycin exposure - Wenpeng Li; Xiaohan Zhang; Xiaohan Hao; Rui Xin; Ying Zhang; Yongzheng Ma; Zhiguang Niu (Environmental Research, 2024)

Sea surface temperature prediction by stacked generalization ensemble of deep learning - Hao Dai; Famei Lei; Guomei Wei; Xining Zhang; Rui Lin; Weijie Zhang; Shaoping Shang (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Reindeer (Rangifer tarandus) hindlimb joint kinetics: propulsive and energy storage mechanisms and mechanical work - Guoyu Li; Rui Zhang; Hao Pang; Junfeng Wang; Dan Jin; Xumin Sun; Dianlei Han; Zhisong Li; Lige Wen (Polar Biology, 2024)

Optimizing Blasting Schemes: A Comprehensive Approach through Macro–Micro Simulation and Field Experiment - Yun-Juan Chen; Jia-Rui Su; Hao-Shuang Wang; Hou-Lei Xi; Dong Gao (Geotechnical and Geological Engineering, 2024)

In situ profiling reveals spatially metabolic injury in the initiation of polystyrene nanoplastic-derived intestinal epithelial injury in mice - Xianan Zhang; Jing Wang; Yuansheng Liu; Hemin Wang; Bin Li; Qing Li; Yi Wang; Yuru Zong; Jiajia Wang; Qingtao Meng; Shenshen Wu; Rongzhang Hao; et al. (Science of The Total Environment, 2024)

Feasibility of sulfated BPA and BPS as wastewater-based epidemiology biomarkers: Insights from wastewater and reported human urine analysis - Hao Wang; Rui Gao; Weiqian Liang; Yingyue Zhou; Zhuo Wang; Longxia Lan; Jinfeng Chen; Feng Zeng (Science of The Total Environment, 2024)

Heavy metals potentially drive co-selection of antibiotic resistance genes by shifting soil bacterial communities in paddy soils along the middle and lower Yangtze River - Ya ZHANG; Hao WANG; Minghui HU; Rui CAI; Yuqing MIAO; Xiancan ZHU (Pedosphere, 2024)

Large-scale soil application of hydrochar: Reducing its polycyclic aromatic hydrocarbon content and toxicity by heating - Hongyu Si; Rui Wang; Yuqing Zhao; Han Hao; Changkai Zhao; Sen Xing; Hewei Yu; Xiaohui Liang; JiKai Lu; Xiuxiu Chen; Bing Wang (Journal of Hazardous Materials, 2024)

Unraveling the impact of environmental provisions in preferential trade agreements on green total factor energy efficiency - Hao Yu; Rui Wang; Aiyu Zhang (Journal of Environmental Management, 2024)

Degradation of quinolone antibiotics by freeze activated periodate: effect of the number of fluorine substituents and DFT calculations - Hao Lin; Yan Zhang; Yucan Liu; Xiuping Sun; Bin Ji; Rui Mei; Tongshuai Liu; Zhonglu Gao; Xin Wang (Journal of Environmental Chemical Engineering, 2024)

Lotus pollen-derived nitrogen and phosphorus self-doped TiO2/carbon materials for photoelectrochemical application - Rui Chen; Ying-Ying Wang; Xia Jiang; Ming-Hao Ji; Ke-Xian Li; Hao-Yan Shi; Hai-Long Wang; Yan-Xin Chen; Can-Zhong Lu (Journal of Environmental Chemical Engineering, 2024)

MOF derived highly dispersed bimetallic Fe-Ni nitrogen-doped carbon for enhanced peroxymonosulfate activation and tetracycline degradation - Lingyun Jing; Shasha Liu; Tong Wang; Zeqiang Zhang; Xia Zhao; Zhili Sun; Pengbo Hao; Yeqiang Hu; Wenhan Yang; Rui Quan; Xinyong Li; Dongnian Zhang; et al. (Journal of Environmental Chemical Engineering, 2024)

Developing a combined rotating and air-circulating system for improving radio frequency heating uniformity and controlling Aspergillus in almond kernels - Rui Li; Yu Gao; Junjie Zheng; Mengge Li; Yujun Hao; Longlong Jiang; Shunqin Bai; Dingting Zhou; Juanjuan Xu; Xiaoxi Kou; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

Regulating the defects of MIL-101(Cr) for the efficient and simultaneous determination of eleven plant growth regulators in fresh fruit juice - Rui Cheng; Yiqun Wan; Xuejin Mao; Hao Wan; Fan Liu; Lan Guo; Bingzhen Zhang (Food Chemistry, 2024)

A randomised double-blind placebo-controlled trial of a probiotic combination for manipulating the gut microbiota and managing metabolic syndrome - Rui Xiao; Ying Chen; Xiaofeng Zhu; Linlin Wang; Peijun Tian; Xing Jin; Ming Liang; Zehua Chen; Ting Zhang; Long Qian; Qun Wang; Jianxin Zhao; et al. (Food Bioscience, 2024)

Annual burying of pelletized straw benefits grain amino acid by increasing soil mineral elements: A case study in Northeast China - Peixin Wang; Xiquan Wang; Rui Zong; Xinbo Wang; Haiping Ni; Lumin Liu; Yan Yang; Yubo Hao; Yiteng Zhang; Huancheng Pang; Chunrong Qian (Field Crops Research, 2024)

Study on the effect of NO2 impurity gas on the performance and local current density distribution of PEMFC - Rui Lin; Yuan Jing; Wenbo Dai; Shiyang Hua; Dengcheng Liu; Zhixian Hao (Chemical Engineering Journal, 2024)

Improved seed yield and phosphorus accumulation in soybean are associated with the enhanced root exudates in south-west China - Hong-Lan Zhang; Nian Liang; Rui Dong; Chang-An Liu; Chun-Ling Hao; Kadambot H. M. Siddique; Jin He (Plant and Soil, 2024)

Evaluating the fracture resistance and drainage difficulty of coal reservoirs using log data - Zhi-di Liu; Bin-rui Yang; Xiao-yan Tang; Wei Wang; Liang Ji; Zhi-hao Jiang (Applied Geophysics, 2024)

Calmodulin Gene of Blunt Snout Bream (Megalobrama amblycephala): Molecular Characterization and Differential Expression after Aeromonas hydrophila and Cadmium Challenges - Jinwei Gao; Hao Wu; Xing Tian; Jiayu Wu; Min Xie; Zhenzhen Xiong; Dongsheng Ou; Zhonggui Xie; Rui Song (Fishes, 2024)
Calmodulin (Calm), a crucial Ca2+ sensor, plays an important role in calcium-dependent signal transduction cascades. However, the expression and the relevance of Calm in stress and immune response have not been characterized in Megalobrama amblycephala. In this study, we identified the full-length cDNA of Calm (termed MaCalm) in blunt snout bream M. amblycephala, and analyzed MaCalm expression patterns in response to cadmium and Aeromonas hydrophila challenges. MaCalm was 1603 bp long, including a 5′-terminal untranslated region (UTR) of 97 bp, a 3′-terminal UTR of 1056 bp and an open reading frame (ORF) of 450 bp encoding a polypeptide of 149 amino acids with a calculated molecular weight (MW) of 16.84 kDa and an isoelectric point (pI) of 4.09. Usually, MaCalm contains four conservative EF hand motifs. The phylogenetic tree analysis indicated that the nucleotide sequence of MaCalm specifically clustered with Ctenopharyngodon idella with high identity (98.33%). Tissue distribution analysis demonstrated that the ubiquitous expression of MaCalm mRNA was found in all tested tissues, with the highest expression in the brain and the lowest expression in muscle. MaCalm showed significant upregulation at 14 d and 28 d post exposure to varying concentrations of cadmium in the liver; HSP70 transcripts in the liver significantly upregulated at 14 d post exposure to different concentrations of cadmium. Moreover, in response to the A. hydrophila challenge in vivo, MaCalm transcripts in the liver first increased and then decreased, but MaCalm transcripts in the kidney declined gradually with prolonged infection. After the A. hydrophila challenge, the expression level of HSP70 was significantly downregulated at 24 h in the liver and its expression level was notably downregulated at 12 h and at 24 h in the kidney. Collectively, our results suggest that MaCalm possesses vital roles in stress and immune response in M. amblycephala.

A newly defined latest Carboniferous-Permian ridge subduction in the southern Altaids: Insights from adakitic, S-type, and I-type granitoids in the northern East Junggar (NW China) - Jingmin Gan; Wenjiao Xiao; Qigui Mao; Hao Wang; He Yang; Miao Sang; Xiaoliang Jia; Yin Liu; Zhiyong Zhang; Zhou Tan; Rui Li (International Geology Review, 2024)

Effects of dietary bacterial culture of fengycin-producing Bacillus subtilis on growth performance, intestinal and hepatopancreas health, intestinal microbiota and disease resistance of common carp (Cyprinus carpio) - Rui Xia; Shenghui Li; Hongwei Yang; Yajie Zhao; Tsegay Teame; Qiang Hao; Mingxu Xie; Min Li; Qile Chen; Chunling Song; Chao Ran; Yalin Yang; et al. (Aquaculture, 2024)

A newly isolated strain of Bacillus subtilis W2Z exhibited probiotic effects on juvenile red claw crayfish, Cherax quadricarinatus - Ze-Long Zhang; Jia-Jun Li; Si-Wen Xing; Yao-Peng Lu; Pei-Hua Zheng; Jun-Tao Li; Chen-Guang Hao; Jia-Rui Xu; Jian-An Xian; Li-Min Zhang; Xiu-Xia Zhang (Aquaculture, 2024)

Advanced oxidation process/coagulation coupled with membrane distillation (AOP/Coag-MD) for efficient ammonia recovery: Elucidating biofouling control performance and mechanism - Wucheng Ma; Rui Han; Wei Zhang; Hao Zhang; Linting Zhao; Lin Chen; Liang Zhu (Journal of Hazardous Materials, 2024)

Synergistic effects of chemical additives and mature compost on reducing H2S emission during kitchen waste composting - Yongdi Liu; Haihou Wang; Hao Zhang; Yueyue Tao; Rui Chen; Sheng Hang; Xiaoyan Ding; Meidi Cheng; Guochun Ding; Yuquan Wei; Ting Xu; Ji Li (Journal of Environmental Sciences, 2024)

Temperature driven real-time weakening and strengthening mechanisms of unconfined granite - Fei Wang; Rui Pang; Heinz Konietzky; Ke Hu; Ben-Guo He; De-Hao Meng; Mohamed Ismael (Geothermics, 2024)

A novel MnCoOx@TiO2 double–wall nanocages derived from Prussian blue analogue for NH3-SCR of NOx - Tong Wu; Rui-tang Guo; Chu-fan Li; Yi-hao You; Wei-guo Pan (Fuel, 2024)

Effects of plastic film mulching on yield, water use efficiency, and nitrogen use efficiency of different crops in China: A meta-analysis - Tiantian Huang; Qianxiang Wu; Yangyang Yuan; Xintong Zhang; Ruiqi Sun; Rui Hao; Xiaohua Yang; Congfeng Li; Xiaoliang Qin; Fangqi Song; Charles O. Joseph; Wen Wang; et al. (Field Crops Research, 2024)

Maize cultivar mixtures increase aboveground biomass and grain quality via trait dissimilarity and plasticity - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (European Journal of Agronomy, 2024)

A Senescence-Associated Secretory Phenotype of Bone Marrow Mesenchymal Stem Cells Inhibits the Viability of Breast Cancer Cells - Meng Li; Jie-Xi Liu; Bo Ma; Jin-Yu Liu; Ji Chen; Fang Jin; Cheng-Hu Hu; Hao-Kun Xu; Chen-Xi Zheng; Rui Hou (Stem Cell Reviews and Reports, 2024)

Influence of building spatial patterns on wind environment and air pollution dispersion inside an industrial park based on CFD simulation - Qiang Zhao; Rui Li; Kaifa Cao; Mingjian Yi; Hao Liu (Environmental Monitoring and Assessment, 2024)

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

Preparation and application of biocontrol formulation of nematode-trapping fungus-Duddingtonia flagrans - Luyao Hao; Yuan Guo; Xiaomin Wang; Mingjuan Gao; Tonghai Liu; Yuan Ma; Yanni Zhang; Qiannan Li; Rui Wang; Xihuo You (Veterinary Parasitology, 2024)

Viologen-based ionic conjugated mesoporous polymer as the electron conveyer for efficient polysulfide trapping and conversion - Hai-Yang Li; Zhong-Shan Li; Gang-Hao Qiu; Rou-Rou Zhang; Ya-Rui Wang; Feng Wang; Ren-Wu Huang; Xiao-Fei Liu; Shuang-Quan Zang (Science Bulletin, 2024)

Oxygen-enriched vacancy spinel Mn-Co oxides by deep thermal reduction for enhanced antibiotics degradation efficiency - Xiai Zhang; Rui Zhou; Ruohong Bi; Tong Wang; Qikui Fan; Hao Zhu; Zhimao Yang; Xiaofei Liu; Chuncai Kong (Journal of Environmental Chemical Engineering, 2024)

Flexible phase change materials based on hexagonal boron nitride (hBN) surface modification and styrene-butadiene-styrene (SBS)/low-density polyethylene (LDPE) crosslinking for battery thermal management applications - Jun Zhao; Ziliang Rui; Zhiwei Hu; Zhen Shangguan; Shuai Yin; Hao Peng (Chemical Engineering Journal, 2024)

An organic acid-alkali coordinately regulated liquid electrolyte enables stable cycling of high-voltage proton battery - Huige Ma; Mingsheng Yang; Rui Li; Yan Wang; Liping Zheng; Xiaoming Jing; Yuxing Hao; Yujie Dai; Jiefeng Gao; Mingjun Hu; Jun Yang (Chemical Engineering Journal, 2024)

Enhancing copper recycling through synergistic valence conversions in MnOx-modified capacitive deionization electrodes - Lujie Nie; Lei Wang; Xudong Wang; Miaolu He; Jin Wang; Yongtao Lv; Rui Miao; jiajun An; Jiajin Hao; Jiaqi Wang; Yanna Ren (Chemical Engineering Journal, 2024)

Andesitic arc magmas derived from two contrasting mélange origins: Evidence from central Tibetan dioritic porphyries - Lu-Lu Hao; Qiang Wang; Andrew C. Kerr; Fang Huang; Ming Xiao; Xiao-Long Ma; Wan-Feng Zhang; Wen-Yu Wang; Mao-Rui Liu (Chemical Geology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

DAE-Mask: a novel deep-learning-based automatic detection model for in-field wheat diseases - Rui Mao; Yuchen Zhang; Zexi Wang; Xingan Hao; Tao Zhu; Shengchang Gao; Xiaoping Hu (Precision Agriculture, 2024)

Phenolic components from the fruits of Solanum xanthocarpum with anti-inflammatory activity - Yan Liu; Rui Yang; Hai-Dan Zou; Zhen-Peng Xu; Juan Pan; Jia-Tong Wu; Wei Guan; Zhi-Chao Hao; Adnan Mohammed Algradi; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2024)

The SIDT2/MDA5/IFN axis contributes to virus resistance in teleost fish - Yaoguo Li; Hao Tang; Mingxue Sun; Qiaolin Liu; Yijing Liao; Hong Luo; Rui Li; Ronghua Wang; Hong Yang; Hongquan Wang; Jun Zou; Tiaoyi Xiao (Aquaculture, 2024)

Weak correlations among leaf thermal metrics, economic traits and damages under natural heatwaves - Qiu-Rui Ning; Qiang Li; Hao-Ping Zhang; Yi Jin; Xue-Wei Gong; Rui-Fang Jiao; Emily Patience Bakpa; Han Zhao; Hui Liu (Science of The Total Environment, 2024)

Modulator of TMB-associated immune infiltration (MOTIF) predicts immunotherapy response and guides combination therapy - Zheng-Yu Qian; Yi-Qian Pan; Xue-Xin Li; Yan-Xing Chen; Hao-Xiang Wu; Ze-Xian Liu; Martin Kosar; Jiri Bartek; Zi-Xian Wang; Rui-Hua Xu (Science Bulletin, 2024)

Sesquiterpenoid derivatives isolated from a liquid culture of Hypholoma capnoides 819 - Yu-Ting Wang; Hong-Yu Tan; Xue Zhao; Yu Yang; Rui Xu; Shuai-Ming Zhu; Hao Ma; Fu-Yao Luo; Cai-Hong Dong; Chang-Wei Li (Phytochemistry, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

Towards energy conservation and carbon reduction for wastewater treatment processes: A review of carbon-neutral anaerobic biotechnologies - Xinzheng Zhang; Tianwei Hao; Tao Zhang; Yong Hu; Rui Lu; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Journal of Water Process Engineering, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

Engineering extracellular electron transfer to promote simultaneous brewing wastewater treatment and chromium reduction - Deguang Wu; Baocai Zhang; Sicheng Shi; Rui Tang; Chunxiao Qiao; Teng Li; Jichao Jia; Meiyi Yang; Xiaoguang Si; Yifei Wang; Xi Sun; Dongguang Xiao; et al. (Journal of Hazardous Materials, 2024)

Modeling nitrogen removal performance based on novel microbial activity indicators in WWTP by machine learning and biological interpretation - Yadan Yu; Hao Zeng; Liyun Wang; Rui Wang; Houzhen Zhou; Liang Zhong; Jun Zeng; Yangwu Chen; Zhouliang Tan (Journal of Environmental Management, 2024)

The pH adjustment of Vitis amurensis dry red wine revealed the evolution of organic acids, volatomics, and sensory quality during winemaking - Meng-Bo Tian; Rui-Qi Hu; Zhao-Long Liu; Ning Shi; Hao-Cheng Lu; Chang-Qing Duan; Jun Wang; Yan-Feng Sun; Qing-Sen Kong; Fei He (Food Chemistry, 2024)

Dual stabilization of O/W/O double emulsions by proteins: An interfacial perspective - Zijian Zhi; Hao Li; Indi Geurs; Benny Lewille; Rui Liu; Paul Van der Meeren; Koen Dewettinck; Filip van Bockstaele (Food Hydrocolloids, 2024)

Genetic lineage tracing identifies adaptive mechanisms of pancreatic islet β cells in various mouse models of diabetes with distinct age of initiation - Qi Fu; Yu Qian; Hemin Jiang; Yunqiang He; Hao Dai; Yang Chen; Zhiqing Xia; Yucheng Liang; Yuncai Zhou; Rui Gao; Shuai Zheng; Hui Lv; et al. (Science China Life Sciences, 2024)

Study and verification on an improved comprehensive prediction model of landslide displacement - Tianlong Wang; Rui Luo; Tianxing Ma; Hao Chen; Keying Zhang; Xu Wang; Zhaowei Chu; Hongyue Sun (Bulletin of Engineering Geology and the Environment, 2024)

Numerical study on uplift capacity and behavior of plate anchor considering different dilation angles - Yong-sheng Wang; Wei Ye; Hao Liu; Quanping Gao; Ji-xin Li; Rui-heng Ding; Rui Rui (Arabian Journal of Geosciences, 2024)

Cotton Verticillium wilt monitoring based on UAV multispectral-visible multi-source feature fusion - Rui Ma; Nannan Zhang; Xiao Zhang; Tiecheng Bai; Xintao Yuan; Hao Bao; Daidi He; Wujun Sun; Yong He (Computers and Electronics in Agriculture, 2024)

Investigation of the intrinsic characteristics of two lock-in regions in a 10:1 π-shaped deck - Jiaying Wang; Feng Wang; Rui He; Jiawu Li; Jianming Hao; Jiupeng Zhang; Xiaoming Huang (Ocean Engineering, 2024)

Agronomic performances of biodegradable and non-biodegradable plastic film mulching on a maize cropping system in the semi-arid Loess Plateau, China - Hao ZHANG; Mengqiong CHEN; Ruiquan QIAO; Fan DING; Hao FENG; Rui JIANG (Pedosphere, 2024)

Towards carbon-neutral biotechnologies for rural wastewater: A review of current treatment processes and future perspectives - Xinzheng Zhang; Guangyi Ma; Tao Chen; Churen Yan; Yiheng Chen; Qinye Wang; Xinyu Peng; Wenjie Xu; Tianwei Hao; Tao Zhang; Rui Lu; Dapeng Li; et al. (Journal of Water Process Engineering, 2024)

Improving on mapping long-term surface water with a novel framework based on the Landsat imagery series - Ling Lan; Yu-Ge Wang; Hao-Shuang Chen; Xu-Rui Gao; Xie-Kang Wang; Xu-Feng Yan (Journal of Environmental Management, 2024)

Magnetic biochar enhanced copper immobilization in agricultural lands: Insights from adsorption precipitation and redox - Wucheng Ma; Rui Han; Wei Zhang; Hao Zhang; Lin Chen; Liang Zhu (Journal of Environmental Management, 2024)

Nickel isotope fractionation during intense weathering of basalt: Implications for Ni output from continental weathering - Sheng-Sheng Sun; Teng-Hao-Bo Deng; Ming Ao; Wen-Jun Yang; Xiao-Rui Liu; Ting Liu; Jian-Ming Zhu; Jean Louis Morel; Ye-Tao Tang; Rong-Liang Qiu (Geochimica et Cosmochimica Acta, 2024)

The promotion effect of Pr doping on the catalytic performance of MnCeOx catalysts for low-temperature NH3-SCR - Tong Wu; Shan Ren; Rui-tang Guo; Chu-fan Li; Yi-hao You; Shi-yi Guo; Wei-guo Pan (Fuel, 2024)

Production of carbon nanotubes via catalytic pyrolysis of polyethylene over Ni/ZSM-5 prepared by ethylene glycol assisted impregnation - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Tao-li Huhe; Hao-Ran Yuan; Yong Chen (Fuel, 2024)

Complexities of regulating climate by promoting marine primary production with ocean iron fertilization - Hai-Bo Jiang; David A. Hutchins; Hao-Ran Zhang; Yuan-Yuan Feng; Rui-Feng Zhang; Wei-Wei Sun; Wentao Ma; Yan Bai; Mark Wells; Ding He; Nianzhi Jiao; Yuntao Wang; et al. (Earth-Science Reviews, 2024)

Superfast hydrous-molten salt erosion to fabricate large-size self-supported electrodes for industrial-level current OER - Jie Deng; Zhichao Wang; Hao Yang; Rui Jian; Yufeng Zhang; Ping Xia; Wei Liu; Olivier Fontaine; Yachao Zhu; Luming Li; Si Chen (Chemical Engineering Journal, 2024)

Functionalized Sr2MgSi2O7:(Eu,Dy)@CdS heterojunction photocatalyst for round-the-clock hydrogen production - Jing Wang; Runhui Pan; Zijie Yuan; Qi Hao; Xingyu Niu; Rui Wang; Jilei Ye; Hui Ying Yang; Yuping Wu (Chemical Engineering Journal, 2024)

The Community of Arbuscular Mycorrhizal Fungi in Sugarcane Rhizosphere Soils in Guangxi, China - Jin-Lian Zhang; Juan Song; Yi-Hao Kang; Yun-Ying Wen; Ying-Jie Nong; Qian Wang; Xiao-Juan Qin; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Potential protective effects of sodium butyrate on glycinin-induced oxidative stress, inflammatory response, and growth inhibition in Cyprinus carpio - Deng-Lai Li; Si-Ying Liu; Rui Zhu; Si-Tong Meng; Yin-Tao Wang; Zhi-Yong Yang; Liang Li; Xiao-Fang Wei; Guo-Jun Shang; Hao-Tong Wang; Zi-Hui Qu; Ya-Nan Quan; et al. (Fish Physiology and Biochemistry, 2024)

Risk assessment and source identification of soil heavy metals: a case study of farmland soil along a river in the southeast of a mining area in Southwest China - Huajian Chi; Xin Liu; Xiaofang Yang; Rui Zhang; Ting Xia; Yiping Sun; Kan Hu; Fangfang Hao; Yong Liu; Shengchun Yang; Qingwen Deng; Xiaodong Wen (Environmental Geochemistry and Health, 2024)

GABRP Promotes the Metastasis of Pancreatic Cancer by Activation of the MEK/ERK Signaling Pathway - Yong Meng; Rui Li; Shuaiming Geng; Wenhao Chen; Weirong Jiang; Zhiwen Li; Ji Hao; Zhen Xu (Biochemical Genetics, 2024)

Boron removal in seawater desalination by progressive freezing-melting - Rui Mei; Tongguo Zhao; Yan Zhang; Hao Lin; Chen Zhao; Lin Lin; Yihong Zou; Yucan Liu (Environmental Science and Pollution Research, 2024)

Diversified cropping systems with complementary root growth strategies improve crop adaptation to and remediation of hostile soils - Wei-Ping Zhang; Surigaoge Surigaoge; Hao Yang; Rui-Peng Yu; Jin-Pu Wu; Yi Xing; Yinglong Chen; Long Li (Plant and Soil, 2024)

Emission characteristics, environmental impact, and health risk assessment of volatile organic compounds (VOCs) during manicure processes - Run Hao; Jianling Sun; Rui Liu; Huan Zhao; Zhen Yao; Hailin Wang; Zhengping Hao (Science of The Total Environment, 2024)

The Sailajiazitage volcanic and related rocks in the Tiekelik belt imply a Neoproterozoic seamount accreted to the southern Tarim Craton - Rui Li; Wenjiao Xiao; Qigui Mao; Hao Wang; Miao Sang; Zhou Tan; Songjian Ao; Dongfang Song (Lithos, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

Effects of UHPC shear key on strengthening shear performances of wet joint in prefabricated composite beams - Hao Wang; Ning Wang; Xiao-gang Liu; Qing-rui Yue; Jing-liang Yan; Yu Zhang (Engineering Structures, 2024)

Exosome as non-invasive prognostic and diagnostic biomarker and nanovesicle for targeted therapy of non-small cell lung carcinoma - Zhao Yang; Shi Fu; Yongchao Li; Youfeng Liang; Mingxuan Hao; Rui Guo; Changyuan Yu; Zahid Hussain; Jinku Zhang; Haifeng Wang (Chemical Engineering Journal, 2024)

Facile synthesis of bead-chain structured MWCNTs@CeO2 with oxygen vacancies-rich for promoting electrochemical energy storage - Xiao-Man Cao; Jia-Qi Chen; Xin-Rui Zhao; Hao Ge; Daliang Liu; Qiong Wu; Zhi-Jia Sun; Qingguo Zhang (Chemical Engineering Journal, 2024)

Lipopolysaccharides from a Shiraia fruiting body-associated bacterium elicit host fungal hypocrellin A biosynthesis through nitric oxide generation - Xin Ping Li; Wen Hao Shen; Lu Lu Zhou; Qun Yan Huang; Rui Peng Cong; Li Ping Zheng; Jian Wen Wang (Carbohydrate Polymers, 2024)

Thymol incorporation within chitosan/polyethylene oxide nanofibers by concurrent coaxial electrospinning and in-situ crosslinking from core-out for active antibacterial packaging - Zhaozhang Zhu; Mengjia Yu; Rui Ren; Hao Wang; Baohua Kong (Carbohydrate Polymers, 2024)

Sub-Himalayan Mesozoic-Cenozoic tectonic-stratigraphic properties and deformation features in the western limb of Hazara Kashmir syntaxis, Pakistan - Irshad Hussain; Zuo-Chen Li; Misbah Fida; Jabir Hussain; Wakeel Hussain; Xian-Zhi Pei; Ya-Jie Yang; Meng Wang; Rui-Bao Li; Lei Pei; Hao Lin (Arabian Journal of Geosciences, 2024)

A chitosan-based antibacterial hydrogel with injectable and self-healing capabilities - Rui Chen; Yanan Hao; Secundo Francesco; Xiangzhao Mao; Wen-Can Huang (Marine Life Science & Technology, 2023)
The presence of bacteria directly affects wound healing. Chitosan-based hydrogel biomaterials are a solution as they offer advantages for wound-healing applications due to their strong antimicrobial properties. Here, a double-cross-linking chitosan-based hydrogel with antibacterial, self-healing, and injectable properties is reported. Thiolated chitosan was successfully prepared, and the thiolated chitosan molecules were cross-linked by Ag–S coordination to form a supramolecular hydrogel. Subsequently, the amine groups in the thiolated chitosan covalently cross-linked with genipin to further promote hydrogel formation. In vitro experimental results indicate that hydrogel can release Ag + over an extended time, achieving an antibacterial rate of over 99% against Escherichia coli and Staphylococcus aureus . Due to the reversible and dynamic feature of Ag–S coordination, an antibacterial hydrogel exhibited injectable and self-healing capabilities. Additionally, the hydrogel showed excellent biocompatibility and biodegradability.

Native ApxIIA secreted by Actinobacillus pleuropneumoniae induces apoptosis in porcine alveolar macrophages dependent on concentration and acylation - Hao Tang; Rong Wang; Siqi Pang; Weiyao Han; Qiuhong Zhang; Qiong Fang; Xiabing Chen; Qi Huang; Dexin Qiu; Rui Zhou; Lu Li (Veterinary Microbiology, 2023)

Carbon-neutral potential in treatment of N, N-dimethylformamide-containing industrial wastewater: Comparative investigation of energy conservation, carbon reduction and expenditure between UASB and Fenton process - Xinwei Tan; Yuqin Fan; Xinzheng Zhang; Tianwei Hao; Rong Chen; Tao Zhang; Rui Lu; Jianliang Sun; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Journal of Water Process Engineering, 2023)

A bioinspired hydrogel carrier with pH/redox dual responsiveness for effective protection and intestinal targeted delivery of probiotics - Yanan Hao; Mengyuan Zhou; Rui Chen; Xiangzhao Mao; Wen-Can Huang (Journal of Food Engineering, 2023)

Exploring the relation between aggregation and adsorption of microplastics in aquatic environment containing metal cations - Weiqian Liang; Yingyue Zhou; Shuyin Wei; Longxia Lan; Jinfeng Chen; Jiawei Zhao; Hao Wang; Rui Gao; Feng Zeng (Journal of Environmental Chemical Engineering, 2023)

Mitigating abortion risk of synthetic musk-contained body wash in pregnant women: Risk assessment and mechanism analysis - Xixi Li; Rui Li; Yong Niu; Meijin Du; Hao Yang; Di Liu (Environmental Pollution, 2023)

Soil arching in ground with tunnel: Effect of distance between tunnel and trapdoor - Rui-Xiao Zhang; Dong Su; Xing-Tao Lin; Hao Xiong; Xiang-Sheng Chen (Computers and Geotechnics, 2023)

Calibration of the carbonate clumped isotope thermometer of land snail shells - Rui Bao; Xuefen Sheng; Chenglong Li; Can Cui; Hao Yan; Junfeng Ji; Jun Chen (Chemical Geology, 2023)

Bamboo polysaccharides elicit hypocrellin A biosynthesis of a bambusicolous fungus Shiraia sp. S9 - Wen Hao Shen; Lu Lu Zhou; Xin Ping Li; Rui Peng Cong; Qun Yan Huang; Li Ping Zheng; Jian Wen Wang (World Journal of Microbiology and Biotechnology, 2023)

Effects of Mixed Cropping on Sugarcane Growth and the Community of Arbuscular Mycorrhizal Fungi - Ying-Jie Nong; Qian Wang; Juan Song; Jin-Lian Zhang; Xiao-Juan Qin; Yi-Hao Kang; Xiang-Hua Wei; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2023)

Low-dose IL-2 Treatment Rescues Cognitive Deficits by Repairing the Imbalance Between Treg and Th17 Cells at the Middle Alzheimer’s Disease Stage - Lin Yuan; Lei Xie; Hao Zhang; Yu Zhang; Yunbo Wei; Jinhong Feng; Li Cui; Rui Tian; Jia Feng; Di Yu; Cui Lv (Journal of Neuroimmune Pharmacology, 2023)

Genome resequencing reveals the population structure and genetic diversity of almond in Xinjiang, China - Pengyu Wu; Dong Li; Rui Zhuang; Hao Zuo; Zhiyong Pan; Bo Yang; Chongzhi Xu (Genetic Resources and Crop Evolution, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

The development of ecological civilization in China based on the economic–social–natural complex system - Rui Xiao; Haiguang Hao; Huiyuan Zhang; Yujie Liu; Mengxiao Liu (Ambio, 2023)

Reversing seasonality of Southern Hemisphere Annular Mode trend in the 21st century - Fei Zheng; Xiaoning Liu; Hao Wang; Yuxun Li; Rui Wang; Shuailei Yao; Wenjie Dong (International Journal of Climatology, 2023)
The Southern Hemisphere Annular Mode (SAM) is the dominant mode of atmospheric circulation in the Southern Hemisphere extratropical region. In the late 20th century, the SAM underwent a remarkable positive trend, with the strongest trend occurring in austral summer because of Antarctic ozone depletion. In this study, we quantitatively explore changes in the seasonality of the SAM trend under the background of ozone recovery. As expected, accompanied by ozone recovery since 2001, the summer SAM trend has decreased, thus reducing the seasonal difference in the SAM trend between summer and winter. However, what was not expected and found in this study is that the winter SAM has meanwhile shown an increasing positive trend in the early 21st century, which further reverses the seasonality of the SAM trend, leading to a stronger trend in winter rather than summer, which is different from the seasonality in the late 20th century. The reason underlying the winter SAM changes is explored from the perspective of natural variability. Winter SAM exhibits clear multidecadal variability, and the recent increasing trend is a part of multidecadal oscillation. The multidecadal variability of winter SAM may partly originate from the Atlantic Multidecadal Oscillation. The seasonality of linear trend in extratropical surface climate also exhibits reversing characteristics since 2001. In the early 21st century, the acceleration of westerlies and the strengthening of Amundsen Sea Low are stronger in winter, reversing the previous seasonality in the late 20th century, in which the acceleration of westerlies and the strengthening of Amundsen Sea Low is stronger in summer.

The predictive, preventive, and personalized medicine of insomnia: gut microbiota and inflammation - Hao-Wen Chen; Rui Zhou; Bi-Fei Cao; Kuan Liu; Qi Zhong; Yi-Ning Huang; Hua-Min Liu; Jin-Qing Zhao; Xian-Bo Wu (EPMA Journal, 2023)

Aluminum soap nanoparticles-lignin powder form phase-selective gelator as an efficient sorbent for oils/water separation - Suwan Cui; Bohao Qi; Hao Liu; Xiaojun Sun; Rui He; Junshuai Lian; Yiming Li; Jinren Lu; Mutai Bao (Chemosphere, 2023)

Recombinant Klotho alleviates vancomycin-induced acute kidney injury by upregulating anti-oxidative capacity via JAK2/STAT3/GPx3 axis - MengMeng Wang; Yue Zhou; GuoXiang Hao; Yue E. Wu; Rui Yin; Yi Zheng; Wei Zhao (Toxicology, 2023)

The formins inhibitor SMIFH2 inhibits the cytoskeleton dynamics and mitochondrial function during goat oocyte maturation - Meng-Hao Pan; Rui Xu; Zhi Zheng; Jinfeng Xiong; Haiying Dong; Qiang Wei; Baohua Ma (Theriogenology, 2023)

Thermokarst lake susceptibility assessment using machine learning models in permafrost landscapes of the Arctic - Rui Wang; Lanlan Guo; Yuting Yang; Hao Zheng; Hong Jia; Baijian Diao; Hang Li; Jifu Liu (Science of The Total Environment, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

DEMRL: Dynamic estimation meta reinforcement learning for path following on unseen unmanned surface vehicle - Kefan Jin; Hao Zhu; Rui Gao; Jian Wang; Hongdong Wang; Hong Yi; C.-J. Richard Shi (Ocean Engineering, 2023)

TBtools-II: A “one for all, all for one” bioinformatics platform for biological big-data mining - Chengjie Chen; Ya Wu; Jiawei Li; Xiao Wang; Zaohai Zeng; Jing Xu; Yuanlong Liu; Junting Feng; Hao Chen; Yehua He; Rui Xia (Molecular Plant, 2023)

Widely targeted metabolomics provides insights into the effect of parboiling treatment on the nutritional quality of black rice based on its improved cooking characteristics - Xin Wu; Xingxing Zhang; Min Liu; Tang Tang; Yanhua Li; Hao Chen; Qun Lu; Rui Liu (Journal of Cereal Science, 2023)

On sediment incipient motion of marine cohesive sediments with different bulk densities - Shouqian Li; Mingcheng Zhu; Wei Huang; Hao Zhu; Rui Zhang; Yongjun Lu (Geomorphology, 2023)

Reducing airborne transmission of SARS-CoV-2 by an upper-room ultraviolet germicidal irradiation system in a hospital isolation environment - Haiyang Liu; Zhijian Liu; Junzhou He; Chenxing Hu; Rui Rong; Hao Han; Lingyun Wang; Desheng Wang (Environmental Research, 2023)

Integrative risk assessment method via combining geostatistical analysis, random forest, and receptor models for potentially toxic elements in selenium-rich soil - Hao Wu; Nan Cheng; Ping Chen; Fei Zhou; Yao Fan; Mingxing Qi; Jingyi Shi; Zhimin Zhang; Rui Ren; Cheng Wang; Dongli Liang (Environmental Pollution, 2023)

Peroxymonosulfate enhanced Fe(III) coagulation coupled with membrane distillation for ammonia recovery: Membrane fouling control process and mechanism - Wucheng Ma; Rui Han; Liang Zhu; Wei Zhang; Hao Zhang; Longjie Jiang; Lin Chen (Desalination, 2023)

DEM study on evolution of soil arching in a deep trapdoor in seismic shaking conditions - Rui-Xiao Zhang; Dong Su; Hao Xiong; Xing-Tao Lin; Yuan-Jun Jiang; Xiang-Sheng Chen (Computers and Geotechnics, 2023)

Significantly improved high-temperature capacitive performance in polymer dielectrics utilizing ultra-small carbon quantum dots with Coulomb-blockade effect - Hangchuan Cai; Rui Wang; Bin Gou; Jing Fu; Yujie Zhu; Hao Yang; Jiangang Zhou; Manxi Li; An Zhong; Daoming Zhang; Huasong Xu; Chunhui Bi; et al. (Chemical Engineering Journal, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Demethylation-Driven ligase chain reaction for simultaneously sensitive detection of m6A demethylase FTO and m1A demethylase ALKBH3 in breast cancer at Single-Molecule level - Ming-hao Liu; Qian Zhang; Wan-tong Yu; Jian-Ge Qiu; Hui-min Yuan; Chuan-rui Wang; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Chemical Engineering Journal, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Multi-layer feature fusion for hyperspectral image classification - Siyuan Hao; Rui Li; Min Zhang; Yuanxin Ye (International Journal of Remote Sensing, 2023)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

Ordovician to Triassic episodic growth of the Dananhu arc, Eastern Tianshan (NW China) - Qigui Mao; Wenjiao Xiao; Songjian Ao; Brian F. Windley; Dongfang Song; Miao Sang; Zhou Tan; Hao Wang; Rui Li (International Geology Review, 2023)

Large-scale biomonitoring of bisphenol analogues and their metabolites in human urine from Guangzhou, China: Implications for health risk assessment - Hao Wang; Rui Gao; Weiqian Liang; Shuyin Wei; Yingyue Zhou; Zhuo Wang; Longxia Lan; Jinfeng Chen; Feng Zeng (Chemosphere, 2023)

Dietary acetate promotes growth and nutrients deposition in Nile tilapia (Oreochromis niloticus) through increasing acetyl-CoA-triggered energy production - Wen-Hao Zhou; Samwel M. Limbu; Yuan Luo; Rui-Xin Li; Jiong Ren; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Aquaculture, 2023)

Microplastics affect soil bacterial community assembly more by their shapes rather than the concentrations - Peng-Yang Wang; Ze-Ying Zhao; Xiao-Bin Xiong; Ning Wang; Rui Zhou; Zhi-Ming Zhang; Fan Ding; Meng Hao; Song Wang; Yue Ma; Aimee Grace Uzamurera; Kai-Wen Xiao; et al. (Water Research, 2023)

Soil phosphorus availability mediates facilitation dynamic in maize-grass pea intercropping system - Shuang-Guo Zhu; Wesly Kiprotich; Zheng-Guo Cheng; Rui Zhou; Jing-Wei Fan; Hao Zhu; Wen-Ying Wang; Wei Wang; Ren-Qing Wang; Hong-Yan Tao; You-Cai Xiong (Soil and Tillage Research, 2023)

Dynamic simulation and control strategy exploration of the unsafe behavior of coal mine employees - Wanzhen Li; Lujie Zhou; Jian Hao; Kai Yu; Jing Chen; Pingping Liu; Rui Feng (Resources Policy, 2023)

Energy optimal depth control for multimodal underwater vehicles with a high accuracy buoyancy actuated system - Junjun Cao; Rui Lin; Chunhu Liu; Hao Feng; Caoyang Yu; Baoheng Yao; Lian Lian (Ocean Engineering, 2023)

Enhanced nitrogen removal in a pilot-scale AOA-SBFASR system treating municipal wastewater: Process efficiency, microbial community and nitrogen metabolic pathways - Zhi-li Du; Shao-bin Huang; Rui-jian Zhang; Yong-qing Zhang; Hao-tao Dong; Guang-hua Wang; Zhi-min Sun (Journal of Water Process Engineering, 2023)

Effects of multi-frequency ultrasound on inactivating Chironomus kiiensis eggs: Evidence from a case study in drinking water treatment plant - Hai-guang Yuan; Rui-jian Zhang; Ye-qin Xu; Zhi Dang; Yong Hu; Qian-Bin Wang; Hao-tao Dong; Jia-xin Liu; Shu-juan Pu; Zhi-li Du; Ying-shi Liu; Zong-jia Zhang (Journal of Water Process Engineering, 2023)

Melt-blown fiber felt for efficient all-weather recovery of viscous oil spills by Joule heating and photothermal effect - Bohao Qi; Nuo Wang; Xin Hu; Suwan Cui; Hao Liu; Rui He; Junshuai Lian; Yiming Li; Jinren Lu; Yang Li; Mutai Bao (Journal of Hazardous Materials, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Sustainable production of eco-friendly rubberized asphalt binders through chemically crosslinking with polymer modifier - Naipeng Tang; Chenyang Xue; Gengren Hao; Weidong Huang; Hongzhou Zhu; Rui Li (Journal of Cleaner Production, 2023)

Multiple stages of Au mobilization in the Changshagou Au deposit, Eastern Tianshan, NW China: Insights from mineral chemistry and fluid inclusions - Yi-Hao Liu; Yun Zhao; Chun-Ji Xue; Rui Wang; Hai-Xia Chu; Xiao-Bo Zhao; Matthew J. Brzozowski; Reimar Seltmann; Jun Chen; Jun-Bao Gao (Journal of Asian Earth Sciences, 2023)

A spectral-temporal constrained deep learning method for tree species mapping of plantation forests using time series Sentinel-2 imagery - Zehua Huang; Liheng Zhong; Feng Zhao; Jin Wu; Hao Tang; Zhengang Lv; Binyuan Xu; Longfei Zhou; Rui Sun; Ran Meng (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Trade-offs and synergies of plant traits co-drive efficient nitrogen use in intercropping systems - Hao Yang; Wei-Ping Zhang; Hua-Sen Xu; Rui-Peng Yu; Ye Su; Surigaoge Surigaoge; Pei-Xuan Wang; Xin Yang; Hans Lambers; Long Li (Field Crops Research, 2023)

Crop cultivar mixtures stabilize productivity, partly via facilitation, when conditions are less benign - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Jian-Hao Sun; Jian-Hua Zhao; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (Field Crops Research, 2023)

A multilayer perceptron-based fast sunlight assessment for the conceptual design of residential neighborhoods under Chinese policy - Can Jiang; Xiong Liang; Yu-cheng Zhou; Yong Tian; Shengli Xu; Jia-Rui Lin; Zhiliang Ma; Shiji Yang; Hao Zhou (Building and Environment, 2023)

The role of trifluoroacetic acid in new particle formation from methanesulfonic acid-methylamine - Yue Hu; Shasha Chen; Shasha Ye; Shuqin Wei; Biwu Chu; Rui Wang; Hao Li; Tianlei Zhang (Atmospheric Environment, 2023)

Bradykinin-pretreated Human cardiac-specific c-kit+ Cells Enhance Exosomal miR-3059-5p and Promote Angiogenesis Against Hindlimb Ischemia in mice - Jingzhou Li; Fei Song; Ruolan Chen; Jinjuan Yang; Jie Liu; Li Huang; Fuyu Duan; Meng Kou; Boon Xuan Lian; Xiaoxia Zhou; Weimin Han; Liang Mao; et al. (Stem Cell Reviews and Reports, 2023)

Impact of nitrogen addition on single and mixed tree leaf litter decomposition depends on N forms in subtropical China - Pan-Pan Wu; Zao Zhang; Rui Li; Jing-Hao Ji; Rong Mao (Applied Soil Ecology, 2023)

Research on the source-detector variance reduction method based on the AIS adjoint Monte Carlo method - Yisheng Hao; Rui Qiu; Zhen Wu; Shenshen Gao; Hui Zhang; Junli Li (Annals of Nuclear Energy, 2023)

An epoxide-based covalent sensor to detect cardiac proteome aggregation in a cardio-oncology model - Hao Jin; Di Shen; Biao Jing; Zhenduo Zhang; Zhiming Wang; Rui Sun; Huaiyue Zhang; Jialu Sun; Haochen Lyu; Yu Liu; Lili Wang (Analytica Chimica Acta, 2023)

Complete Genome Sequence of Streptomyces sp. HP-A2021, a Promising Bacterium for Natural Product Discovery - Lan-Fang Li; Qing-Xuan Wu; Hao Wu; Yao Li; Qian Peng; Ren-Hao Han; Da-Hu Zhang; Wei-Dong Yu; Rui Xu; Juan Wang; Zhaobin Fan; Shao-Yang Hou (Biochemical Genetics, 2023)

Phytoplankton control by stocking of filter-feeding fish in a subtropical plateau reservoir, southwest China - Chaoshuo Zhang; Feng Mei; Bin Luo; Dongxu Zhang; Xinyu Cheng; Yongying Xiong; Jianghui Bao; Rui Duan; Hao Jiang; Erik Jeppesen; Ming Duan (Frontiers in Marine Science, 2023)
Stocking of filter-feeding fish (mainly Hypophthalmichthys molitrix and Aristichthys nobilis ) is a common method used in lakes and reservoirs in (sub)tropical China to control phytoplankton, but the results are ambiguous and lack long-term data to support. We analysed a decade (2010-2020) of monitoring data from a subtropical plateau reservoir, southwest China, to which filter-feeding fish were stocked annually. We found that the total phytoplankton biomass, cyanobacteria biomass and average individual mass of phytoplankton decreased significantly during the study period despite absence of nutrient concentration reduction. However, the grazing pressure of zooplankton on phytoplankton also decreased markedly as judged from changes in the ratio of zooplankton biomass to phytoplankton biomass and Daphnia proportion of total zooplankton biomass. This is likely a response to increasing predation on zooplankton by the stocked fish. Our results also indicated that water temperature, total phosphorus and water level promoted phytoplankton growth. Our results revealed that filter-feeding fish contributed to the decline in the biomass of phytoplankton but that it also had a strong negative effect on the grazing pressure of zooplankton on phytoplankton, even in this deep reservoir where zooplankton may have a better chance of survival through vertical migration. The particular strong effect on zooplankton is most likely due to imbalance of stocking and harvesting of fish. In the management of eutrophic reservoirs, the reduction of external nutrient loading should have highest priority. In highland (low temperature) deep-water eutrophic reservoirs, stocking of filter-feeding fish may help to control filamentous phytoplankton provided that the fish stocking is properly managed. The optimal stocking intensity of filter-feeding fish that can help control phytoplankton in such reservoirs without excessive impact on large-bodied zooplankton is a topic for further elucidation, however.

Comparative transcriptome profiling reveals RNA splicing alterations and biological function in patients exposed to occupational noise - Jia-Wei Chen; Jun-Jie Shao; Shao-Fei Zhao; Pei-Heng Lu; Si-Yu Li; Hao Yuan; Peng-Wei Ma; Yu-Qiang Lun; Wei-Long Wang; Rui Liang; Wei Gao; Qian Yang; et al. (Environmental Science and Pollution Research, 2023)

Suppression effects and mechanisms of three typical solid suppressants on titanium hydride dust explosions - Shi-zhou Li; Yang-fan Cheng; Rui Wang; Meng Li; Run Li; Hong-hao Ma (Process Safety and Environmental Protection, 2023)

Structure, rheology, and antifreeze property of the exopolysaccharide from Naematelia aurantialba through basidiospore fermentation - Tao Sun; Xiaoyi Xu; Yuhang Ma; Hao jiang; Kai Yang; Rui Wang; Yian Gu; Sha Li; Yibin Qiu; Dafeng Sun; Hong Xu; Peng Lei (Food Hydrocolloids, 2023)

Exfoliation behavior and superior photothermal conversion performance of MXenes beyond Ti3C2T - Cuilian Wen; Qiugang Liao; Zhou Cui; Ziqiang Chen; Hao Liu; Rui Xiong; Baisheng Sa (Chemical Engineering Journal, 2023)

A surface-induced coating strategy for constructing hydrophobic zeolite composite to enhance the toluene adsorption in humid environment - Shuangchun Lu; Wenjuan Xue; Hao Wang; Qingling Liu; Rui Han; Donghai Mei (Chemical Engineering Journal, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Reduced Survival and Resistance of Rhodotorula mucilaginosa Following Inhibition of Pigment Production by Naftifine - Nur Fazleen Binti Idris; Qianying Jia; He Lu; Yanan Guo; Yang Wang; Rui Hao; Zeng Tu (Current Microbiology, 2023)

Impact of rhizosphere priming on soil organic carbon dynamics: Insights from the perspective of carbon fractions - Hao Cui; Chaoyang Mo; Pengfei Chen; Rui Lan; Chao He; Jingdong Lin; Zhenhui Jiang; Jingping Yang (Applied Soil Ecology, 2023)

Resolved CFD-DEM Simulation of Free Settling of Polyhedral Particles with Various Orientations: Insights Provided by Oscillation Behavior in Quiescent Liquid - Zhimin Zhang; Yuanyi Qiu; Hao Xiong; Rui Tang (Journal of Marine Science and Engineering, 2023)
Particle settling is the process by which particulates move toward the bottom of a liquid, which can affect the sediment transport and energy balance of marine systems. However, the deficiency in understanding the resolved fluid–particle interactions with complex boundaries in the settling process awaits resolution. This study employs a hybrid approach that combines computational fluid dynamics (CFD) with the discrete element method (DEM) to fully simulate the free-settling behavior of polyhedral particles in water. The accuracy of the method is verified by comparing numerical results with experimental data of ellipsoidal particle settling. Two series of tests with horizontal and vertical particle release directions are established to investigate the effects of particle shape features, such as the aspect ratio (AR) and corner (C), on the particles’ mechanical behavior and hydrodynamic characteristics. The results demonstrate that particle shape exerts a substantial influence on fluid resistance, rotational motion, and fluid disturbance throughout the settling process. The maximum velocities in vertically released cases are roughly 1.2–1.3 times greater than those in horizontally released cases. The study highlights the potency of the resolved CFD-DEM method as a robust technique for comprehending fluid–particle phenomena within the marine geotechnical engineering, including sedimentation and erosion of seabed sediments.

Predictive value of serum proteomic biomarkers for noise-induced hearing loss - Yuqiang Lun; Jiawei Chen; Peiheng Lu; Hao Yuan; Pengwei Ma; Weilong Wang; Rui Liang; Siyu Li; Wei Gao; Xuerui Ding; Zi Wang; Jianing Guo; et al. (Environmental Science and Pollution Research, 2023)

Recent advances in core-shell structured catalysts for low-temperature NH3-SCR of NOx - Tong Wu; Rui-tang Guo; Chu-fan Li; Yi-hao You; Wei-guo Pan (Chemosphere, 2023)

Heterophyllin B ameliorates gastric cancer tumor growth through activating ER stress - Wanli Xue; Rui Sun; Zheng Hao; Zhenzhen Xing; Hongjie Cheng; Lei Shao (Tissue and Cell, 2023)

Nano-pesticide carrier O-Carboxymethyl chitosan is indigestible in Apis cerana cerana and affects intestinal flora - Sheng-nan Li; Hao Wu; Rui-quan Hou; Jing-tong Zhou; Su-kun Lin; Kun-yu Zhao; Rui-fei Wang; Su-qing Huang; Zhi-xiang Zhang (Science of The Total Environment, 2023)

Soil acidification in a tailing area of ionic rare earth in Southeast China - Zhe Xu; Jin-ling Yang; Yue Zhao; Rui Hao; Gan-lin Zhang (Science of The Total Environment, 2023)

Dynamic probabilistic risk assessment of emergency response for intelligent coal mining face system, case study: Gas overrun scenario - Yan Zhang; Yu-Hao Wang; Xu Zhao; Rui-Peng Tong (Resources Policy, 2023)

CausalViT: Domain generalization for chemical engineering process fault detection and diagnosis - Hao Huang; Rui Wang; Kun Zhou; Lu Ning; Kai Song (Process Safety and Environmental Protection, 2023)

Experimental study on low-frequency flow noise at the stern of a surface vessel induced by pulsating pressure - Rui Deng; Zhenpu Yan; Xiang Yu; Hao Li; Hailong Liu; Tiecheng Wu (Ocean Engineering, 2023)

Prediction of Permian karst reservoirs in the Yuanba gas field, northern Sichuan Basin, China - Yuxin Hao; Rebecca Bell; Ying Rao; Rui Fan; Yanghua Wang (Marine and Petroleum Geology, 2023)

Aggregation and stability of selenium nanoparticles: Complex roles of surface coating, electrolytes and natural organic matter - Sujuan Yu; Hao Liu; Rui Yang; Wenjing Zhou; Jingfu Liu (Journal of Environmental Sciences, 2023)

Geological ahead-prospecting method while TBM drilling using improved seismic interferometry method: A case - Lei Chen; Lei Hao; Xinji Xu; Fengkai Zhang; Rui Wang (Journal of Applied Geophysics, 2023)

Formation of giant copper deposits in Tibet driven by tearing of the subducted Indian plate - Zengqian Hou; Rui Wang; Haijiang Zhang; Yuanchuan Zheng; Sheng Jin; Hans Thybo; Roberto F. Weinberg; Bo Xu; Zhiming Yang; Ao-Wei Hao; Lei Gao; Letian Zhang (Earth-Science Reviews, 2023)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Bang-Yin Tan; Cai-Feng Ding; Rui-Rong Guo; Jing-Zhi Zhao; Di-Wei Ma; Kun Fan; Lan-Chun Zhang; Rong-Ping Zhang; Wei-Yan Hu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Climate changes in the Hexi Corridor, western China over the past 13.3 ka - Yanzhen Li; Rui Zhang; Hao Long; Peng Cheng; David B. Kemp; Ze Zhang; Chunju Huang; Mengyang Hou; Yue Li; Shizhen Jia; Zhixiang Wang; Liangcheng Tan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Study of infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection in different organs of Penaeus vannamei - Zi-Hao Hou; Yang Gao; Jing-Jing Wang; Cai-Yi Chen; Lin-Rui Chang; Ting Li; Ling-Jun Si; Fan Li; Dong-Chun Yan (Journal of Invertebrate Pathology, 2023)

Carbon nanotubes production from catalytic pyrolysis of polyethylene over nickel-based catalysts: The influence of support materials - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Hao-Ran Yuan; Yong Chen (Fuel, 2023)

Resistant starch formation mechanism of amylosucrase-modified starches with crystalline structure enhanced by hydrothermal treatment - Ren Wang; Pinxin Rui; Tao Wang; Wei Feng; Zhengxing Chen; Xiaohu Luo; Hao Zhang (Food Chemistry, 2023)

Low-Temperature robust MAPbI3 perovskite solar cells with power conversion efficiency exceeding 22.4% - Wenyu Qiu; Yukun Wu; Yichen Wang; Zhiting Yang; Rui Yang; Chenxi Zhang; Yang Hao; Yuying Hao (Chemical Engineering Journal, 2023)

The Regulation of the AMPK/mTOR Axis Mitigates Tendon Stem/Progenitor Cell Senescence and Delays Tendon Aging - Guangchun Dai; Yingjuan Li; Ming Zhang; Panpan Lu; Yuanwei Zhang; Hao Wang; Liu Shi; Mumin Cao; Renwang Shen; Yunfeng Rui (Stem Cell Reviews and Reports, 2023)

A Novel D-π-A Type Fluorescent Probe for Cu2+ Based on Styryl-Pyridinium Salts Conjugating Di-(2-picolyl)amine (DPA) Units - Rui Cao; Mengyu Zhang; Wen Tang; Jing Wu; Meixiang Wang; Xiaoxiao Niu; Zhaodi Liu; Fuying Hao; Huajie Xu (Journal of Fluorescence, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

Lithospheric controls on the formation of the Qilian Shan plateau: Evidence from apatite (U Th)/He and cosmogenic 21Ne results in the Central Qilian Shan - Yan Ma; Jianzhang Pang; Dewen Zheng; Huiping Zhang; Jingxing Yu; Chaopeng Li; Rui Zhang; Yuqi Hao; Ying Wang; Ying Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Sensing property of Pt-doped Janus SnSSe monolayer upon thermal runaway gases in the lithium-ion battery with effects of biaxial strains and electric fields - Di Zheng; Wenjing Peng; Rui Wu; Shunan Quan; Lijuan Qian; Hao Cui (Journal of Environmental Chemical Engineering, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Barbican-inspired bimetallic core–shell nanoparticles for fabricating natural leather-based radiation protective materials with enhanced X-ray shielding capability - Hao Li; Jibo Zhou; Linping Yan; Rui Zhong; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2023)

Boosting charge separation and transfer at the boron-triggered BiVO4 interface for efficient and stable solar water splitting - Hao Wang; Rui-Ting Gao; Lei Wang (Chemical Engineering Journal, 2023)

Comparison of thermal alkaline pretreatment and zinc acetate-catalyzed methanolysis (MtOH-ZnOAc) for anaerobic digestion of bioplastic waste - Jayen Aris Kriswantoro; Chen-Yeon Chu; Ting-Rui Chang; Hao-Jen Pai; Chih-Kai Chang; Yi-Pang Chiu (Bioresource Technology, 2023)

Enhanced biological stabilization of metal-chelant complexes in the chelator-washed soils by sulfate-reducing bacteria - Guixiang Zhang; Yu Gao; Rui Ren; Xiaofang Guo; Baoshan Xing; Yang Li; Zheyun Zhang; Hao Wu (Journal of Soils and Sediments, 2023)

Large-scale characteristics of thermokarst lakes across the source area of the Yellow River on the Qinghai-Tibetan Plateau - Wen-hui Liu; Guang-hao Zhou; Hai-rui Liu; Qing-peng Li; Chang-wei Xie; Qing Li; Jian-yun Zhao; Qi Zhang (Journal of Mountain Science, 2023)

Spatial-temporal Coupling Analysis of Economic Development-Social Development-Government Governance in Xinjiang, China - Haifeng Hu; Yong Sun; Hao Zhao; Baoyin Liu; Rui Guo (Chinese Geographical Science, 2023)

The distribution and emission of CO2, CH4 and light hydrocarbons in an anticyclonic eddy of the Kuroshio extension - Xiao-Jun Li; Jian Wang; Hao Qiao; Rui-Chen Zhu; Hong-Hai Zhang; Zhao-Hui Chen; Andrew Montgomery; Shan Zheng; Guang-Chao Zhuang (Frontiers in Marine Science, 2023)
Mesoscale eddies are energetic and swirling circulations that frequently occur in the open ocean. The effects of mesoscale eddies on the biogeochemical cycling of climate-relevant gases remain poorly constrained. We investigated the distribution and air-sea fluxes of CO 2 , methane, and five non–methane hydrocarbons (NMHCs) in an anticyclone eddy of Kuroshio Extension during September 2019. Within eddy core, intense stratification hindered the replenishment of nutrients and favored the growth of small-size phytoplankton, such as Prochlorococcus . Seawater pCO 2 decreased from 406.1 μatm at the eddy outside to 377.5 μatm at the eddy core, accompanied by a decrease in surface seawater temperature from 26.7 °C to 25.2 °C. The vertical distribution of methane (0.3-9.9 nmol L -1 ) was influenced by the eddy process, with a maximum at 80 m in the eddy core, which might be attributed to the degradation of phosphonates sustained by Prochlorococcus . The concentrations of five NMHCs (ethane, ethylene, propane, propylene, and isoprene) ranged from 17.2-126.2, 36.7-168.1, 7.5-29.2, 22.6-64.1, 54.5-172.1, 3.5-27.9 pmol L -1 , respectively. Isoprene correlated well with Chl- a concentrations at the eddy core, while no significant correlation was observed at the eddy outside. Air-sea fluxes of CO 2 and isoprene associated with the eddy core were higher than those of the eddy outside, while the maximum ventilation of methane and other NMHCs (ethane, ethylene, propane, and propylene) was found at the eddy outside. Collectively, physical processes such as eddies impact the production and distribution of light hydrocarbons in seawater and further influence their regional emissions to the atmosphere.

Plant litter strengthens positive biodiversity–ecosystem functioning relationships over time - Wei-Ping Zhang; Dario Fornara; Hao Yang; Rui-Peng Yu; Ragan M. Callaway; Long Li (Trends in Ecology & Evolution, 2023)

High magnesian schist, granitic gneiss, amphibolite and monzogneiss in the eastern Ama Drime Massif in South Tibet (China): A rifted Paleoproterozoic arc fringed the western Columbia supercontinent? - Rui Li; Wenjiao Xiao; Qigui Mao; Ji'en Zhang; Songjian Ao; Dongfang Song; Zhou Tan; Hao Wang; Saunak Bhandari (Precambrian Research, 2023)

Particulate matter capturing over manganese dioxides with different crystal structures - Rui Liu; Huan-Huan Yang; Hao Zhou; Xianliang Yi; Yang Liu (Journal of Environmental Sciences, 2023)

Theoretical study the electrocatalytic performance and mechanism of novel designed electrocatalyst Ru@2DMs for CO2RR - Linxia Cui; Ke Shi; Mingyuan Zhang; Jiuwen Guo; Zhe Yan; Haigang Hao; Rui Gao (Fuel, 2023)

Preparation and characterization of V-type starch nanoparticles by an oil-water interface method - Hao Lu; Xiaoyang He; Yang Qin; Na Ji; Lei Dai; Liu Xiong; Rui Shi; Tao Wang; Qingjie Sun (Food Hydrocolloids, 2023)

Seismic damage characteristics and evaluation of aboveground-underground coupled structures - Gang Li; Han Zhang; Rui Wang; Zhi-Qian Dong; Ding-Hao Yu (Engineering Structures, 2023)

Construction of 1D/2D core-shell structured K6Nb10.8O30@Zn2In2S5 as S-scheme photocatalysts for cocatalyst-free hydrogen production - Jing Wang; Runhui Pan; Shiye Yan; Rui Wang; Xingyu Niu; Qi Hao; Jilei Ye; Yuping Wu; Hui Ying Yang (Chemical Engineering Journal, 2023)

Hybrid plasma-thermal system for methane conversion to ethylene and hydrogen - Rui Liu; Yingzi Hao; Tong Wang; Li Wang; Annemie Bogaerts; Hongchen Guo; Yanhui Yi (Chemical Engineering Journal, 2023)

Centrifuge and numerical modeling of h-type anti-slide pile reinforced soil-rock mixture slope - Hao Zhang; Hao-feng Xing; Dao-rui Xue; Dwayne Tannant (Journal of Mountain Science, 2023)

Comparative transcriptomes analysis of the ovary reveals potential ovarian development-related genes and pathways in Macrobrachium rosenbergii - Yan-Hao Yang; Rui Wang; Ming Li; Hui-Zan Yang; Guang-Hua Huang; Ke-Yi Ma; Gao-Feng Qiu; Yong Lin (Invertebrate Reproduction & Development, 2023)

Interpretable machine learning assisted spectroscopy for fast characterization of biomass and waste - Rui Liang; Chao Chen; Tingxuan Sun; Junyu Tao; Xiaoling Hao; Yude Gu; Yaru Xu; Beibei Yan; Guanyi Chen (Waste Management, 2023)

High-grade complexes record the Late Permian-Middle Triassic arc metamorphism in the southernmost Altaids: Implications for the final closure of the Paleo-Asian Ocean - Hao Wang; Wenjiao Xiao; Rui Li; Hongxu Chen; Zhou Tan; Qigui Mao; Mengyan Shi (Lithos, 2023)

Responses of agricultural drought to meteorological drought under different climatic zones and vegetation types - Peng Sun; Ruilin Liu; Rui Yao; Hao Shen; Yaojin Bian (Journal of Hydrology, 2023)

Multi-model analysis of historical runoff changes in the Lancang-Mekong River Basin – Characteristics and uncertainties - Yuxin Li; Aifang Chen; Ganquan Mao; Penghan Chen; Hao Huang; Hong Yang; Zifeng Wang; Kai Wang; He Chen; Ying Meng; Rui Zhong; Pengfei Wang; et al. (Journal of Hydrology, 2023)

New insight into the role of the emulsified diesel droplet size in low rank coal flotation - Jincheng Liu; Rui Zhang; Xicheng Bao; Yesheng Hao; Xiahui Gui; Yaowen Xing (Fuel, 2023)

Highly stability Cu+ species in hollow Cu2O nanoreactors by modulating cavity size for CO2 electroreduction to C2+ products - Rui Zhang; Feifei Chen; Haokun Jin; Yong Zhang; Xiaoya Hao; Yingda Liu; Tianming Feng; Xinghua Zhang; Zunming Lu; Weihua Wang; Feng Lu; Hong Dong; et al. (Chemical Engineering Journal, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Discovery of Neoproterozoic adakitic rocks in the Eastern Tianshan (NW China) of the southern Altaids - Meng Wang; Qigui Mao; Wenjiao Xiao; He Yang; Hao Wang; Rui Li (International Journal of Earth Sciences, 2023)

Determination of lead in Gentiana rigescens and evaluation of the effect of lead exposure on the liver protection of the natural medicine - Rui Zhang; Caixia Yan; Xiaofang Yang; Kan Hu; Fangfang Hao; Shengchun Yang; Qingwen Deng; Zhenjuan Duan; Yong Liu; Xiaodong Wen (Analytica Chimica Acta, 2023)

Study on non-point source pollution characteristics under different spatial scales: a case study of Hanjiang River Basin, China - Ya-jiao Li; Jia-ping Wang; Zi-hang Zhang; Gai-rui Hao; Ya-fang Li; Jia-ke Li (Environmental Science and Pollution Research, 2023)

Diffusion simulation and risk assessment model establishment of chlorine gas leakage based on terrain conditions - Xiao-ting Ren; Xiao-ling Ma; Jiang-zheng Liu; Rui Liu; Chen-qian Zhao; Hao Wu; Zhao Wang; Chun-xu Hai; Xiao-di Zhang (Environmental Science and Pollution Research, 2023)

Circ_0021573 acts as a competing endogenous RNA to promote the malignant phenotypes of human ovarian cancer cells - Lifang Liu; Bingkai Han; Lixia Liu; Hongying Cui; Hao Liu; Rui Jia; Xiaoyan Zhang; Xiaoxiao Lu (Reproductive Biology, 2023)

SUMOylation-modified Pelota-Hbs1 RNA surveillance complex restricts the infection of potyvirids in plants - Linhao Ge; Buwei Cao; Rui Qiao; Hongguang Cui; Shaofang Li; Hongying Shan; Pan Gong; Mingzhen Zhang; Hao Li; Aiming Wang; Xueping Zhou; Fangfang Li (Molecular Plant, 2023)

Machine learning approaches to predict the apparent rate constants for aqueous organic compounds by ferrate - Shan-Shan Zheng; Wan-Qian Guo; Hao Lu; Qi-Shi Si; Bang-Hai Liu; Hua-Zhe Wang; Qi Zhao; Wen-Rui Jia; Tai-Ping Yu (Journal of Environmental Management, 2023)

Variability of fuel consumption and CO2 emissions of a gasoline passenger car under multiple in-laboratory and on-road testing conditions - Boya Zhou; Liqiang He; Shijian Zhang; Rui Wang; Luowei Zhang; Mengliang Li; Yu Liu; Shaojun Zhang; Ye Wu; Jiming Hao (Journal of Environmental Sciences, 2023)

Sulfite altered permanganate effects on acetate-enriched short-chain fatty acids production during sludge anaerobic fermentation - Lijuan Wu; Rui Zhu; Xiaoxia Han; Yan Chen; Zhen Long; Hao Dong; Xiaojiang Chen; Yang Wu; Yinglong Su; Zhengyong Zhang; Jingyang Luo (Bioresource Technology, 2023)

Morphology and location of sensilla in the antennae and ovipositor of Sirex noctilio (Hymenoptera: Siricidae) - Enhua Hao; Rui Liu; Ruirui Xu; Pengfei Lu; Haili Qiao (Arthropod Structure & Development, 2023)

Research in superior bearing performance of the ostrich tarsometatarsus based on its structural features - Rui Zhang; Xumin Sun; Hao Pang; Shuliang Xue; Hua Zhang; Zhenyu Hu; Meng Zou (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

High cholesterol intake remodels cholesterol turnover and energy homeostasis in Nile tilapia (Oreochromis niloticus) - Rui-Xin Li; Ling-Yun Chen; Samwel M. Limbu; Yu-Cheng Qian; Wen-Hao Zhou; Li-Qiao Chen; Yuan Luo; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Marine Life Science & Technology, 2023)
The roles of dietary cholesterol in fish physiology are currently contradictory. The issue reflects the limited studies on the metabolic consequences of cholesterol intake in fish. The present study investigated the metabolic responses to high cholesterol intake in Nile tilapia ( Oreochromis niloticus ), which were fed with four cholesterol-contained diets (0.8, 1.6, 2.4 and 3.2%) and a control diet for eight weeks. All fish-fed cholesterol diets showed increased body weight, but accumulated cholesterol (the peak level was in the 1.6% cholesterol group). Then, we selected 1.6% cholesterol and control diets for further analysis. The high cholesterol diet impaired liver function and reduced mitochondria number in fish. Furthermore, high cholesterol intake triggered protective adaptation via (1) inhibiting endogenous cholesterol synthesis, (2) elevating the expression of genes related to cholesterol esterification and efflux, and (3) promoting chenodeoxycholic acid synthesis and efflux. Accordingly, high cholesterol intake reshaped the fish gut microbiome by increasing the abundance of Lactobacillus spp. and Mycobacterium spp., both of which are involved in cholesterol and/or bile acids catabolism. Moreover, high cholesterol intake inhibited lipid catabolic activities through mitochondrial β-oxidation, and lysosome-mediated lipophagy, and depressed insulin signaling sensitivity. Protein catabolism was elevated as a compulsory response to maintain energy homeostasis. Therefore, although high cholesterol intake promoted growth, it led to metabolic disorders in fish. For the first time, this study provides evidence for the systemic metabolic response to high cholesterol intake in fish. This knowledge contributes to an understanding of the metabolic syndromes caused by high cholesterol intake or deposition in fish.

Phytoplankton biomass dynamics with diffuse terrestrial nutrients pollution discharge into bay - Wei Ouyang; Rui Wang; Kaiyue Ji; Xitao Liu; Fang Geng; Xin Hao; Chunye Lin (Chemosphere, 2023)

Dietary sodium acetate improves high-fat diet utilization through promoting differential nutrients metabolism between liver and muscle in Nile tilapia (Oreochromis niloticus) - Wen-Hao Zhou; Samwel M. Limbu; Rui-Xin Li; Yuan Luo; Jiong Ren; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Aquaculture, 2023)

Effects of varying levels of crawfish (Procambarus clarkia) shell meals on growth, fillet quality, and health of koi carp (Cyprinus carpio) - Xiaofei Cheng; Jin Xiang; Jingjing Tian; Xing Tian; Hao Wu; Xiping Yuan; Zhigang He; Min Xie; Rui Song (Aquaculture, 2023)

Predictive and estimation model of Cd, Ni, and Zn bioaccumulations in maize based on diffusive gradients in thin films - Rui Chen; Xiulin Mu; Jiaxing Liu; Nuo Cheng; Rongguang Shi; Miaomiao Hu; Zhuoran Chen; Hao Wang (Science of The Total Environment, 2023)

In situ degradation of low-density polyethylene film in irrigation maize field: Thickness-dependent effect - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Rui Zhou; Jing Cao; Jing Wang; Kiprotich Wesly; Wen-Li Wang; Ning Wang; Meng Hao; Yi-Bo Wang; Hong-Yan Tao; et al. (Science of The Total Environment, 2023)

WITHDRAWN:Prediction of Permian karst reservoirs in the Yuanba gas field, northern Sichuan Basin, China - Yuxin Hao; Rebecca Bell; Dongfeng Hu; Rui Fan; Yanghua Wang (Marine and Petroleum Geology, 2023)

How seasonality affects the environmental performance of fresh appetite: Insights from cherry consumption in China - Xin Xiong; Junyi Shen; Yan Hao; Lixiao Zhang; Rui Zhao; Shoujuan Tang; Xinqing Li; Zhimin Shi (Journal of Environmental Management, 2023)

Novel polysaccharide from Panax notoginseng with immunoregulation and prebiotic effects - Hui-Rong Yang; Xue Li; Hao Liu; Dong-Rui Zhao; Ying-Jie Zeng (Food Bioscience, 2023)

Longitudinal shear behavior and design method of UHPC connection for prefabricated slabs in composite beams - Hao Wang; Xiao-gang Liu; Qing-rui Yue; Ning Wang; Ming-zhao Zheng (Engineering Structures, 2023)

Axial compression behaviour of round-ended recycled aggregate concrete-filled steel tube stub columns (RE-RACFST): Experiment, numerical modeling and design - Hui Zhao; Wen-Hao Zhang; Rui Wang; Chuan-Chuan Hou; Dennis Lam (Engineering Structures, 2023)

Facile fabrication of flexible and ultrathin self-assembled Ti3C2T /bacterial cellulose composite films with multifunctional electromagnetic shielding and photothermal conversion performances - Hao Liu; Zhou Cui; Lijin Luo; Qiugang Liao; Rui Xiong; Chao Xu; Cuilian Wen; Baisheng Sa (Chemical Engineering Journal, 2023)

Friction induced mechanochemistry: self-adaptive lubrication through in-situ tribo-click system - Rui Dong; Yunlei Zhang; Hao-Zhe Xu; Luyao Bao; Shuanhong Ma; Xin-Gang Wang; Qiangliang Yu; Meirong Cai; Feng Zhou; Weimin Liu (Chemical Engineering Journal, 2023)

Redox of anionic and cationic radical intermediates in a bipolar polyimide COF for high-performance dual-ion organic batteries - Shuai Gu; Jingjing Chen; Rui Hao; Xi Chen; Zhiqiang Wang; Iftikhar Hussain; Guiyu Liu; Kun Liu; Qingmeng Gan; Zhiqiang Li; Hao Guo; Yingzhi Li; et al. (Chemical Engineering Journal, 2023)

Nitrogen-doped carbonized polyaniline (N-CPANI) for peroxydisulfate (PDS) activation towards efficient degradation of doxycycline (DOX) via the non-radical pathway dominated by electron transfer - Minxian Cheng; Rui Ma; Guodong Chai; Yongjun Chen; Linqin Bai; Dongqi Wang; Jin Qian; Guang-Hao Chen (Chemical Engineering Journal, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Territorial function differentiation and its comprehensive regionalization in China - Jie Fan; Kan Zhou; Kerong Sheng; Rui Guo; Dong Chen; Yafei Wang; Hanchu Liu; Zheng Wang; Yong Sun; Jie Zhang; Jianxiong Wu; Hao Zhao (Science China Earth Sciences, 2023)

A Medicago truncatula lncRNA MtCIR1 negatively regulates response to salt stress - Rui Tian; Xiaohan Sun; Cuimei Liu; Jinfang Chu; Mingui Zhao; Wen-Hao Zhang (Planta, 2023)

MicroRNA-588 regulates the invasive, migratory and vasculogenic mimicry-forming abilities of hypoxic glioma cells by targeting ROBO1 - Rui Yu; Rongrong Zhao; Xiaopeng Sun; Zongpu Zhang; Shaobo Wang; Xiao Gao; Zhongzheng Sun; Hao Xue; Gang Li (Molecular Biology Reports, 2023)
Background The microenvironment of hypoxia is an important factor contributing to the development of glioblastoma (GBM). MicroRNA-588 and its potential target Roundabout-directed receptor 1 (ROBO1) have been reported to promote tumor invasion and proliferation in diseases such as gastric, pancreatic and hepatocellular carcinoma, while their function in GBM and response to hypoxic states remain elusive. Methods A microarray was leveraged to identify differentially expressed microRNAs in U251 glioma cells cultured under normoxic and hypoxic conditions. The expression of miR-588 was assessed using quantitative real-time PCR (qRT‒PCR). Gain- and loss-of-function studies were used to evaluate the role of miR-588 under hypoxic and normoxic conditions. Cell invasion, migration, proliferation, and vasculogenic mimicry (VM) formation experiments were performed. The relationship between miR-588 and ROBO1 was confirmed using western blot and luciferase reporter assays. Intracranial xenograft tumor mouse models were used to study the function of miR-588 in vivo. Results The expression of miR-588 was significantly upregulated in hypoxic glioma cells relative to normoxic glioma cells. miR-588 inhibited the invasive, migratory and VM-forming abilities of glioma cells in vitro and in vivo. Mechanistically, roundabout guidance receptor 1 (ROBO1) is a direct, functionally relevant target of miR-588 in glioma. ROBO1 knockdown suppressed the expression of matrix metallopeptidase 2 (MMP2) and matrix metallopeptidase 9 (MMP9), thereby inhibiting the invasive, migratory and VM-forming abilities of glioma. Conclusions MiR-588 regulated the behaviors of hypoxic glioma cells by targeting ROBO1. miR-588 can be used as a prognostic marker for glioma and has potential implications in glioma gene therapy.

Orbital and Millennial-Scale Climate Variability over the Past 76 ka in the Western Tarim Basin, Northwest China - Rui Zhang; Qiuzhen Yin; Weihua Nai; Zhixiang Wang; Hao Lu; Chunju Huang; Yansheng Gu; Lin Li; Yusong Wang; Linjing Liu (Journal of Earth Science, 2023)

Intercrop overyielding weakened by high inputs: Global meta-analysis with experimental validation - Shuang-Guo Zhu; Hao Zhu; Rui Zhou; Wei Zhang; Wei Wang; Yi-Ning Zhou; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; Hong-Yan Tao; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Effects of chemical additives and mature compost on reducing nitrogen loss during food waste composting - Shangao Xiong; Yongdi Liu; Hao Zhang; Shaoqi Xu; Songrong Li; Xinqi Fan; Rui Chen; Guochun Ding; Ji Li; Yuquan Wei (Environmental Science and Pollution Research, 2023)

Effects of dietary methionine on growth and body composition, indicators of digestion, protein metabolism and immunity, and resistance to heat stress of abalone Haliotis discus hannai - Hao Chen; Wenhao Fan; Hongyang Zhang; Panpan Yue; Rui Wang; Wenbing Zhang; Kangsen Mai (Aquaculture, 2023)

Evaluation of the pathogenesis of non-typical strain with α-hemolysin, Vibrio parahaemolyticus 353, isolated from Chinese seafood through comparative genome and transcriptome analysis - Fei Zha; Rui Pang; Shixuan Huang; Jumei Zhang; Juan Wang; Moutong Chen; Liang Xue; Qinghua Ye; Shi Wu; Meiyan Yang; Qihui Gu; Yu Ding; et al. (Marine Pollution Bulletin, 2023)

Soil microbial community structure dynamics shape the rhizosphere priming effect patterns in the paddy soil - Hao Cui; Pengfei Chen; Chao He; Zhenhui Jiang; Rui Lan; Jingping Yang (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Combination of hyperspectral imaging and machine learning models for fast characterization and classification of municipal solid waste - Junyu Tao; Yude Gu; Xiaoling Hao; Rui Liang; Biyu Wang; Zhanjun Cheng; Beibei Yan; Guanyi Chen (Resources, Conservation and Recycling, 2023)

Fungal polyketides from a rhizospheric soil-derived Penicillium sp. YUD17004 associated with Gastrodia elata - Hong-Tao Li; Rui-Ning Yang; Tao Liu; Fei Xie; Hao-Jie Duan; Dan-Dan Xia; Hao Zhou; Zhong-Tao Ding (Phytochemistry, 2023)

Characteristics and origin of Lower Triassic Feixianguan Formation dolostones on the west side of Kaijiang–Liangping Trough, northeastern Sichuan Basin, China - Ling Zhou; Guangwei Wang; Ya Zhang; Yanping Qiao; Fang Hao; Rui Xu; Li Quan; Ping Wang (Marine and Petroleum Geology, 2023)

Impact of international trade on water scarcity: An assessment by improving the Falkenmark indicator - Rui Zhong; Aifang Chen; Dandan Zhao; Ganquan Mao; Xu Zhao; Hao Huang; Junguo Liu (Journal of Cleaner Production, 2023)

Learn then match: A fast coarse-to-fine depth image-based indoor localization framework for dark environments via deep learning and keypoint-based geometry alignment - Qing Li; Rui Cao; Jiasong Zhu; Hao Fu; Baoding Zhou; Xu Fang; Sen Jia; Shenman Zhang; Kanglin Liu; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Identification of high iron–chelating peptides with unusual antioxidant effect from sea cucumbers and the possible binding mode - Chaozhong Fan; Xiaofan Ge; Junyu Hao; Tao Wu; Rui Liu; Wenjie Sui; Jieting Geng; Min Zhang (Food Chemistry, 2023)

Characteristics of non-point source pollution based on monitoring experiment in the Yingwugou small watershed, China - Kai Peng; Jia-ke Li; Gai-rui Hao; Yi-wen Liu; Xiang Zhou; Wei-feng Xie (Ecohydrology & Hydrobiology, 2023)

Acute deltamethrin exposure induces oxidative stress, triggers endoplasmic reticulum stress, and impairs hypoxic resistance of crucian carp - Xiping Yuan; Hao Wu; Jinwei Gao; Xiangchang Geng; Min Xie; Rui Song; Jiaomei Zheng; Yuanan Wu; Dongsheng Ou (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Construction of polyphosphazene-functionalized Ti3C2TX with high efficient flame retardancy for epoxy and its synergetic mechanisms - Hao Jiang; Yuhui Xie; Rui Zhu; Yong Luo; Xinxin Sheng; Delong Xie; Yi Mei (Chemical Engineering Journal, 2023)

Facile fabrication of hierarchically porous melamine foam@COF composite for sample treatment of non-targeted food safety analysis and oil/water separation - Wei Li; Wei-Liang Jin; Hong-Xin Jiang; Rui Wang; Hao Jia; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

All-in-one additive enables defect passivated, crystallization modulated and moisture resisted perovskite films toward efficient solar cells - Chuanming Tian; Yu Zhao; Xuefei Han; Bin Li; Yichuan Rui; Hao Xiong; Yu Qiu; Wei An; Kerui Li; Chengyi Hou; Yaogang Li; Hongzhi Wang; et al. (Chemical Engineering Journal, 2023)

Enhancing structural and cycle stability of Prussian blue cathode materials for calcium-ion batteries by introducing divalent Fe - Chong-Yu Du; Zi-Hao Zhang; Xun-Lu Li; Rui-Jie Luo; Cui Ma; Jian Bao; Jie Zeng; Xuan Xu; Fei Wang; Yong-Ning Zhou (Chemical Engineering Journal, 2023)

Rapid, selective, and room temperature dissolution of crystalline xylan by a hydrotrope - Qiaoling Liu; Rui Tian; Ziwen Lv; Yuying Wu; Baozhong Lv; Xiang Hao; Zhimin Xue; Feng Peng (Carbohydrate Polymers, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

Soil water and phosphorus availability determines plant-plant facilitation in maize-grass pea intercropping system - Shuang-Guo Zhu; Hao Zhu; Zheng-Guo Cheng; Rui Zhou; Yu-Miao Yang; Jing Wang; Wei Wang; Bao-Zhong Wang; Hong-Yan Tao; You-Cai Xiong (Plant and Soil, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Effects of Dietary Eucommia ulmoides Leaf Extract on Growth, Muscle Composition, Hepatopancreas Histology, Immune Responses and Microcystin-LR Resistance of Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Yao-Peng Lu; Pei-Hua Zheng; Jia-Rui Xu; Yan-Lei Cao; Jun-Tao Li; Chen-Guang Hao; Ze-Long Zhang; Jian-An Xian; Xiu-Xia Zhang; An-Li Wang (Fishes, 2022)
The objective of the present study was to investigate the effects of different doses of dietary Eucommia ulmoides leaf extract (ELE) on juvenile red claw crayfish (Cherax quadricarinatus). A total number of 720 red claw crayfish (initial body weight of 0.24 ± 0.01 g) were randomly assigned to six groups and fed diets containing 0 (Diet 1), 0.5 (Diet 2), 1 (Diet 3), 2 (Diet 4), 4 (Diet 5) and 10 (Diet 6) g dry weight (dw) ELE kg (dw)−1 diets for eight weeks and challenged with microcystin-LR stress. The results indicated that dietary supplementation with 1–2 g dw ELE kg (dw)−1 diet could significantly improve the weight gain rate (WGR) and specific growth rate (SGR) of crayfish. Muscle crude protein contents of crayfish fed Diet 2, Diet 3, and Diet 4 were significantly higher than those of the control group. Compared with the control group, dietary ELE could increase total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GPx), acid phosphatase (ACP), alkaline phosphatase (AKP), and phenoloxidase (PO) activities and decrease malondialdehyde (MDA) level of crayfish. Dietary ELE significantly increased the relative expression levels of SOD, thioredoxin 1 (TRX1), GPx, selenium-dependent glutathione peroxidase (Se-GPx), cytochrome P450 (CYP450), anti-lipopolysaccharide factor (ALF) and C-type lysozyme (C-LZM) mRNA of crayfish compared with the control group during the feeding experiment. When subjected to MC-LR stress for 48 h, the mRNA expression levels of SOD, GPx, Se-GPx, glutathione-s-transferase 1 (GST1), ALF, hemocyanin (HEM), and C-LZM in the hepatopancreas could be improved to varying degrees compared with the Diet 1. Supplementation of 1–2 g dw ELE kg (dw)−1 diet could improve the survival rate (SR) of crayfish under MC-LR stress. These results indicated that dietary ELE (1–2 g dw ELE kg (dw)−1 diet) could improve the growth performance, muscle protein, and non-specific immune response and increase the SR of crayfish under MC-LR stress by regulating the mRNA expression levels of the immune- and antioxidant-related genes.

Leakage Fault Diagnosis of Lifting and Lowering Hydraulic System of Wing-Assisted Ships Based on WPT-SVM - Ranqi Ma; Haoyang Zhao; Kai Wang; Rui Zhang; Yu Hua; Baoshen Jiang; Feng Tian; Zhang Ruan; Hao Wang; Lianzhong Huang (Journal of Marine Science and Engineering, 2022)
Wing-assisted technology is an effective way to reduce emissions and promote the decarbonization of the shipping industry. The lifting and lowering of wing-sail is usually driven by hydraulic system. Leakage, as an important failure form, directly affects the safety as well as the functioning of hydraulic system. To increase the system reliability and improve the wing-assisted effect, it is essential to conduct leakage fault diagnosis of lifting and lowering hydraulic system. In this paper, an AMESim simulation model of lifting and lowering hydraulic system of a Very Large Crude Carrier (VLCC) is established to analyze the operation characteristics of the hydraulic system. The effectiveness of the model is verified by the operation data of the actual hydraulic system. On this basis, a wavelet packet transform (WPT)-based sensitive feature extracting method of leakage fault for the hydraulic system is proposed. Subsequently, a support vector machine (SVM)-based multi-classification model and diagnosis method of leakage fault are proposed. The study results show that the proposed method has an accuracy of as high as 97.5% for six leakage fault modes. It is of great significance for ensuring the reliability of the wing-sail operation and improving the utilization rate of the offshore wind resources.

Establishment and comprehensive analysis of a new human cell line (NK-NJ) with NK-cell characteristics established from extranodal natural killer cell lymphoma/leukemia - Jin-Hua Liang; Wei-Ting Wang; Kai-Xin Du; Tong-Yao Xing; Yan Wang; Hui Wang; Lu Liu; Rui Guo; Yang Shao; Junheng Liang; Yue Li; Hao-Rui Shen; et al. (Human Cell, 2022)

Effects and mechanism of ultrasound treatment on Chironomus kiiensis eggs - Bo-dong Liu; Hao-tao Dong; Hong-wei Rong; Rui-jian Zhang (Environmental Science and Pollution Research, 2022)

Ferroptosis induced by the biocontrol agent Pythium oligandrum enhances soybean resistance to Phytophthora sojae - Yang Cheng; Huanxin Zhang; Wenyi Zhu; Qing Li; Rui Meng; Kun Yang; Ziqian Guo; Ying Zhai; Haijing Zhang; Rui Ji; Hao Peng; Daolong Dou; et al. (Environmental Microbiology, 2022)
Ferroptosis is a newly discovered form of cell death accompanied by iron accumulation and lipid peroxidation. Both biotic and abiotic stresses can induce ferroptosis in plant cells. In the case of plant interactions with pathogenic Phytophthora oomycetes, the roles of ferroptosis are still largely unknown. Here, we performed transcriptome analysis on soybean plants treated with the biocontrol agent Pythium oligandrum , a soilborne and non‐pathogenic oomycete capable of inducing plant resistance against Phytophthora sojae infection. Expression of homologous soybean genes involved in ferroptosis and resistance was reprogrammed upon P. oligandrum treatment. Typical hallmarks for characterizing ferroptosis were detected in soybean hypocotyl cells, including decreased glutathione (GSH) level, accumulation of ferric ions, and lipid peroxidation by reactive oxygen species (ROS). Meanwhile, ferroptosis‐like cell death was triggered by P. oligandrum to suppress P. sojae infection in soybean. Protection provided by P. oligandrum could be attenuated by the ferroptosis inhibitor ferrostatin‐1 (Fer‐1), suggesting the critical role of ferroptosis in soybean resistance against P. sojae . Taken together, these results demonstrate that ferroptosis is a P. oligandrum ‐inducible defence mechanism against oomycete infection in soybean.

Tectonic framework of Eastern Tianshan in the Early Carboniferous: constraints from alkalic intrusive rocks - Yi-Hao Liu; Chun-Ji Xue; Yun Zhao; Rui Wang; Liang Yu (International Journal of Earth Sciences, 2022)

Characterization of a Hyaluronidase-Producing Bacillus sp. CQMU-D Isolated from Soil - Lu Wang; Qianqian Liu; Rui Hao; Jing Xiong; Junxing Li; Yanan Guo; Lu He; Zeng Tu (Current Microbiology, 2022)

Sex-Specific Association Between Iron Status and the Predicted 10-Year Risk for Atherosclerotic Cardiovascular Disease in Hypertensive Patients - Juan Zhou; Rui Zhao; Dongxia Wang; Qin Gao; Dan Zhao; Binfa Ouyang; Liping Hao; Xiaolin Peng (Biological Trace Element Research, 2022)
Serum ferritin (SF) and haemoglobin (Hb) are widely used in clinical practice to assess iron status. Studies exploring the relationship of SF and Hb with atherosclerotic cardiovascular disease (ASCVD) risk have yielded conflicting results, and some indicated sex specificity. Hypertensive patients have abnormal iron status. However, research on patients with hypertension is limited. We aim to investigate the sex-specific links of SF and Hb with the predicted 10-year ASCVD risk in hypertensive patients. This cross-sectional study included 718 hypertensive men and 708 hypertensive women. The predicted 10-year ASCVD risk was calculated based on the China-PAR equation. The dose–response curves were illustrated by fitting linear and quadratic models. In hypertensive men, the iron status fits for a quadratic model for ASCVD risk, showing a U-shape. After adjusting for potential confounding factors, the regression coefficients and 95% confidence intervals (95% CI) across tertile of SF were 0.0 (reference), − 0.99 (− 1.65, − 0.33) and − 0.22 (− 0.88, 0.44), and of Hb were 0.0 (reference), − 0.74 (− 1.41, − 0.08) and − 0.77 (− 1.46, − 0.08). In hypertensive women, iron status was linearly and positively associated with ASCVD risk. Per one unit increment of log-transformed SF as well as Hb was associated with a 1.22 (95% CI: 0.97, 1.48) and 0.04 (95% CI: 0.02, 0.07) increased in ASCVD risk score, respectively. A significant interaction between iron status and inflammation on ASCVD risk was observed in hypertensive women. SF and Hb showed a U-shape with ASCVD risk in hypertensive men; however, a positive linear relationship was observed in hypertensive women.

Will climate change cause the global peatland to expand or contract? Evidence from the habitat shift pattern of Sphagnum mosses - Xiao‐Ying Ma; Hao Xu; Zi‐Yin Cao; Lei Shu; Rui‐Liang Zhu (Global Change Biology, 2022)
Peatlands play a crucial role in the global carbon cycle. Sphagnum mosses (peat mosses) are considered to be the peatland ecosystem engineers and contribute to the carbon accumulation in the peatland ecosystems. As cold‐adapted species, the dominance of Sphagnum mosses in peatlands will be threatened by climate warming. The response of Sphagnum mosses to climate change is closely related to the future trajectory of carbon fluxes in peatlands. However, the impact of climate change on the habitat suitability of Sphagnum mosses on a global scale is poorly understood. To predict the potential impact of climate change on the global distribution of Sphagnum mosses, we used the MaxEnt model to predict the potential geographic distribution of six Sphagnum species that dominate peatlands in the future (2050 and 2070) under two greenhouse gas emission scenarios (SSP1‐2.6 and SSP5‐8.5). The results show that the mean temperature of the coldest quarter, precipitation of the driest month, and topsoil calcium carbonate are the main factors affecting the habitat availability of Sphagnum mosses. As the climate warms, Sphagnum mosses tend to migrate northward. The suitable habitat and abundance of Sphagnum mosses increase extensively in the high‐latitude boreal peatland (north of 50°N) and decrease on a large scale beyond the high‐latitude boreal peatland. The southern edge of boreal peatlands would experience the greatest decline in the suitable habitat and richness of Sphagnum mosses with the temperature rising and would be a risk area for the transition from carbon sink to carbon source. The spatial–temporal pattern changes of Sphagnum mosses simulated in this study provide a reference for the development of management and conservation strategies for Sphagnum bogs.

Impact of climate change on long-term variations of small yellow croaker (Larimichthys polyactis) winter fishing grounds - Rui Zhang; Yang Liu; Hao Tian; Shuhao Liu; Kaiwei Zu; Xinmei Xia (Frontiers in Marine Science, 2022)
Small yellow croaker ( Larimichthys polyactis ) is one of the key demersal species with high economic values and wide distribution in the China Seas. In this study, a Winter Fishing ground Abundance Index (WFAI) was developed by using fisheries survey data in 1971–1982 and used as the response variable to investigate the impacts of environmental variables, including surface current velocity (SCV), sea surface salinity (SSS), sea surface temperature (SST), and depth (DE). A total of 45 combinatorial generalized additive models (GAMs), generalized linear models (GLMs), and random forest models (RFs) were used to select the optimal WFAI prediction. The final WFAI distribution results showed that the winter fishing ground hotspots of small yellow croaker were mainly distributed between 11°C and 16°C isotherms and between 50-m and 100-m isobaths, and the area of winter fishing ground hotspots (WFHA) significantly decreased and the hotspots tended to move northward over the past 50 years. The shape of hotspots was strongly affected by temperature fronts and salinity fronts. Analysis with the climate indices revealed that the Atlantic Multidecadal Oscillation (AMO) might have a large influence on the distribution of small yellow croaker by affecting SST and SSS in the China Seas more than the Pacific Decadal Oscillation (PDO), North Pacific Gyre Oscillation (NPGO), and Arctic Oscillation Index (AOI). The future prediction based on two extreme scenarios (RCP2.6 and RCP8.5) indicated that the hotspots would obviously move northward. These findings will serve effectively the fishery resources monitoring, management, and evaluation of small yellow croaker in the China Seas.

Modeling-Based Multiscale Deep Prospectivity Mapping: A Case Study of the Haoyaoerhudong Gold Deposit, Inner Mongolia, China - Nan Li; Rui Cao; HuiShou Ye; Qiang Li; Yitian Wang; Xiping Lv; Na Guo; Yuanxiang Su; Jianrui Hao; Shitao Yin; Wenkai Chu (Natural Resources Research, 2022)

Influence of different inoculation densities of black soldier fly larvae (Hermetia illucens) on heavy metal immobilization in swine manure - Dongmei Jiang; Kunhong Jiang; Rui Li; Liangbin Zhao; Zile Liu; Bangjie Xiong; Du Jin; Xiaoxia Hao; Li Zhu; Bo Kang; Lin Bai (Environmental Science and Pollution Research, 2022)

Detection and typing of dengue virus by one-step RT-PCR-based high-resolution melting assay - Rui Tian; Hao Yan; Yang Jiang; Aiping Wu; Ling Li; Zhangnv Yang; Kuangming Yu (Virus Genes, 2022)

Belowground processes and sustainability in agroecosystems with intercropping - Rui-Peng Yu; Hao Yang; Yi Xing; Wei-Ping Zhang; Hans Lambers; Long Li (Plant and Soil, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Bionic study of the cushioning and energy-saving joints of leg of the walking robot - Rui Zhang; Wenchao Dong; Lujiang Liu; Xuemei Ju; Hao Pang; Qingqiu Cao; Lige Wen (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)

Toxicities of nanomaterials and metals to rice under low atmospheric pressure - Kerui Guo; Dongheng Fu; Muhammed Adeel; Yunze Shen; Kexiang Wang; Yi Hao; Tonghao Bai; Yaoyao Wang; Yukui Rui (Acta Physiologiae Plantarum, 2022)

Toxic encephalopathy induced by radix Sophorae tonkinensis - Xue-Lin Li; Hao-Tian Zhao; Jinming Han; Zhong-Rui Yan; Hai-Yang Wang (Acta Neurologica Belgica, 2022)

Two new cytotoxic cycloartane triterpenoids from Aphanamixis polystachya (Wall.) R. N. Parker - Yi-ting Wang; Shi-rui Fan; Jie-yun Cai; Jing-jing Guo; Xin-fang Zhang; Bi-juan Yang; Xiao-jiang Hao; Duo-zhi Chen (Natural Product Research, 2022)

Laboratory and centrifugal model tests on failure mechanism of canal slopes under cyclic action of wetting–drying - Rui Zhu; Ying-hao Huang; Chen Zhang; Wan-li Guo; Hao Chen (European Journal of Environmental and Civil Engineering, 2022)

TRIP13 knockdown inhibits the proliferation, migration, invasion, and promotes apoptosis by suppressing PI3K/AKT signaling pathway in U2OS cells - De-Chen Yu; Xiang-Yi Chen; Hai-Yu Zhou; De-Quan Yu; Xiao-Lei Yu; Yi-Cun Hu; Rui-Hao Zhang; Xiao-Bo Zhang; Kun Zhang; Mao-Qiang Lin; Xi-Dan Gao; Tao-Wen Guo (Molecular Biology Reports, 2022)

Correction to: Desiccation cracking in clay‑bottom ash mixtures: insights from crack image analysis and digital image correlation - Rui Liu; Mark Vail; Behrad Koohbor; Cheng Zhu; Chao‑Sheng Tang; Hao Xu; Xiang‑Chao Shi (Bulletin of Engineering Geology and the Environment, 2022)

Desiccation cracking in clay-bottom ash mixtures: insights from crack image analysis and digital image correlation - Rui Liu; Mark Vail; Behrad Koohbor; Cheng Zhu; Chao-Sheng Tang; Hao Xu; Xiang-Chao Shi (Bulletin of Engineering Geology and the Environment, 2022)

Experimental study on the mechanical properties and energy evolution of hard rock during water immersion - Fan-Bo Wei; Bing-Rui Chen; Rui Wang; Guo-Liang Li; Tao Li; Xu Wang; Xin-Hao Zhu (Arabian Journal of Geosciences, 2022)

Identification and Expression Analysis of the SBP-box Gene Family Related to Abiotic Stress in Tea Plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Hao Liu; Yu Wang; Jing Zhuang (Plant Molecular Biology Reporter, 2022)

Physiological Responses of Ribosomal Protein S12 K43 Mutants of Corynebacterium glutamicum - Guihong Zhao; Rui Su; Meng Yuan; Hongkun Ma; Taidong Bo; Hao Jiang; Chen Wu; Yanjun Li (Current Microbiology, 2022)

Epigallocatechin‐3‐gallate inhibits replication of white spot syndrome virus in the freshwater crayfish Procambarus clarkii - Yitong Zhang; Jinxuan Wen; Yao Xu; Hao Wang; Liqun Lu; Rui Song; Jixing Zou (Journal of Fish Diseases, 2022)
The freshwater crayfish Procambarus clarkii is native to North America and Mexico, and it was introduced to China in 1929. The production and consumption of P. clarkii in China are the highest worldwide, reaching 208.96 million tons in 2020. The white spot syndrome virus (WSSV) is a major pathogen that affects shrimp, crayfish, crabs and lobsters, and it has caused widespread loss to the P. clarkii industry. Epigallocatechin‐3‐gallate (EGCG), a small‐molecule compound, has a multitude of biological functions and the ability to bind to the 37 kDa/67 kDa laminin receptor ( LamR ). EGCG has potential antiviral effects against WSSV. In this study, we evaluated the potential anti‐WSSV applications of EGCG in P. clarkii . We demonstrated that various concentrations (10 μg/g·bw, 20 μg/g·bw and 40 μg/g·bw) of EGCG can suppress WSSV infection in P. clarkii . Histopathological examination revealed no characteristic pathological changes due to EGCG administration in P. clarkii tissues. Furthermore, pharmacokinetics studies of EGCG in P. clarkii revealed its rapid absorption (T max = 2 h), and the peak concentrations of EGCG were 73.78 µg/g in the liver and 24.87 µg/g in the muscle. Our results indicate the high potential applications of EGCG against WSSV in P. clarkii .

Microseismic Monitoring of Rock Mass Fracture Response to Blasting Excavation of Large Underground Caverns Under High Geostress - Jin-Shuai Zhao; Bing-Rui Chen; Quan Jiang; Jian-Fei Lu; Xian-Jie Hao; Shu-Feng Pei; Fei Wang (Rock Mechanics and Rock Engineering, 2022)

Spermatogonia From Cryopreserved Testes of Critically Endangered Chinese Sturgeon Efficiently Colonized and Preferentially Proliferated in the Recipient Gonads of Yangtze Sturgeon - Huan Ye; Yutaka Takeuchi; Hao Du; Huamei Yue; Rui Ruan; Chuangju Li; Qiwei Wei (Marine Biotechnology, 2022)

Two new threonine-containing metabolites from fungus Curvularia inaequalis strain HS-FG-257 - Shao-Yong Zhang; Jian-Song Li; Hui Zhang; Huan Qi; Rui-Jun Wang; Chou-Fei Wu; Li-Qin Zhang; An-Liang Chen; Ji-Dong Wang; Zhi-Kui Hao (Natural Product Research, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Serine protease HtrA2/Omi regulates adaptive mitochondrial reprogramming in the brain cortex after ischemia/reperfusion injury via UCP2-SIRT3-PGC1 axis - Hao Meng; Lian-Kun Sun; Jing Su; Wan-Yu Yan; Yao Jin; Xin Luo; Xian-Rui Jiang; Hong-Lei Wang (Human Cell, 2022)

Bmi1 Regulates Wnt Signaling in Hematopoietic Stem and Progenitor Cells - Hao Yu; Rui Gao; Sisi Chen; Xicheng Liu; Qiang Wang; Wenjie Cai; Sasidhar Vemula; Aidan C. Fahey; Danielle Henley; Michihiro Kobayashi; Stephen Z. Liu; Zhijian Qian; et al. (Stem Cell Reviews and Reports, 2021)

Risk assessment of non-point source pollution based on landscape pattern in the Hanjiang River basin, China - Yi-wen Liu; Jia-ke Li; Jun Xia; Gai-rui Hao; Fang-Yenn Teo (Environmental Science and Pollution Research, 2021)

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

The effect of maternal seafood consumption on perinatal outcomes: a systematic review and dose-response meta-analysis - Rui Zhao; Qin Gao; Shanshan Wang; Xuefeng Yang; Liping Hao (Critical Reviews in Food Science and Nutrition, 2021)

Loganin ameliorates depression-like behaviors of mice via modulation of serotoninergic system - Chen-Hao Pan; Cong-Yuan Xia; Yu Yan; Yan Han; Rui Shi; Jun He; Ze-Xing Wang; Yu-Ming Wang; Wei-Ku Zhang; Jie-Kun Xu (Psychopharmacology, 2021)

Associations between air pollution exposure and birth defects: a time series analysis - Shu Sun; Qi Zhang; Xinmiao Sui; Liu Ding; Jie Liu; Mei Yang; Qihong Zhao; Chao Zhang; Jiahu Hao; Xiujun Zhang; Shilei Lin; Rui Ding; et al. (Environmental Geochemistry and Health, 2021)

Microseismic source location method based on a velocity model database and statistical analysis - Bing-Rui Chen; Tao Li; Xin-Hao Zhu; Fan-Bo Wei; Xu Wang; Ming-Xing Xie (Arabian Journal of Geosciences, 2021)

Ectobacillus aegiceratis sp. nov., a novel bacterium isolated from branch of Aegiceras corniculatum - Xiao-Hui Chen; Xiao-Rui Yan; Zi-Hao Huang; Ming-Sheng Chen; Li Tuo (Antonie van Leeuwenhoek, 2021)

Jiella mangrovi sp. nov., a novel endophytic bacterium isolated from leaf of Rhizophora stylosa - Ming-Sheng Chen; Fei-Na Li; Xiao-Hui Chen; Zi-Hao Huang; Xiao-Rui Yan; Li Tuo (Antonie van Leeuwenhoek, 2021)

Light and high-strength structure inspired by the characteristics of double-nutrient foramens in intertarsal joint of ostrich - Rui Zhang; Chengjin Wang; Shichao Fan; Dong Li; Hao Pang; Lei Ling; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Silurian to early Permian slab melting and crustal growth in the southern Altaids: insights from adakites and associated mineral deposits in the Dananhu arc, Eastern Tianshan, NW China - Qigui Mao; Songjian Ao; Dongfang Song; Wenjiao Xiao; Brian F. Windley; Miao Sang; Zhou Tan; Hao Wang; Rui Li (International Journal of Earth Sciences, 2021)

The Water Resisting Properties of the Top Portion of the Ordovician Limestone Aquifer in the North China Coalfield - Hao Wang; Shuning Dong; Rui Chai; Wei Qiao; Jian Yang; Ji Liu; Linsheng Zhou; Zhenfang Zhou; Zhaoxing Liu; Hongbo Shang (Mine Water and the Environment, 2021)

Phycicoccus avicenniae sp. nov., a novel endophytic actinomycete isolated from a branch of Avicennia mariana - Ming-Sheng Chen; Xiao-Hui Chen; Zi-Hao Huang; Xiao-Rui Yan; Li Tuo (Antonie van Leeuwenhoek, 2021)

Tracing Nutrients and Organic Matter Changes in Eutrophic Wenchang (China) and Oligotrophic Krka (Croatia) Estuaries: A Comparative Study - You-You Hao; Zhuo-Yi Zhu; Fu-Tao Fang; Tihana Novak; Milan Čanković; Enis Hrustić; Zrinka Ljubešić; Ming Li; Jin-Zhou Du; Rui-Feng Zhang; Blaženka Gašparović (Frontiers in Marine Science, 2021)
Estuaries modify the concentration and composition of riverine nutrients and organic matter (OM), which eventually determine the riverine flux effect to coasts. Nutrients, organic carbon (OC), pigments, and amino acids (AAs) from the samples collected in the eutrophic Wenchang River Estuary (WRE) in China and the oligotrophic Krka River Estuary (KRE) in Croatia were analyzed in order to have a better understanding of how estuaries regulate terrestrial materials. We found a clear increase of dissolved inorganic nitrogen (DIN) concentration and its subsequent decrease due to the removal of DIN (over 100 μM) in the WRE, whereas DIN showed minor variation lengthwise in the KRE, i.e., with the salinity changes, ranging between 1.0 and 5.8 μM. The elevated algae-derived OC, dissolved organic nitrogen, and particulate AAs nitrogen suggest that the OM assimilation may explain approximately one-third of the DIN removal in the WRE, whereas in the oligotrophic KRE, such inorganic to organic transformation is not likely to be significant. Due to the prominent estuarine nitrogen removal/assimilation process, DIN/dissolved inorganic phosphorus (DIP) ratio was as high as 425 in the upper WRE under strong riverine influence, but it declined to as low as 5.4 at the mouth of WRE, that is even lower than DIN/DIP ratio at the mouth of oligotrophic KRE (12). When compared with other rivers worldwide, the Wenchang River showed high nutrients and organic carbon yields. Given the contrasting estuarine process (e.g., DIN removal) between the KRE and the WRE, apparent high nutrient yield from eutrophic rivers should be viewed with caution in ocean studies as the final impact to coastal zone could be similar to the oligotrophic rivers like the KRE.

Insights into heat response mechanisms in Clematis species: physiological analysis, expression profiles and function verification - Hao Zhang; Changhua Jiang; Rui Wang; Long Zhang; Ruonan Gai; Siyuan Peng; Yi Zhang; Chanjuan Mao; Yuxia Lou; Jianbin Mo; Shucheng Feng; Feng Ming (Plant Molecular Biology, 2021)

Overexpression of MdPHR1 Enhanced Tolerance to Phosphorus Deficiency by Increasing MdPAP10 Transcription in Apple (Malus × Domestica) - Rui Li; Jian-Ping An; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Journal of Plant Growth Regulation, 2021)

A new dineolignan with anti- β -amyloid aggregation activity from the fruits of crataegus pinnatifida bge - Peng Zhao; Li-Li Lou; Hao Zhang; Rui Guo; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2021)

3D DEM analysis on tractive trafficability of a lunar rover wheel with bionic wheel lugs - Hao Pang; Rui Zhang; Ping Ge; Fang Liu; Chengjin Wang; Wenchao Dong; Tao Li; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Discussion on Some Topical Issues of Water Prevention and Control in Coal Mines - Shuning Dong; Wenzhong Zhang; Wanfang Zhou; Rui Chai; Hao Wang; Chunhu Zhao; Xingling Dong; Qiangmin Wang (Mine Water and the Environment, 2021)

Different physiological responses of C3 and C4 plants to nanomaterials - Tonghao Bai; Peng Zhang; Zhiling Guo; Andrew J. Chetwynd; Mei Zhang; Muhammad Adeel; Mingshu Li; Kerui Guo; Ruize Gao; Jianwei Li; Yi Hao; Yukui Rui (Environmental Science and Pollution Research, 2021)

Graphitic carbon nitride (g-C3N4) alleviates cadmium-induced phytotoxicity to rice (Oryza sativa L.) - Yi Hao; Ruitao Lv; Chuanxin Ma; Muhammad Adeel; Ziqian Zhao; Yuhang Rao; Yukui Rui (Environmental Science and Pollution Research, 2021)

Ruegeria haliotis sp. nov., Isolated from the Gut of the Abalone Haliotis rubra - Wen-Rui Cao; Dan-Dan Shang; Bang-Tao Liu; Yi-Hao Hu; Xun-Ke Sun; Yuan-Yuan Sun; Ming-Yu Jiang; Zong-Jun Du (Current Microbiology, 2021)

Design of the bionic wheel surface based on the friction characteristics of ostrich planta - Hao Pang; Hua Zhang; Rui Zhang; Wenchao Dong; Tao Li; Songsong Ma; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Protective equipment and health education program could benefit students from dust pollution - Yi-Chen Chiang; Xian Li; Chun-Yang Lee; Jia Rui; Chiung-Wen Hu; Hao-Jan Yang; Szu-Chieh Chen; Tianmu Chen; Yanhua Su; Chung-Yih Kuo; Shao-Chieh Hsueh (Air Quality, Atmosphere & Health, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Ca2+/Calmodulin-NOS/NO-TNFs Pathway Hallmarks the Inflammation Response of Oyster During Aerial Exposure - Hao Chen; Lusheng Xin; Lin Wang; Huan Zhang; Rui Liu; Hao Wang; Xue Qiao; Lingling Wang; Linsheng Song (Frontiers in Marine Science, 2021)
Aerial exposure (emersion) due to the periodical ebb and flow of tides is a major stressor for intertidal organisms and a key environmental factor in shaping their local communities. Oysters are among the most emersion-tolerant mollusk species and can survive for several days under aerial exposure. Noticeably, overwhelming inflammation responses could occur during the emersion stress. However, mechanisms beneath the activation and modulation of emersion-induced inflammation response have remained largely unknown. Ca 2+ is an important intracellular second messenger that plays indispensable roles in inflammation response by cooperation with calmodulin (CaM) genes. Here, we showed that intracellular Ca 2+ accumulates rapidly in oyster hemocytes during emersion stress along with the changes in the protein levels of three CaM genes, which function as intracellular sensors of Ca 2+ . As downstream effector of Ca 2+ /CaM complex, nitric oxide synthase (NOS) activity in hemocytes was enhanced during the emersion stress, facilitating a greater production of nitrite oxide (NO). Augmentation of NO concentration was associated with the increased mRNA expression levels of two oyster cytokines (CgTNFs) during aerial exposure. The robust accumulation of cytokines and severe injury of tissues in oysters have been regarded as potential cause and marker of their death in prolonged emersion stress. Here, both the expression levels of CgTNFs and the tissue injuries of oysters were attenuated when Ca 2+ /CaM complex or NOS activity were repressed in vivo during the emersion stress. These findings indicate that Ca 2+ /CaM-NOS/NO-CgTNFs pathway is critically involved in the emersion-induced inflammation response in oysters and plays a role in the resistance against long-term aerial exposure.

Partial recovery of disturbed V-J pairing profiles of T-cell receptor in people living with HIV receiving long-term antiretroviral therapy - Guoli Li; Jiarui Li; Henghui Zhang; Yu Zhang; Di Liu; Yu Hao; Junyan Han; Juan Du; Liuluan Zhu; Yongqin Zeng; Bei Li; Rui Li; et al. (Science China Life Sciences, 2021)

Identification and expression analysis of caffeoyl-coenzyme A O-methyltransferase family genes related to lignin biosynthesis in tea plant (Camellia sinensis) - Shi-Jia Lin; Ya-Zhuo Yang; Rui-Min Teng; Hao Liu; Hui Li; Jing Zhuang (Protoplasma, 2021)

Effects of shading on lignin biosynthesis in the leaf of tea plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Shi-Jia Lin; Hao Liu; Jing Zhuang (Molecular Genetics and Genomics, 2021)

Two new bioactive lignans from leaves and twigs of Cleistanthus concinnus Croizat - Shi-rui Fan; Jing-jing Guo; Yi-ting Wang; Bi-juan Yang; Duo-zhi Chen; Xiao-jiang Hao (Natural Product Research, 2020)

Graph-based network analysis of resting-state fMRI: test-retest reliability of binarized and weighted networks - Jie Xiang; Jiayue Xue; Hao Guo; Dandan Li; Xiaohong Cui; Yan Niu; Ting Yan; Rui Cao; Yao Ma; Yanli Yang; Bin Wang (Brain Imaging and Behavior, 2020)

Role of the C9ORF72 Gene in the Pathogenesis of Amyotrophic Lateral Sclerosis and Frontotemporal Dementia - Zongbing Hao; Rui Wang; Haigang Ren; Guanghui Wang (Neuroscience Bulletin, 2020)

The study on loess liquefaction in China: a systematic review - Siyue He; Xiuling Wang; Haobo Fan; Hao Wang; Rui Ren; Chunxia Guo (Natural Hazards, 2020)

Quantitative assessment of non-point source pollution load of PN/PP based on RUSLE model: a case study in Beiluo River Basin in China - Gai-rui Hao; Jia-ke Li; Shu Li; Kang-bin Li; Zi-hang Zhang; Huai-en Li (Environmental Science and Pollution Research, 2020)

Bioaccumulation of ytterbium oxide nanoparticles insinuate oxidative stress, inflammatory, and pathological lesions in ICR mice - Muhammad Adeel; Jin Tingting; Tariq Hussain; Xiao He; Muhammad Arslan Ahmad; Muhammad Kashif Irshad; Noman Shakoor; Peng Zhang; Xie Changjian; Yi Hao; Zhang Zhiyong; Rabia Javed; et al. (Environmental Science and Pollution Research, 2020)

Reconstructing the 3D digital core with a fully convolutional neural network - Qiong Li; Zheng Chen; Jian-Jun He; Si-Yu Hao; Rui Wang; Hao-Tao Yang; Hua-Jun Sun (Applied Geophysics, 2020)

Role of Chromatin Remodeling Genes and TETs in the Development of Human Midbrain Dopaminergic Neurons - Li Xiang; Guobin Huang; Wenjing Shu; Chunli Gong; Nan Cao; Rui Chen; Jixi Li; Hao Lu; Gaofeng Jiang (Stem Cell Reviews and Reports, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Distribution and risk of mercury in the sediments of mangroves along South China Coast - Rui-Fei Ma; Hao Cheng; Aniefiok Inyang; Ming Wang; You-Shao Wang (Ecotoxicology, 2020)

An artificial target detection method combining a polarimetric feature extractor with deep convolutional neural networks - Rui Sun; Xiaobing Sun; Feinan Chen; Hao Pan; Qiang Song (International Journal of Remote Sensing, 2020)

Candidate proteins involved in the calyx abscission process of ‘Kuerlexiangli’ (Pyrus sinkiangensis Yu) identified by iTRAQ analysis - Xin Gong; Jianping Bao; Jing Chen; Kaijie Qi; Zhihua Xie; Weikang Rui; Guowei Hao; Katsuhiro Shiratake; Shahrokh Khanizadeh; Shaoling Zhang; Shutian Tao (Acta Physiologiae Plantarum, 2020)

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Effects of different NO3−:NH4+ ratios on the photosynthesis and ultrastructure of lettuce seedlings - Xu Zhu; Rui Yang; Yingyan Han; Jinghong Hao; Chaojie Liu; Shuangxi Fan (Horticulture, Environment, and Biotechnology, 2020)

Clinical strategies for differentiating IgG4-related cholecystitis from gallbladder carcinoma to avoid unnecessary surgical resection - Rui Zhang; Hao-Ming Lin; Zhao-Xi Cai; Su-Juan Du; Hong Zeng; Lei-Bo Xu; Jie Wang; Chao Liu (Science China Life Sciences, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Design of the Key Bearing Layer and Secondary Mining Technology for Previously Mined Areas of Small Coal Mines - Rui Wu; P. H. S. W. Kulatilake; Hao Luo; Kui Zhao (Rock Mechanics and Rock Engineering, 2020)

Plasma Endostatin Levels at Acute Phase of Ischemic Stroke Are Associated with Post-Stroke Cognitive Impairment - Sifan Qian; Ruyi Li; Chenhuan Zhang; Rui Zhang; Daoxia Guo; Xiaoqing Bu; Aili Wang; Hao Peng; Jing Chen; Yonghong Zhang; Jiang He; Tan Xu; et al. (Neurotoxicity Research, 2020)

Bionic design in anti-bending and lightweight tube based on the tarsometatarsus of ostrich - Rui Zhang; Hao Pang; Dianlei Han; Shuliang Xue; Lei Jiang; Dong Li; Lige Wen; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2020)

Molecular cloning and functional characterization of the CEP RECEPTOR 1 gene MdCEPR1 of Apple (Malus × domestica) - Rui Li; Jian-Ping An; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

The stability and pressure behavior characteristics of a special L-type face end formed by low-pressure mining technology without pre-driving roadway - Ya-jun Wang; Jun Yang; Man-chao He; Rui-feng Huang; Xi-chun Tian; Jian-ning Liu; Hao-jie Xue (Arabian Journal of Geosciences, 2020)

The giant Zaozigou Au-Sb deposit in West Qinling, China: magmatic- or metamorphic-hydrothermal origin? - Kun-Feng Qiu; Hao-Cheng Yu; Jun Deng; Duncan McIntire; Zong-Yang Gou; Jian-Zhen Geng; Zhao-Shan Chang; Rui Zhu; Kang-Ning Li; Richard Goldfarb (Mineralium Deposita, 2020)

Interaction between CA repeat microsatellites and HIF1α regulated the transcriptional activity of porcine IGF1 promoter - Hongwei Geng; Linlin Hao; Yunyun Cheng; Chunli Wang; Shan Huang; Wenzhen Wei; Rui Yang; Haoyang Li; Songcai Liu; Hao Yu; Huayi Lu (Journal of Applied Genetics, 2020)

PDGFRβ-targeted TRAIL specifically induces apoptosis of activated hepatic stellate cells and ameliorates liver fibrosis - Rui Li; Zhao Li; Yanru Feng; Hao Yang; Qiuxiao Shi; Ze Tao; Jingqiu Cheng; Xiaofeng Lu (Apoptosis, 2020)

Improvement and application research of the SRM in alpine regions - Gai-rui Hao; Jia-ke Li; Kang-bin Li; Kang Huang; Jia-bao Song; Huai-en Li (Environmental Science and Pollution Research, 2019)

Evaluation of Liquefaction Potential in Saturated Sand under Different Drainage Boundary Conditions—An Energy Approach - Chang-Rui Yao; Bo Wang; Zhi-Qiang Liu; Hao Fan; Fang-Hao Sun; Xin-Hao Chang (Journal of Marine Science and Engineering, 2019)
Drainage conditions are supposed to have significant influence on sand liquefaction behavior. An infiltration device was utilized in cyclic triaxial tests to reproduce different drainage conditions by altering dry density of the within silt. Permeability coefficient ratio (kp) was utilized for quantifying the drainage boundary effect. Cyclic triaxial tests were conducted on saturated Fujian standard sand samples. Test results were used to evaluate the liquefaction potential by using the energy approach. It can be concluded that, if kp increases slightly bigger than zero, excess pore water pressure (EPWP) will respond more fiercely, and the dissipated energy that triggers sand liquefaction will be less. By considering kp, an energy-based database was built by taking kp into consideration and different neural network (NN) models were constructed to predict liquefaction potential by energy approaches accurately under different drainage boundary conditions. It was suggested that the neuro-fuzzy (NF)-based NN model has more satisfactory performance.

The basolateral amygdala regulation of complex cognitive behaviours in the five-choice serial reaction time task - Fangyuan Yin; Hao Guo; Jingjing Cui; Yuhui Shi; Rui Su; Qiaoli Xie; Jinrui Chang; Yunpeng Wang; Jianghua Lai (Psychopharmacology, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Design and Experiment of a Plateau Data-Gathering AUV - Hao Xu; Guo-Cheng Zhang; Yu-Shan Sun; Shuo Pang; Xiang-Rui Ran; Xiang-Bin Wang (Journal of Marine Science and Engineering, 2019)
The design, control, and implementation of an autonomous underwater vehicle (AUV) for collecting hydrological information from plateau rivers and lakes are presented in this paper. The hardware and software structures of the control system were previously described. A novel sliding mode controller (SMC) with combinational reaching law of vertical hovering motion is proposed to improve the robustness and stability. The S-plane control, a nonlinear controller with little parameters, is used in the horizontal motion. Besides, the navigation strategy based on the dead-reckoning algorithm, a path tracking based on the light-of-sight (LOS) algorithm, and a control allocation strategy considering saturation are present. Finally, experiments were performed in a tank and in a river in the Qinghai–Tibet Plateau to prove the feasibility and reliability of the AUV system.

Poly-PR in C9ORF72-Related Amyotrophic Lateral Sclerosis/Frontotemporal Dementia Causes Neurotoxicity by Clathrin-Dependent Endocytosis - Rui Wang; Xingyun Xu; Zongbing Hao; Shun Zhang; Dan Wu; Hongyang Sun; Chenchen Mu; Haigang Ren; Guanghui Wang (Neuroscience Bulletin, 2019)

Effects of exogenous putrescine on the ultrastructure of and calcium ion flow rate in lettuce leaf epidermal cells under drought stress - Xu Zhu; Lin Wang; Rui Yang; Yingyan Han; Jinghong Hao; Chaojie Liu; Shuangxi Fan (Horticulture, Environment, and Biotechnology, 2019)

Relationship between stand characteristics and soil properties of two typical forest plantations in the mountainous area of Western Sichuan, China - Hao Yang; Ning Miao; Shao-cai Li; Rui Ma; Zi-yan Liao; Wei-ping Wang; Hai-long Sun (Journal of Mountain Science, 2019)

Downregulation of AIF-2 Inhibits Proliferation, Migration, and Invasion of Human Glioma Cells via Mitochondrial Dysfunction - Wei Chen; Hao Liu; Tuo Wang; Gang Bao; Ning Wang; Rui-Chun Li (Journal of Molecular Neuroscience, 2019)

A miR-511-binding site SNP in the 3′UTR of IGF-1 gene is associated with proliferation and apoptosis of PK-15 cells - Wenzhen Wei; Gang Wang; Yunyun Cheng; Rui Yang; Jie Song; Shan Huang; Haoyang Li; Hongwei Geng; Hao Yu; Songcai Liu; Linlin Hao (In Vitro Cellular & Developmental Biology - Animal, 2019)

Antioxidant defense against rust infection in the leaf tissue of Malus crabapple - Yudan Duan; Suxiao Hao; Rui Luo; Yanfen Lu; Ge Li; Jie Zhang; Ji Tian; Yuncong Yao (Acta Physiologiae Plantarum, 2019)

Pine needles as biomonitors of polybrominated diphenyl ethers and emerging flame retardants in the atmosphere of Shanghai, China: occurrence, spatial distributions, and possible sources - Hao-Hao Jia; Xue-Tong Wang; Hang-Xin Cheng; Ying Zhou; Rui Fu (Environmental Science and Pollution Research, 2019)

QsvR integrates into quorum sensing circuit to control Vibrio parahaemolyticus virulence - Yiquan Zhang; Linghui Hu; Yue Qiu; George Osei‐Adjei; Hao Tang; Ying Zhang; Rui Zhang; Xiumei Sheng; Shungao Xu; Wenhui Yang; Huiying Yang; Zhe Yin; et al. (Environmental Microbiology, 2019)
Summary Vibrio parahaemolyticus , the leading cause of seafood‐associated gastroenteritis worldwide, requires the two type‐III secretion systems (T3SS1 and T3SS2) and a thermostable direct hemolysin (encoded by tdh1 and tdh2 ) for full virulence. The tdh genes and the T3SS2 gene cluster constitute an 80 kb pathogenicity island known as Vp‐PAI located on the chromosome II. Expression of T3SS1 and Vp‐PAI is regulated in a quorum sensing (QS)‐dependent manner but its detailed mechanisms remain unknown. Herein, we show that three factors (QS regulators AphA and OpaR and an AraC‐type transcriptional regulator QsvR) form a complex regulatory network to control the expression of T3SS1 and Vp‐PAI genes. At low cell density (LCD), whereas Vp‐PAI expression is repressed, T3SS1 genes are induced by AphA, which directly binds (an operator region of) the exsBAD‐vscBCD operon. At high cell density (HCD), the bacterium turns off T3SS1 expression by replacing AphA with OpaR, triggering the induction of Vp‐PAI. Furthermore, QsvR binds to the regulatory regions of all the tested T3SS1 and Vp‐PAI genes to activate their transcription at HCD. Taken together, our data highlight how multiple QS regulators contribute to the pathogenicity of V. parahaemolyticus by precisely controlling the expression of major virulence determinants during different stages of growth.

The role of lamin A/C in mesenchymal stem cell differentiation - Bo Zhang; Yang Yang; Reziwan Keyimu; Jin Hao; Zhihe Zhao; Rui Ye (Journal of Physiology and Biochemistry, 2019)

Multi-year assessment of paralytic shellfish toxins in hard clam species along the coastline of Jiangsu Province, China - Xinzhi Wang; Hao Wu; Ying Cheng; Hongmei Wen; Rui Liu; Libao Wang; Chenxiao Shan; Chuan Chai (Acta Oceanologica Sinica, 2019)

Natural and synthetic estrogens in leafy vegetable and their risk associated to human health - Muhammad Adeel; Muhammad Zain; Shah Fahad; Muhammad Rizwan; Asif Ameen; Hao Yi; Mansoor A. Baluch; Jie Yinn Lee; Yukui Rui (Environmental Science and Pollution Research, 2018)

Characterization of clinical features and outcome for human-to-human transmitted severe fever with thrombocytopenia syndrome - Bei Jia; Weihua Wu; Rui Huang; Guiyang Wang; Peixin Song; Yang Li; Yong Liu; Yali Xiong; Xiaomin Yan; Yingying Hao; Juan Xia; Zhaoping Zhang; et al. (Infectious Diseases, 2018)

Genome-wide analysis and identification of the SMXL gene family in apple (Malus × domestica) - Rui Li; Jian-Ping An; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Tree Genetics & Genomes, 2018)

Specific effects of neuregulin-1β on the communication between DRG neurons and skeletal muscle cells in vitro - Menglin Cong; Jianmin Li; Yuan Qiao; Rui Jing; Hao Li; Zhenzhong Li (Journal of Muscle Research and Cell Motility, 2018)

The health hazards of potentially toxic metals in the daily diets of adults and children from a mining and smelting region (Hezhang County) in southwestern China - Mengmeng Shao; Yi Zhu; Rui Hao; Zhen Yu; Minghan Song (Environmental Monitoring and Assessment, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

The gravity field model IGGT_R1 based on the second invariant of the GOCE gravitational gradient tensor - Biao Lu; Zhicai Luo; Bo Zhong; Hao Zhou; Frank Flechtner; Christoph Förste; Franz Barthelmes; Rui Zhou (Journal of Geodesy, 2018)

Effects of diurnal temperature range on mortality in Hefei city, China - Jing Tang; Chang-chun Xiao; Yu-rong Li; Jun-qing Zhang; Hao-yuan Zhai; Xi-ya Geng; Rui Ding; Jin-xia Zhai (International Journal of Biometeorology, 2018)

Porosity model and air leakage flow field simulation of goaf based on DEM-CFD - Gang Wang; Hao Xu; Mengmeng Wu; Yue Wang; Rui Wang; Xiaoqiang Zhang (Arabian Journal of Geosciences, 2018)

Screening HCV genotype-specific epitope peptides based on conserved sequence analysis and B cell epitope prediction in HCV E2 region - Rui Hua; Xiaoyu Jiang; Lingxia Qi; Shanshan Guan; Ziyu Kuai; Yongbo Qiao; Yan Xu; Xin Gong; Yuhua Shi; Wei Kong; Junqi Niu; Hao Zhang; et al. (Immunologic Research, 2018)

Nature and origin of Triassic igneous activity in the Western Qinling Orogen: the Wenquan composite pluton example - Kun-Feng Qiu; Hao-Cheng Yu; Zong-Yang Gou; Zhi-Lu Liang; Jia-Lin Zhang; Rui Zhu (International Geology Review, 2018)

Precipitation drives the biogeographic distribution of soil fungal community in Inner Mongolian temperate grasslands - Di Wang; Yichao Rui; Kai Ding; Xiaoyong Cui; Yanbin Hao; Li Tang; Zhe Pang; Biao Zhang; Shutong Zhou; Kui Wang; Yanfen Wang (Journal of Soils and Sediments, 2018)

Profiling methyl jasmonate-responsive transcriptome for understanding induced systemic resistance in whitebark pine (Pinus albicaulis) - Jun-Jun Liu; Holly Williams; Xiao Rui Li; Anna W. Schoettle; Richard A. Sniezko; Michael Murray; Arezoo Zamany; Gary Roke; Hao Chen (Plant Molecular Biology, 2017)

Identification of the SRO gene family in apples (Malus×domestica) with a functional characterization of MdRCD1 - Haohao Li; Rui Li; Fengjia Qu; Jifang Yao; Yujin Hao; Xiaofei Wang; Chunxiang You (Tree Genetics & Genomes, 2017)

An anther-specific gene PhGRP is regulated by PhMYC2 and causes male sterility when overexpressed in petunia anthers - Yuanzheng Yue; Chaoqun Yin; Rui Guo; Hao Peng; Zhaonan Yang; Guofeng Liu; Manzhu Bao; Huirong Hu (Plant Cell Reports, 2017)

Memantine Can Reduce Ethanol-Induced Caspase-3 Activity and Apoptosis in H4 Cells by Decreasing Intracellular Calcium - Xiaolong Wang; Jiajun Chen; Hongbo Wang; Hao Yu; Changliang Wang; Jiabin You; Pengfei Wang; Chunmei Feng; Guohui Xu; Xu Wu; Rui Zhao; Guohua Zhang (Journal of Molecular Neuroscience, 2017)

Characterization of angiotensin-І converting enzyme inhibiting peptide from Venerupis philippinarum with nano-liquid chromatography in combination with orbitrap mass spectrum detection and molecular docking - Lei Shi; Tizhi Wu; Naijuan Sheng; Li Yang; Qian Wang; Rui Liu; Hao Wu (Journal of Ocean University of China, 2017)

Tissue and cell-type co-expression networks of transcription factors and wood component genes in Populus trichocarpa - Rui Shi; Jack P. Wang; Ying-Chung Lin; Quanzi Li; Ying-Hsuan Sun; Hao Chen; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2017)

Intelligent diagnosis of jaundice with dynamic uncertain causality graph model - Shao-rui Hao; Shi-chao Geng; Lin-xiao Fan; Jia-jia Chen; Qin Zhang; Lan-juan Li (Journal of Zhejiang University-SCIENCE B, 2017)

Proteomic Analysis of Phloem Proteins Leads to the Identification of Potential Candidates for JA-Mediated RKN-Resistant Elements in Solanum lycopersicum - Wenchao Zhao; Jinghong Hao; Jiayi Xing; Rui Yang; Fukuan Zhao; Jianli Wang; Shaohui Wang (Journal of Plant Growth Regulation, 2017)

Efficient Generation of Functionally Active Spinal Cord Neurons from Spermatogonial Stem Cells - Hao Yang; Cuicui Liu; Bo Chen; Jing An; Rui Zhang; Qian Zhang; Jingjing Zhao; Baorong He; Ding-Jun Hao (Molecular Neurobiology, 2017)

Frequency and type of inheritable mutations induced by γ rays in rice as revealed by whole genome sequencing - Shan Li; Yun-chao Zheng; Hai-rui Cui; Hao-wei Fu; Qing-yao Shu; Jian-zhong Huang (Journal of Zhejiang University-SCIENCE B, 2016)

Evaluation of serum immunoglobulins concentrations and distributions in vitiligo patients - Yulong Li; Min Yang; Rui Zhang; Wan Liu; Kuo Zhang; Wei Wen; Lang Yi; Qiaoxian Wang; Mingju Hao; Hui Yang; Jianmin Chang; Jinming Li (Immunologic Research, 2016)

A Novel PhLRR Gene Promoter is Sufficient for Engineering Male Sterility in Petunia - Yuanzheng Yue; Di Yang; Jian Sun; Hao Peng; Chaoqun Yin; Rui Guo; Guogui Ning; Huirong Hu (Plant Molecular Biology Reporter, 2016)

Mitochondrial DNA Haplogroup A Decreases the Risk of Drug Addiction but Conversely Increases the Risk of HIV-1 Infection in Chinese Addicts - A-Mei Zhang; Qiu-Xiang Hu; Feng-Liang Liu; Rui Bi; Bi-Qing Yang; Wen Zhang; Hao Guo; Ian Logan; Yong-Tang Zheng; Yong-Gang Yao (Molecular Neurobiology, 2016)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Cadmium Levels in Tissue and Plasma as a Risk Factor for Prostate Carcinoma: a Meta-Analysis - Liang Zhang; Yi Zhu; Rui Hao; Mengmeng Shao; Yunbo Luo (Biological Trace Element Research, 2016)

A new cell line derived from embryonic tissues of Holotrichia parallela (Coleoptera:Scarabaeidae) - Miao-Miao Li; Gui-Ling Zheng; Rui Su; Fang-Hao Wan; Chang-You Li (In Vitro Cellular & Developmental Biology - Animal, 2016)

Circulation and in vivo distribution of duck hepatitis A virus types 1 and 3 in infected ducklings - Shao-Li Lin; Ri-Chao Cong; Rui-Hua Zhang; Jun-Hao Chen; Lin-Lin Xia; Zhi-Jing Xie; Yu Wang; Yan-Li Zhu; Shi-Jin Jiang (Archives of Virology, 2016)

Identification of a regulatory element responsible for salt induction of rice OsRAV2 through ex situ and in situ promoter analysis - Yong-Bo Duan; Juan Li; Rui-Ying Qin; Rong-Fang Xu; Hao Li; Ya-Chun Yang; Hui Ma; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Molecular Biology, 2016)

Lysobacter chengduensis sp. nov. Isolated from the Air of Captive Ailuropoda melanoleuca Enclosures in Chengdu, China - Caifang Wen; Lixin Xi; Rong She; Shan Zhao; Zhongxiang Hao; Lu Luo; Hong Liao; Zhenrong Chen; Guoquan Han; Sanjie Cao; Rui Wu; Qigui Yan; et al. (Current Microbiology, 2016)

Metabolic responses to Lactobacillus plantarum contamination or bacteriophage treatment in Saccharomyces cerevisiae using a GC–MS-based metabolomics approach - Feng-Xia Cui; Rui-Min Zhang; Hua-Qing Liu; Yan-Feng Wang; Hao Li (World Journal of Microbiology and Biotechnology, 2015)

Flow regime of the three outlets on the south bank of Jingjiang River, China: an impact assessment of the Three Gorges Reservoir for 2003–2010 - Rui Zhang; Shuang-hu Zhang; Wei Xu; Ben-de Wang; Hao Wang (Stochastic Environmental Research and Risk Assessment, 2015)

Fecal Bacterial Composition of the Endangered Yangtze Finless Porpoises Living Under Captive and Semi-natural Conditions - Xiaoling Wan; Rui Ruan; Richard William McLaughlin; Yujiang Hao; Jinsong Zheng; Ding Wang (Current Microbiology, 2015)

Curcumin Promotes Cell Cycle Arrest and Inhibits Survival of Human Renal Cancer Cells by Negative Modulation of the PI3K/AKT Signaling Pathway - Hao Zhang; Weili Xu; Baolin Li; Kai Zhang; Yudong Wu; Haidong Xu; Junyong Wang; Jun Zhang; Rui Fan; Jinxing Wei (Cell Biochemistry and Biophysics, 2015)

Transcriptome profiling reveals auxin suppressed anthocyanin biosynthesis in red-fleshed apple callus (Malus sieversii f. niedzwetzkyana) - Xiao-Hao Ji; Rui Zhang; Nan Wang; Long Yang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

DNA methylation level of promoter region of activating transcription factor 5 in glioma - Xiao-min Hua; Juan Wang; Dong-meng Qian; Jing-yi Song; Hao Chen; Xiu-li Zhu; Rui Zhou; Yu-dan Zhao; Xiu-zhi Zhou; Ling Li; Li Zhang; Xu-xia Song; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Dependence of shrub canopy water storage on raindrop size in revegetated desert - Xin-ping Wang; Hao Zhang; Ya-feng Zhang; Rui Hu; Yan-xia Pan (Hydrological Sciences Journal, 2015)

Evaluation of yeasts from Tibetan fermented products as agents for biocontrol of blue mold of Nashi pear fruits - Hao Hu; Yang Xu; Huang-ping Lu; Rui Xiao; Xiao-dong Zheng; Ting Yu (Journal of Zhejiang University-SCIENCE B, 2015)

In Vivo Antioxidant Effects of Hydrolysate Derived from Waste Proteins of Mactra veneriformis - Rui Liu; Lingchong Wang; Wenwen Zheng; Hao Wu (Journal of Aquatic Food Product Technology, 2015)

Detection of burned areas from mega-fires using daily and historical MODIS surface reflectance - Rui Zhang; John J. Qu; Yongqiang Liu; Xianjun Hao; Chengquan Huang; Xiwu Zhan (International Journal of Remote Sensing, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Hyperacetylation of Histone H3K9 Involved in the Promotion of Abnormally High Transcription of the gdnf Gene in Glioma Cells - Zheng-Quan Yu; Bao-Le Zhang; Hai-Bo Ni; Ze-Hao Liu; Jian-Cun Wang; Qing-Xian Ren; Jian-Bing Mo; Ye Xiong; Rui-Qin Yao; Dian-Shuai Gao (Molecular Neurobiology, 2014)

A down-regulated epi-allele of the genomes uncoupled 4 gene generates a xantha marker trait in rice - Rui-Qing Li; Jian-Zhong Huang; Hai-Jun Zhao; Hao-Wei Fu; You-Fa Li; Guo-Zhen Liu; Qing-Yao Shu (Theoretical and Applied Genetics, 2014)

Snail regulated by PKC/GSK-3β pathway is crucial for EGF-induced epithelial-mesenchymal transition (EMT) of cancer cells - Zong-cai Liu; Xiao-hui Chen; Hai-xing Song; Hong-sheng Wang; Ge Zhang; Hao Wang; Dan-yang Chen; Rui Fang; Hao Liu; Shao-hui Cai; Jun Du (Cell and Tissue Research, 2014)

The influence of Caragana korshinskii shrub on soil and hydrological properties in a revegetation-stabilized desert ecosystem - Yan-Xia Pan; Xin-Ping Wang; Xin-Rong Li; Ya-Feng Zhang; Rui Hu; Hao Zhang (Hydrological Sciences Journal, 2014)

Isolation and functional characterization of a novel rice constitutive promoter - Juan Li; Rong-Fang Xu; Rui-Ying Qin; Hui Ma; Hao Li; Ying-Ping Zhang; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Cell Reports, 2014)

Gabapentin Enhances the Morphine Anti-Nociceptive Effect in Neuropathic Pain via the Interleukin-10-Heme Oxygenase-1 Signalling Pathway in Rats - Yu-Hua Bao; Quan-Hong Zhou; Rui Chen; Hao Xu; Lu-Lu Zeng; Xin Zhang; Wei Jiang; Dong-Ping Du (Journal of Molecular Neuroscience, 2014)

Modeling Carbon Fluxes Using Multi-Temporal MODIS Imagery and CO2 Eddy Flux Tower Data in Zoige Alpine Wetland, South-West China - Xiaoming Kang; Yanfen Wang; Huai Chen; Jianqing Tian; Xiaoyong Cui; Yichao Rui; Lei Zhong; Paul Kardol; Yanbin Hao; Xiangming Xiao (Wetlands, 2014)

miR-208-Induced Epithelial to Mesenchymal Transition of Pancreatic Cancer Cells Promotes Cell Metastasis and Invasion - Anan Liu; Chenghao Shao; Gang Jin; Rui Liu; Jun Hao; Bin Song; Liu Ouyang; Xiangui Hu (Cell Biochemistry and Biophysics, 2014)

Detection of respiratory syncytial virus fusion protein variants between 2009 and 2012 in China - Qiuling Xia; Lili Zhou; Caijing Peng; Rui Hao; Ke Ni; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Linli He; Daiyin Tian; Lijia Wang; et al. (Archives of Virology, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

The Neuroprotective Effects of Isoflurane Preconditioning in a Murine Transient Global Cerebral Ischemia–Reperfusion Model: The Role of the Notch Signaling Pathway - Hao-peng Zhang; Yan-yan Sun; Xiao-mei Chen; Li-bang Yuan; Bin-xiao Su; Rui Ma; Rui-ni Zhao; Hai-long Dong; Lize Xiong (NeuroMolecular Medicine, 2014)

Condensation of water vapour on moss-dominated biological soil crust, NW China - XIN-PING WANG; YAN-XIA PAN; RUI HU; YA-FENG ZHANG; HAO ZHANG (Journal of Earth System Science, 2014)

Molecular dynamics-based self-organizing molecular field analysis on 3-amino-6-arylpyrazines as the ataxia telangiectasia mutated and Rad3 related (ATR) protein kinase inhibitors - Hao Luo; Jianyou Shi; Lufei Lu; Feng Wu; Meng Zhou; Xueyan Hou; Wenjuan Zhang; Zhengyu Ding; Rui Li (Medicinal Chemistry Research, 2014)

Association between interferon gamma +874 T>A polymorphism and acute renal allograft rejection: evidence from published studies - Yu-Zheng Ge; Ran Wu; Rui-Peng Jia; Hao Liu; Peng Yu; Yan Zhao; Yu-Ming Feng (Molecular Biology Reports, 2013)

Potato leafroll virus (PLRV) and Potato virus Y (PVY) influence vegetative growth, physiological metabolism, and microtuber production of in vitro-grown shoots of potato (Solanum tuberosum L.) - Jing-Wei Li; Biao Wang; Xiao-Ming Song; Ren-Rui Wang; Long Chen; Hao Zhang; Zhi-Bo Zhang; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Magma mixing revealed from in situ zircon U–Pb–Hf isotope analysis of the Muhuguan granitoid pluton, eastern Qinling Orogen, China: implications for late Mesozoic tectonic evolution - Rui Liu; Jian-Wei Li; Shi-Jian Bi; Hao Hu; Mi Chen (International Journal of Earth Sciences, 2013)

Valproic acid reduces autophagy and promotes functional recovery after spinal cord injury in rats - Hai-Hu Hao; Li Wang; Zhi-Jian Guo; Lang Bai; Rui-Ping Zhang; Wei-Bing Shuang; Yi-Jia Jia; Jie Wang; Xiao-Yu Li; Qiang Liu (Neuroscience Bulletin, 2013)

Effects of grazing on CO2 balance in a semiarid steppe: field observations and modeling - Xiaoming Kang; Yanbin Hao; Xiaoyong Cui; Huai Chen; Changsheng Li; Yichao Rui; Jianqing Tian; Paul Kardol; Lei Zhong; Jinzhi Wang; Yanfen Wang (Journal of Soils and Sediments, 2013)

Heterogeneity of soil surface temperature induced by xerophytic shrub in a revegetated desert ecosystem, northwestern China - YA-FENG ZHANG; XIN-PING WANG; YAN-XIA PAN; RUI HU; HAO ZHANG (Journal of Earth System Science, 2013)

Molecular cloning and functional analysis of a blue light receptor gene MdCRY2 from apple (Malus domestica) - Yuan-Yuan Li; Ke Mao; Cheng Zhao; Xian-Yan Zhao; Rui-Fen Zhang; Hua-Lei Zhang; Huai-Rui Shu; Yu-Jin Hao (Plant Cell Reports, 2013)

Study on a comprehensive evaluation method for the assessment of the operational efficiency of wastewater treatment plants - Rui Xia Hao; Feng Liu; Hui Qin Ren; Shui Yuan Cheng (Stochastic Environmental Research and Risk Assessment, 2013)

Protective effects of Lycium barbarum polysaccharide on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion - Chen Rui; Li Yuxiang; Hao Yinju; Zhu Qingluan; Wu Yang; Zhao Qipeng; Wang Hao; Ma Lin; Liu Juan; Zhao Chengjun; Jiang Yuanxu; Wang Yanrong; et al. (Journal of Molecular Histology, 2012)

Construction of self-cloning, indigenous wine strains of Saccharomyces cerevisiae with enhanced glycerol and glutathione production - Rui-Ying Hao; Yan-Lin Liu; Zhao-Yue Wang; Bo-run Zhang (Biotechnology Letters, 2012)

A novel hydrolytic product from flesh of Mactra veneriformis and its bioactivities in calcium supplement - Lingchong Wang; Shiyong Chen; Rui Liu; Hao Wu (Journal of Ocean University of China, 2012)

Mantle-derived noble gases in ore-forming fluids of the granite-related Yaogangxian tungsten deposit, Southeastern China - Rui-Zhong Hu; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Jian-Tang Peng; You-Qiang Qi; Li-Yan Wu; Wen-Feng Wei (Mineralium Deposita, 2012)

Stratigraphic architecture and computer modelling of carbonate platform margin, late ordovician Lianglitage formation, Central Tarim Basin - Hao Li; Changsong Lin; Yanmei Zhang; Rongxi Zhang; Zhifeng Rui; Lili Huang (Journal of Earth Science, 2012)

Effects of Danggui Buxue Tang, a traditional Chinese herbal decoction, on high glucose-induced proliferation and expression of extracellular matrix proteins in glomerular mesangial cells - Hao-Liang Ke; Ying-Wen Zhang; Bi-Fa Zhou; Rui-Tang Zhen (Natural Product Research, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Implication of genetic variants near TMEM18, BCDIN3D/FAIM2, and MC4R with coronary artery disease and obesity in Chinese: a angiography-based study - Hao Huang; Zhi Zeng; Li Zhang; Rui Liu; Xian Li; Ou Qiang; Yucheng Chen (Molecular Biology Reports, 2012)

Modeling impacts of climate change on carbon dynamics in a steppe ecosystem in Inner Mongolia, China - Xiaoming Kang; Yanbin Hao; Changsheng Li; Xiaoyong Cui; Jinzhi Wang; Yichao Rui; Haishan Niu; Yanfen Wang (Journal of Soils and Sediments, 2011)

Cloning and characterisation of a novel 2,4-dichlorophenol hydroxylase from a metagenomic library derived from polychlorinated biphenyl-contaminated soil - Yang Lu; Ying Yu; Rui Zhou; Wei Sun; Chunyan Dai; Pei Wan; Lanying Zhang; Dongyun Hao; Hejun Ren (Biotechnology Letters, 2011)

Effect of host plants on development and reproduction of Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae) - Rui-Ting Ju; Feng Wang; Fang-Hao Wan; Bo Li (Journal of Pest Science, 2011)

He and Ar isotopic compositions and genetic implications for the giant Shizhuyuan W–Sn–Bi–Mo deposit, Hunan Province, South China - Li-Yan Wu; Rui-Zhong Hu; Jian-Tang Peng; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Qiao-Yun Wang; Ya-Ying Liu (International Geology Review, 2011)

A stand dynamic model for red pine plantations with different initial densities - Shusheng Li; Qingyu Hao; Edwin Swift; Charles P.-A. Bourque; Fan-Rui Meng (New Forests, 2011)

Scutellarin exerts its anti-hypertrophic effects via suppressing the Ca2+-mediated calcineurin and CaMKII signaling pathways - Zhen-Wei Pan; Ying Zhang; Dong-Hua Mei; Rui Zhang; Jing-Hao Wang; Xiang-Ying Zhang; Chang-Qing Xu; Yan-Jie Lu; Bao-Feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Fast and dynamic generation of linear octrees for geological bodies under hardware acceleration - Hao Deng; LiQiang Zhang; XianCheng Mao; JingTao Ma; ZhiZhong Kang; JunHuan Peng; XiaoPing Rui; Liu Liu (Science China Earth Sciences, 2010)

Fingerprint analysis of Lingzhi (Ganoderma) strains by high-performance liquid chromatography coupled with chemometric methods - Xian-Min Shi; Jing-Song Zhang; Qing-Jiu Tang; Yan Yang; Rui-Xia Hao; Ying-Jie Pan (World Journal of Microbiology and Biotechnology, 2008)

Effect of vinasse irrigation on the activity of three enzymes and agronomic characters at seedling stage of sugarcane - Wang Yi-Ding; Mo Yun-Chuan; Wang Wei-Hao; Li Yang-Rui; Ye Yan-Ping (Sugar Tech, 2006)

A Study of Conservation Genetics in Cupressus chengiana, an Endangered Endemic of China, Using ISSR Markers - Bingqing Hao; Wang Li; Mu Linchun; Yao Li; Zhang Rui; Tang Mingxia; Bao Weikai (Biochemical Genetics, 2006)